Structure-based virtual screening identifies dicoumarol as a potent InhA inhibitor against Nocardia seriolae infection in largemouth bass (Micropterus salmoides) - Jin-Lai Gu; Chen-Wang Lu; Lin-Feng Kuang; Jie He; Zheng-Ran Jian; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Zheng-Yang Zhou; Ming-Zhu Liu; Peng-Fei Li; Er-Long Wang; et al. (Aquaculture, 2027)

Digital model reconstruction of shield tunnels based on 3D point cloud - Yu Li; Huai-Na Wu; Dong-Lin Feng; Si-Qi Yang; Ren-Peng Chen (Tunnelling and Underground Space Technology, 2026)

Postharvest biocontrol potential and mechanisms of Fusarium tricinctum against pear black spot caused by Alternaria alternata - Yun-Feng Liu; Zheng-Yu Zhu; Na Liu; Bo-Lin Li; Xue-Li He; Yu-Xing Zhang (Postharvest Biology and Technology, 2026)

Polystyrene nanoparticles impair endometrial decidualization in early pregnant mice via oxidative stress-driven autophagy suppression and ferroptosis induction - Li-Qing Wang; Qian-Feng Qiao; Huang-Nian You; Yi-bin Zheng; Xiao-Mei Wu; Wen-Jie Yu; Zeng Liu; Wen-Juan Song; Lin-Hong Zhang; Jia-Rui Hu; Xin-Yu Mao; Yong-Jiang Zhou (Food and Chemical Toxicology, 2026)

Endothelial-Mesenchymal transition in cerebrovascular diseases: molecular mechanisms and promising pharmacological strategies - Jinlin Xiao; Canyang Yu; Dianda Chen; Feng Lin; Shuhua Zhang; Daya Luo; Erming Zeng (Molecular Biology Reports, 2026)

Tirzepatide improves neutrophilic inflammation in obese asthmatic mice by downregulating Th17 cell differentiation - Lu Sun; Su-Yan Yao; Zhong-Fu Zuo; Sheng-Xue Yu; Hong-Dan Yu; Qing-Lin Sun; Han-Song Zheng; Yang Hou; Si-Jing Lu; Tie-Feng Yao (Molecular Biology Reports, 2026)

Zinc-binding protein metallothionein 3 protects vascular smooth muscle cells from ferroptosis via blocking lysosomal degradation of GPX4 - Wenxin Lin; Xin Feng; Jingjie Chen; Bo Huo; Xian Guo; Molin Yang; Ding-Sheng Jiang; Linling Yu; Yue Chen (Journal of Molecular Medicine, 2026)

Targeting EFEMP1 enhances chondrogenesis and inhibits hypertrophic differentiation in a spontaneous osteoarthritis mouse model - Yuhan Chang; Pei-Heng Jiang; Yung-Heng Hsu; Yu-Chih Lin; Chih-Chien Hu; Yi-Zhen Li; Steve Wen-Neng Ueng; Mei-Feng Chen (Journal of Molecular Medicine, 2026)

Genotype-dependent Food Competition Behaviors in Male Fruit Flies Under Distinct Thermal Conditions - Rui Han; Jun Zhang; Jia-Xin Wang; Yu-Xin Wang; An-Qi Wen; Hao-Wei Wang; Xu Liang; Xiang-Haoran Lin; Lin-Xiang Liu; Ke-Jing Feng (Journal of Insect Behavior, 2026)

Dihydrolipoamide dehydrogenase promotes hepatocellular carcinoma progression and modulates cuproptosis-dependent cell death - Mao-feng Zhong; Yu-yu Guo; Yuan Tian; Tian-xiao Zheng; Lu-yuan Zhu; Juan Du; Wan-fu Lin (Functional & Integrative Genomics, 2026)

Two-stage instance segmentation method based on Tunnel-SPVNet for shield tunnel segments - Yu Li; Huai-Na Wu; Dong-Lin Feng; Yu-Liang Li; Ren-Peng Chen (Tunnelling and Underground Space Technology, 2026)

First record of Brachyphyllum (Cheirolepidiaceae) from the Lower Jurassic of the Ordos Basin, China: Paleogeographic and paleoclimatic implications linked to T-OAE - Chao-Hui Wei; Yun-Feng Li; Chang-Lu Zhang; Xiao Tan; Fei Liang; Chun-Lin Sun; Tao Li; Yu-Ling Na (Review of Palaeobotany and Palynology, 2026)

Palaeoenvironmental evolution and stage-dependent organic matter enrichment in the Late Permian Longtan Formation, Upper Yangtze Block, South China - Hai-Feng Chen; Xin Jin; Marcello Caggiati; Ting-Cong Ren; Bo Luo; Lin-Hao Fang; Hua-Wen Cao; Yang Liu; Chang-Cheng Huang; Bin Xiao; Zi-Han Ma; Hui-Dong Yu; et al. (Sedimentary Geology, 2026)

Cyprosulfamide effectively alleviates flusulfinam phytotoxicity in maize with enhanced dissipation - Yu Wang; Junqi Zhu; Mingdong Deng; Huijin Lin; Huanyu Zhou; Wenyu Dai; Ya Zhou; Tengfei Zhang; Yanmei Liu; Huihua Tan; Feng Zhao (Pesticide Biochemistry and Physiology, 2026)

Discovery of cytotoxic 1,4-benzodioxane oxyneolignan analogues from Glechoma longituba - Ming-Ming Yuan; Xi Wu; Yang-Bing Zheng; Yu-Lin Feng; Er-Lei Xie (Phytochemistry, 2026)

Phylogenomics of Tanypodinae (Diptera: Chironomidae) redefines relationships in Procladiini and Tanypodini and supports a new tribe - Xiu-Ru Xiao; Yi-Ni Zhang; Hai-Feng Xu; Zhi-Chao Zhang; Yu-Yi Jiang; Yan-Xin Chen; Chen-Hong Li; Bing-Jiao Sun; Fabio Laurindo da Silva; Xiao-Long Lin (Molecular Phylogenetics and Evolution, 2026)

Endocrine-disrupting chemical-induced gene networks confer coronary heart disease risk revealed by causal inference and single-cell analyses - Tao Yao; Yun-Lu Lin; Luo-Xiang Fang; Yu-Tian Wang; Lan-Feng Zhou; Ning Zhang; Gang Chen (Food and Chemical Toxicology, 2026)

Metagenomic indications of potential pathogen-associated and antibiotic resistance risks following UV–chlorine disinfection in sprout production - Yufei Wei; Lin Zhu; Xiangfu Jin; Huangli Yao; Shanshan He; Pu Feng; Feihong Yu; Yulu Xiang; Zhiheng Li; Shanying He (Environmental Pollution, 2026)

Numerical investigation on collapse-induced impact among reinforced concrete frame structures based on DEM - Qian-Qian Yu; Chen-Chen Lu; Xiang-Lin Gu; Tian Zhou; Feng Lin (Engineering Structures, 2026)

pH-Controlled co-adsorption and selective separation for Cs+ and Sr2+ by an ultra-stable layered titanoniobate - Zhi-Hua Chen; Hao-Wei Lin; Bu-Bu Gao; Hai-Yan Sun; Tian-Yu Pan; Mei-Ling Feng; Xiao-Ying Huang (Chemical Engineering Journal, 2026)

Arginine and putrescine ameliorate heat stress-induced testicular inflammation and apoptosis via inhibiting endoplasmic reticulum stress in mice - Kun Wu; Chenglong Yu; Guangmang Liu; Yong Zhuo; Bin Feng; Lianqiang Che; Shengyu Xu; Lun Hua; Jian Li; Zhengfeng Fang; De Wu; Yan Lin (Theriogenology, 2026)

Climate-adaptive optimization of low-carbon slag–fly ash cementitious systems considering CO2 emissions and carbonation durability - Feng Sun; Hongzhi Zhang; Runsheng Lin; Qingliang Yu; Xiao-Yong Wang (Sustainable Chemistry and Pharmacy, 2026)

Integrated transcriptomic and metabolomic analyses reveal the involvement of AtGASA1 and AtGASA4 in salicylic acid pathway-associated immune responses in Arabidopsis - Jian-Bo Song; Ya-Ru Li; Zi-Xin Zhao; Xian-Zhi Zuo; Cai-Feng Wang; Min Huang; Shu-Fan Liu; Yu-Fan Chen; Wen-Qian Song; Lin Wang; Ying-Juan Wang; Xuan Huang (Plant Science, 2026)

Size matching between laccase and carrier via tunable diamine-derived flexible spacer arms for enhanced phenolic wastewater degradation - Jie Zhang; Yiqi Gong; Zhipeng Qin; Xinyi Liu; Jiao Yu; Tao Feng; Wan Zhang; Wenjing Lin; Kaiyue Kang; Xuemei Tan; Lin Zhuo; Ruiqi Wang; et al. (Journal of Water Process Engineering, 2026)

Connectivity and function determine whether ponds act as sources or sinks of nonpoint-source phosphorus - Xiaofen Bai; Chen Lin; Ke Song; Wenlan Feng; Junfeng Xiong; Siyu Ge; Wanqian Yu; Jianchun Chen; Yijun Tong (Journal of Hydrology, 2026)

Ru-Co bimetallic catalysts with synergistic crystalline phase regulation and hydrogen spillover for deep hydrodeoxygenation of lignin oil - Jing-jing Wu; Jia-yuan Tian; Feng Lin; Yu-long Ma; Yong-gang Sun; Pei Ma; Shuai-lei Li; Xue Zhang; Yi-shu Ma; Xiao-lin Xue (Journal of Environmental Chemical Engineering, 2026)

Divergent activation of a glutathione-tryptophan module by cysteine and hydrogen sulfide enables metabolic recovery from cyanide poisoning in rice - Yi Kang; Xing-Hui Feng; Cheng-Zhi Li; Yu-Juan Lin; Xiao-Zhang Yu (Journal of Environmental Chemical Engineering, 2026)

Hydroclimatic trend and millennial abruptions in southwestern China since the last deglaciation - Yan Yang; Hai Xu; Jing Wang; Ye Yang; Yunping Song; Jin Zhang; Siwei Shi; Yanpeng Li; Lin Shi; Kaiyang He; Yu Feng; Sheng Xu (Global and Planetary Change, 2026)

N-3 PUFA deposition and esterification patterns drive aroma profile remodeling in the longissimus dorsi of pigs fed flaxseed oil - Yingsen Liu; Longzhu Zhou; Luxi Lin; Shijie Wang; Yiyu Yin; Haoyang Han; Huihui Tian; Miaomiao Dong; Pingyang Li; Youyou Yang; Xiaohui Feng; Weihai Xing; et al. (Food Chemistry, 2026)

Corrigendum to “flexible chain-engineered conjugated polymers with phosphonic acid anchors for synergistic photocatalysis-adsorption uranium extraction” [Chem. Eng. J. 521 (2025) 166451] - Yuanping Jiang; Feng Wang; Junshuo An; Xingfang Yu; Menghan Cao; Guohang He; Danning Xu; Jiajian Yang; Kai Zhang; Yunxiu Zhang; Lin Xu; Zuojia Li; et al. (Chemical Engineering Journal, 2026)

Tailoring Cu-doped SmMn2O5 with rich Mn4+ active sites for highly efficient and selective ultra-low temperature photothermal NOx catalytic reduction - Mingxia Wu; Jiale Cheng; Yu Wang; Siying Zhang; Yi Li; Ruixue Bai; Chunming Yang; Lin Liu; Feng Fu; Jun Wan (Chemical Engineering Journal, 2026)

Causal inference reveals the dominant role of climate-adaptation coupling in future potato production - Zhihao He; Tengcong Jiang; Lin Zhu; Ning Yao; Yi Li; Hao Feng; De Li Liu; Liang He; Jianqiang He; Qiang Yu (Agricultural Systems, 2026)

Targeting multidimensional nociceptor-tumor interactions to mitigate immune evasion of cancer - Aojia Jin; Jiaxing Pan; Jingyi Su; Shutong Lin; Xiaohan Shi; Yu Zhang; Jing Feng; Bruno De Geest; Twan Lammers; Tong Ji; Gang Jin; Zhiai Xu; et al. (Science Bulletin, 2026)

Single-cell multi-omics dissects transcript isoform and immune repertoire dynamics in human immunosenescence - Yuhui Zheng; Ze-Hui Ren; Yafei Yang; Wenteng Liu; Fupeng Li; Yajun Zuo; Tao Zeng; Xue Wang; Xiumei Lin; Xinyue Zhu; Baibing Guan; Wenwen Zhou; et al. (Science China Life Sciences, 2026)

A parallel electrical impedance tomography system for tissue-resolved imaging of relative stem conductivity dynamics in sunflower under PEG-induced stress - Liu-Deng Zhang; Ao-Wen Wang; Bing-Zhou Chen; Yang Xiang; Yu-Bin Lin; Chang Chen; Huan-Rui Ge; Ke-Lei Xia; Li-Feng Fan; Lan Huang; Zhong-Yi Wang (Biosystems Engineering, 2026)

Investigation on performance-based deformation control criteria for shield tunnel linings under typical adjacent construction disturbances - Dong-Lin Feng; Yu Li; Huai-Na Wu; Si-Qi Yang; Ren-Peng Chen (Tunnelling and Underground Space Technology, 2026)

Lactobacillus helveticus MB2-1 powders prepared using different drying strategies reshape dominant intermolecular interaction patterns and structural network formation during fermentation of coconut-based yogurt alternatives - Jianwei Zang; Yimeng Kou; Yibo Shi; Xiaotong Hao; Shiyuan Feng; Chunling Meng; Jiamin Xu; Di Yu; Tao Lin; Kai Ma; Changliang Zhang; Mingsheng Dong; et al. (Food and Bioproducts Processing, 2026)

Targeting the phenolic A-ring unifies the toxicology and remediation of environmental estrogens in aquatic environments - Liu-Feng Yu; Yi-Lin Ye; Jie Zhou; Yu-Han Jin; Yu-Han Sun; Li-Xia Yan; Chen-Man Li; Jia-Yi Chang; Wei-Jie Chen; Feng Liu; Yong-Wei Feng; Xiao-Dong Huang; et al. (Environmental Research, 2026)

Coupled effect of crack inclination and microstructure on the mechanical behavior of soils - Zhao-Lin Cai; Yu-Jun Cui; Chao-Sheng Tang; Qing Cheng; Zhi-Xiong Zeng; Xin-Lun Ji; Tao Wang; Hao Wang; Hai Wang; Jun-Feng Ren (Engineering Geology, 2026)

Dopamine-functionalized gel for rapid iodine and triiodide capture through adsorption-conversion pathway in aqueous media - Xinxin Li; Lin Jiang; Feng Lin; Zikang He; Rongzhi Tang; Yu Tan (Chemical Engineering Journal, 2026)

Genomic mining of the terpene synthase family in magnoliids reveals novel clades - Fang Wang; Qiongqiong Lin; Zijian Zhang; Yunyang Yu; Mengxue Feng; Meixiu Lin; Yongjuan Ren; Liuming Luo; Xin Liu; Huan Liu; Sunil Kumar Sahu; Tong Wei; et al. (The Nucleus, 2026)

Unveiling the Impact of Copper Metabolism on Epithelial-Mesenchymal Transition of Triple-Negative Breast Cancer: Identification of Therapeutic Targets - Kai Zhuang; Lin Yan; Muhammad Waqas; Haixin Feng; Siqi Tang; Haoqi He; Xinshi Yu; Yanling Wang; Zunnan Huang (Interdisciplinary Sciences: Computational Life Sciences, 2026)

BRAIN-DISC: a novel analytical approach integrating data-driven brain pattern discovery with cohort studies for evaluating findings in brain modulation interventions - Meishan Ai; Adam Turnbull; Kanhao Zhao; Yang Liu; Yu Zhang; Feng Vankee-Lin (GeroScience, 2026)

Baicalin alleviates repeated superovulation induced ovarian dysfunction and oocyte impairment by suppressing excessive glycolysis - Lin-Feng Li; Hao Shen; Zhi-Min Qi; Tian Luo; Sheng-Ming Liu; Li-Li Ou; Chang-Long Xu; Yu Liu (Theriogenology, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Phytohormonal orchestration of plant phosphate starvation responses - Kai-Kai Lu; Ru-Feng Song; Yu-Pu Fan; Ling-Yu Xu; Bo-Hao Chen; Shu-Xian Li; Meng-Tian Sun; Guo-Mao Liu; Xiao-Li Huang; Lin Li; Xin-Ru Guo; Feng Ren; et al. (Journal of Plant Physiology, 2026)

Divergent trends in global vegetation sensitivity to soil moisture and atmospheric dryness - Mengxiang Kong; Yu Feng; Ziqi Lin; Chunmiao Zheng (Journal of Hydrology, 2026)

Synergistic effects of iron-based metal-organic frameworks on enhancing electron transfer and shaping microbial communities for ethanol-driven carboxylate chain elongation - Weizhong Huo; Jing Yu; Zhaofan Lin; Xutong Pang; Feng Gao; Sebam Gill; Youzhi Miao; Qirong Shen; Ruifu Zhang (Journal of Environmental Chemical Engineering, 2026)

Corrigendum to “Limonene-loaded nanostructured lipid carriers incorporated in hydrogels: Enhanced acid stability and controlled release properties” [Food Res. Int. 214 (2025) 116601] - Simin Feng; Yitong Tian; Jiahao Yu; Yang Lin; Alan Giovanini de Oliveira Sartori; Ping Shao (Food Research International, 2026)

Comprehensive analysis of microbial community assembly and metabolic dynamics reveals the effects of environmental acidity on flavor formation pathways during the Zhejiang rosy vinegar fermentation process - Cheng-Hao Jin; Yong-Zhu Zhang; Wen-Tian Song; Peng Wang; Chang-Ling Wu; Lin-Mei Liang; Wei Feng; Xiao-Tao Sun; Xing-Quan Liu; Guan-Yu Fang (Food Research International, 2026)

Beyond conventional biochar: Sulfur-iron modification unlocks redox control for synergistic cadmium-arsenic sequestration in paddy soils - Zihao Liang; Hua Lin; Honghu Zeng; Sze-Mun Lam; Jin-Chung Sin; Xuehong Zhang; Guo Yu; Mi Feng; Yanpeng Liang; Huawei Li; Yuxi Lu; Gongning Chen (Environmental Research, 2026)

Coupled water-heat-salt transport in the vadose zone of loess: A numerical framework considering phase changes and ionic fractionation - Shi-Feng Lu; Jia-Qi Yu; Meng-Yuan Ma; Xiao-Lin Huang; Ling Xu (Computers and Geotechnics, 2026)

Atomically precise ferrocene-based Fe/Mn nanocluster for solar-driven cycloaddition of epoxides with carbon dioxide - Xue-Feng He; Chun-Yang Li; Yu-Lin Jiang; Wan-Yu Zhu; Qiu-Hong Cheng; Kun Huang; Da-Bin Qin; Xiang-Yu Zhang (Chemical Engineering Journal, 2026)

Construction of conductive polyimide dressings for accelerated wound healing via an interfacial compatibility optimization and polyelectrolyte complexation synergistic strategy - Lizhi Lin; Kexiang Fan; Hang Luo; Jueying Yang; Huaping Liang; Yongqiang Feng; Lijie Li; Kelin Peng; Yu Chen (Chemical Engineering Journal, 2026)

Reaction-generated secondary phase advances electronic-phonon decoupling and boosted mechanical performance in Bi0.42Sb1.58Te3 alloys - Yi-lin Liu; Hao Liang; Chong-Yu Wang; Jiang-Hu Yu; Kang Yue; Qian Deng; Ju Rong; Jing Feng; Zhen-Hua Ge (Chemical Engineering Journal, 2026)

Bioinspired self-assembled gradient Janus bilayer aerogel enabling coupled solar desalination and purification of multicomponent oily emulsions - Peng Pi; Yu Feng; Wen Jung Li; Ling Pan; Youxi Lin; Linxi Hou; Zihao Huang; Qinwei Wang; Xuhui Wang; Zhiying Ren (Chemical Engineering Journal, 2026)

Structural characterization and in vitro evaluation of the hypolipidemic activity of the HSP-Ia, a bioactive polysaccharide derived from hemp (Cannabis sativa L.) seeds - Ya-Zhi Wang; Lan-Yan Li; Yong-Zhe Chen; Dong-Xue Song; Feng-Yu Liu; Zi-Yi Zhang; Hong-Lin Guo; Jun Li; Tao Liu; Chen-Feng Ji; Shou-Dong Guo (Carbohydrate Polymers, 2026)

Proteomic comparison of human neural cell-derived extracellular vesicles and parental cells from Alzheimer’s disease and cognitively normal individuals - Jia-Yan Xin; Jie Liu; Hao-Min Dong; Hai-Lun Yu; Zhong-Song Xiao; Jian-Ni Hu; Qiu Jiang; Yu-Peng Zhu; Lin Feng; Yun Feng; Yu-Juan Jia; Zi-Yu Yuan; et al. (Science China Life Sciences, 2026)

TRIM9-Mediated Degradation of SMAD4 Promotes Pyroptosis and Disruption of the Endothelial Barrier in Aortic Dissection Disease - Hong-Qin Bi; Tan Yang; Sheng-Lin Ling; Feng-Xu Yu (Cardiovascular Toxicology, 2026)

Solar-tracking photovoltaic systems enhance soil carbon accumulation in desert steppe through microclimate-mediated changes in vegetation and microbial communities - Fei Huang; Bo Wang; Jie Feng; Dongya Liu; Yu Li; Gao-Lin Wu; Zhigang Li (Applied Soil Ecology, 2026)

Insular divergence and host-associated diversification in ovoid-gall Daphnephila (Diptera: Cecidomyiidae) from Taiwan, with description of a new species - Sheng-Feng Lin; Tung-Chuan Chiang; Hsuan Chang; Yu-Chu Weng; Man-Miao Yang (Applied Entomology and Zoology, 2026)
The Old World cecidomyiid genus Daphnephila is primarily associated with Machilus (Lauraceae) plants and exhibits exceptionally high gall diversity in Taiwan. At present, six described species correspond to only seven of 40 known Daphnephila gall morphospecies on the island. In this study, we clarified the species identities of Taiwanese Daphnephila inducing long ovoid-galls and ovoid-galls on the leaves of five Machilus plants, and explored their diversification using molecular evidence. Accordingly, two species, D. yukawai sp. n. and D. taiwanensis , were recognized based on morphological characteristics and species delimitation method (Assemble Species by Automatic Partitioning). The former species utilizes only the endemic M . mushaensis , primarily inducing ovoid-galls along the major leaf vein, whereas the latter species associates with five Machilus species and induces two gall types on various leaf parts. Notably, when sympatric with D. yukawai sp. n., D. taiwanensis exhibits character displacement of galling habit, forming long ovoid-galls along the minor leaf veins. Furthermore, the COI-based IQ tree supported: (1) a single origin of East Asian ovoid-gall Daphnephila species, (2) the sister-group relationship between the Taiwanese lineage and a Chinese species, and (3) the role of M. mushaensis as the probable ancestral host of the Taiwanese lineage, including D. taiwanensis. These results suggest that D. taiwanensis colonized additional Machilus hosts after diverging from D. yukawai sp. n. Taken together, our findings indicate that novel plant associations and shifts in galling sites may have facilitated diversification in Daphnephila cecidomyiids, contributing to the remarkable richness of Daphnephila galls in Taiwan.

Taxonomy of Neostagonosporella on Chimonobambusa with descriptions of two new taxa - Xiu-Lan Xu; Yu Deng; Li-Ping Gao; Qian-Ying Huang; Wei Liu; Li Zhuang; Fei Chen; Qian-Gang Xiao; Zhen Zeng; Feng Liu; Qi-Rong Sun; Ying-Gao Liu; et al. (Mycological Progress, 2026)

A 44-min periodic radio transient in a supernova remnant - Di Li; Mao Yuan; Lin Wu; Jingye Yan; Xuning Lv; Chaowei Tsai; Pei Wang; Jiaqi Zhao; Weiwei Zhu; Li Deng; Ailan Lan; Renxin Xu; et al. (Science Bulletin, 2026)

Management regimes underpin soil carbon accrual following forest conversion to tea plantations across China - Lin Chen; Li Ruan; Yu Duan; Biao Feng; Yixuan Bai; Scott X. Chang; Teng Yang; Yowhan Son; Yuwei Yuan; Shangwen Fu; Chuan Yue; Zhongyi Li; et al. (Science Bulletin, 2026)

Tolypaxillines A–J: indole diterpenoids with neuroprotective activities from a soil-derived fungus Tolypocladium album DWS131 - Yu-Fen Tan; Xing-Yi Chen; Chao Wang; Ai-Lin Liang; Wen-Yu Lu; Le-Meng Feng; Qi Huang; Yue-Ping Jiang; Shao Liu; Xiao-Bo Xia; Jing Li; Wen-Xuan Wang (Phytochemistry, 2026)

Application of short-wave infrared spectroscopy in sandstone-type uranium deposits: A case study of the Yuejin-II uranium deposit in the Qaidam Basin, China - Wen-Yi Wu; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Yi-Han Lin; Yan Zhou; Chen Zhang; Ruo-Yu Shi; Xue-Feng Gao; Duo Wang; Bin Guo; Xiao-Qin Xu; et al. (Journal of Geochemical Exploration, 2026)

Cretaceous sediment provenance, dispersal systems, and tectono-paleogeography of the western Tarim Basin, Northwest China: Far-field effects of Neo-Tethyan flat subduction - Hong-Xiang Wu; Feng-Qi Zhang; Cai-Yun Wang; Xiao-Gan Cheng; Kai-Xuan An; Yildirim Dilek; Cai Chen; Yu-Qing Zhang; Xiu-Bin Lin; Shuan-Hong Zhang; Han-Lin Chen (Global and Planetary Change, 2026)

Green and sustainable dual-pathway strategies for high-efficiency photoconversion of ergosterol to vitamin D₂ from agaricus bisporus - Jiahao Yu; Yan Tang; Yang Lin; Simin Feng; Mofei Shen; Ping Shao (Food Chemistry, 2026)

Enhancing Ore Recovery and Profitability Through Blast-Aware Dig-Limit Optimization in Open-Pit Mining - Zhi Yu; Lin-Feng Du; Zong-Xian Zhang; Ming-Qing Huang; Jian-Hua Hu; Jian Zhou; Xing-Qi Cai (Rock Mechanics and Rock Engineering, 2026)

Lactate acts as a metabolic brake on inflammation by repressing NLRP3 transcription via NF-κB inhibition - Hsin-An Lin; Hsin-Chung Lin; Chih-Yung Chiou; Hao-Hsuan Peng; Yu-Jen Chen; Bo-Ying Bao; Kuen-Jou Tsai; Chao-Feng Lin; Chieh-Tien Shih; Sheng-I. Hu; Kuo-Yang Huang; Lih-Chyang Chen (Inflammation Research, 2026)

Cerebellar Contributions to Cognitive Affective Function and Postural Tremor in Neurological Wilson’s Disease - Ping Jin; Dong-xu Yin; Yu-xie Huang; Zi-wen Li; Xin-feng Ma; Kang Lin; Ya-yun Xu; Wei-ming Gao; Qun-rong Ye; Yong-zhu Han; Gong-qiang Wang (The Cerebellum, 2026)

A chimeric PRRSV vaccine with dual Nsp2 deletions elicits cross-lineage protection against heterologous challenge - Zhuo-ran Miao; Bo Han; Ling-zhai Meng; Zhen-hui Ren; Yi-han Lu; Jing Li; Wen Sun; Shi-qin Zhang; Jia Wang; Jin-jin Ma; Jia-Lu Li; Yu-tong Zhu; et al. (The Veterinary Journal, 2026)

Mapping global floodplain development disparities highlights drivers behind intensifying flood losses - Zhiyang Lan; Wenbin Liu; Rafael Jan Pablo Schmitt; Chaoyang Wu; Yingjie Li; Deliang Chen; Peirong Lin; Kailiang Yu; Xinli Bai; Kaihao Zheng; Tingting Wang; Hong Wang; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Orchestrated multicopper heterostructural motifs in MOF enable tandem CO2 valorization via photothermal-photocatalytic C–N coupling - Jian-Qiang Zhao; Hui-Li Zheng; Yu-Jia Cheng; Cheng-Xia Chen; Xiong-Feng Ma; Zheng Yin; Jia-Wei Li; Dong-Dong Ma; Hua Lin; Xin-Tao Wu; Cheng-Yong Su; Qi-Long Zhu (Science Bulletin, 2026)

Multifunctional Cu2O@Ag probe for ultra-sensitive SERS detection and inhibition of Escherichia coli O157: H7 - Hao Jiang; Yu-Qing Wang; Huan Cheng; Shi-Ying Fu; Hongmei Li; Jia-Sheng Lin; Yue-Jiao Zhang; Jian-Feng Li (Food Chemistry, 2026)

Chitosan oligosaccharides activate PPARγ to alleviate aflatoxin B1-induced testicular inflammation and barrier damage - Pei-Yu Dong; Zhuang-Bing Li; Sheng-Lin Liang; Xi-Feng Zhang; Yan-Ni Feng; Wei You (Food Bioscience, 2026)

Single-cell sequencing reveals metabolic reprogramming and immune regulation underlie the maintenance of teleost granulomas - Zheng-Yang Zhou; Zheng-Ran Jian; Jin-Lai Gu; Xin-Yuan Jiang; Jie He; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Chen-Wang Lu; Lin-Feng Kuang; Ming-Zhu Liu; Peng-Fei Li; et al. (Fish & Shellfish Immunology, 2026)

Adapting nitrogen fertilization to increase cotton productivity sustainably and decrease nitrogen loss to the environment - Yu Tian; Feng Shi; Xianzhe Hao; Xiaojuan Shi; Junhong Li; Humei Zhang; Nannan Li; Zemin Li; Hairong Lin; Jiongchao Zhao; Honghai Luo; Karine Chenu (Field Crops Research, 2026)

From air to adipose: Investigating PM2.5-bound chlorinated paraffins and overweight/obesity in Chinese children and adolescents - Qi Yang; Hai-Xin Tu; Yu He; Ya-Qin Zhang; Muhammad Amjad; Jing-Fu Lai; Jing-Wen Huang; Yun-Ting Zhang; Wan-Ting He; Li-Xia Liang; Wen-Wen Bao; Yang Zhou; et al. (Environmental Research, 2026)

N-heterocycle substitution engineering on tetra-coordinated boron framework for high-performance narrow-band bidentate Pt(II) complex phosphor - Zhao Feng; Siqi Liu; Ziyi Chen; Xiong Huang; Jie Zhang; Ruiqin Zhu; Lin Ma; Yue Yu; Daokun Zhong; Yuanhui Sun; Xiaolong Yang; Guijiang Zhou (Chemical Engineering Journal, 2026)

Coupling a Ti/SnO₂-Sb@TiO₂/SnO₂ photoanode with Ce-cu/BC particle electrodes for synergistic ofloxacin detoxification: Insights into mechanisms and transformations - Siyu Yi; Lei Yu; Lin Liu; Zhiwei Fan; Yingke Zhou; Huizhen Zhao; Fuping Li; Xuanming Feng; Hao Wang (Chemical Engineering Journal, 2026)

Lactiplantibacillus Plantarum O126 Postbiotics Boost growth, Antioxidant levels, Disease resistance, and Gut Health in Sea Cucumber (Apostichopus japonicus) - Feng-Li Chen; Hui-Ting Zhao; Wei Gu; Zong-Xiu Wu; Jing-Wen Xiang; Qing Yang; Yu-Lin Yang; Lei Tan; Meng-Xia Sun; Wei Cong; Shu Li; Bin-Tong Yang; et al. (Probiotics and Antimicrobial Proteins, 2026)

Application of antimony stable isotopes in revealing the source and migration of Sb in rivers - Xinyu Li; Guangyi Sun; Yunjie Wu; Yu Lin; Chenmeng Yang; Xinbin Feng (Water Research, 2026)

Quantifying the cooling effects of multi-scale urban blue-green spaces on surrounding local climate zones in hot and humid climatic areas - Lin Liu; Yilin Wang; Xin Feng; Mengxiao Yu; Hua Yuan; Jian Hang (Sustainable Cities and Society, 2026)

Adaptive backstepping sliding mode heading control for wave glider using neural network–based extended state observer - Qi-Jin Feng; Bao-Lin Zhang; Meng Cui; Peiyuan Yu; Qi Zhao; Zidong Ai; Xiujun Sun (Ocean Engineering, 2026)

Efficient Co-hydrothermal conversion of corn straw and pig manure into nitrogen-enriched soluble humic acid fertilizer - Weizhong Huo; Zhaofan Lin; Feng Gao; Jing Yu; Xutong Pang; Rong Ye; Yuchao Shao; Youzhi Miao; Qirong Shen; Ruifu Zhang (Journal of Environmental Management, 2026)

Applying the iRIC Morpho2DH model to determine the effectiveness of check dams against debris flows - Zheng-Yi Feng; Philipp Marr; Tien-Chun Hsu; Ping-Hsuan Kuo; Yu-Po Lin; Ming-Chih Chuang; Ching-Mao Huang; Edoardo Carraro; Su-Chin Chen; Chen-Yu Chen; Thomas Glade (Landslides, 2026)

Preparation of cancer cell membrane-coated Gambogic acid-loaded pH-sensitive liposomes to enhance targeted anti-hepatocellular carcinoma effect - Yi-Feng Zhang; Kun Chen; Yu-Qing Zhu; Lin Liu; Xiang-Tao Kong; Yan Dai; Xiu-Juan Fu; Ya-Ling Li; Ming-Hua Liu; Dan Zhang (Drug Delivery and Translational Research, 2026)

Vegetation in Central Asia is more sensitive to soil moisture stress than to precipitation and vapor pressure deficit stresses - Hongwu Liang; Guli Jiapaer; Cun Chang; Tao Yu; Liancheng Zhang; Pingping Feng; Kaixiong Lin; Tongwei Ju; Xiapeng Jiang; Philippe De Maeyer; Tim Van de Voorde (Agricultural and Forest Meteorology, 2026)

The inflammatory–autophagy–NETs axis in renal fibrosis: mechanistic crosstalk and pathological feed-forward amplification loops - Haixu Chen; Yu Lin; Changying Guo; Feng Li (Molecular and Cellular Biochemistry, 2026)

The emerging role of high-throughput proteomics in advancing precision medicine - Jia You; Yue-Ting Deng; Luo Chen; Lin-Bo Wang; Yu Guo; Ze-Yu Li; Jian-Feng Feng; Jin-Tai Yu; Wei Cheng (Science Bulletin, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Spurious seasonality in satellite turbidity monitoring driven by K1 tidal aliasing - Shiyi Cao; Qian Yu; Shiyu Zhang; Jie Feng; Yidong Guo; Hangjie Lin; Yunwei Wang (Remote Sensing Applications: Society and Environment, 2026)

Metamifop-induced human breast cancer cells proliferation: Revealing a proliferation mechanism distinct from 17β-estradiol - Jingjing Wu; Ya Zhou; Yu Wang; Junqi Zhu; Lu Lin; Huihua Tan; Shiling Liu; Yahui Li; Feng Zhao (Pesticide Biochemistry and Physiology, 2026)

Obstacle avoidance path tracking control for underwater tracked robots with path-dependent constraints - Xiaolong Yao; Kelin Feng; Kewen Li; Yongming Li; Yu Wang; Xuejian Bai; Wenxing Sun; Yazhou Fan; Zheng Wang; Guohai Lin (Ocean Engineering, 2026)

Benefit evaluation of reclaimed water utilization in megacities: Multidimensional evaluation framework and case study - Lin Feng; Yao Ye; Lihua Li; Jing Zhang; Aiqing Chen; Xin Yu; Wenling Chen (Journal of Environmental Management, 2026)

Concurrent removal of salinity and microplastics from wastewater using a stacked microbial desalination cell - Siyu Yi; Lei Yu; Lin Liu; Zhiwei Fan; Yingke Zhou; Huizhen Zhao; Xuanming Feng; Fuping Li; Hao Wang (Journal of Environmental Chemical Engineering, 2026)

Waste lignin-based N/O-rich carbon nanofibers as bifunctional materials for efficient CO2 conversion and energy storage - Wei Hui; Xin Wang; Zao-Lin Hu; Ming-Yu Zhao; Jia-Xin Feng; Wen Chen; Xiao-Yu Xiao; Chuang-Qi Zheng; Lei Pu (Journal of Environmental Chemical Engineering, 2026)

Climate change intensifies carbon emissions from the Earth's Third Pole: Projected trajectories of soil and ecosystem respiration - Tongqing Shen; Zhongbo Yu; Qin Ju; Junliang Jin; Guoqing Wang; Yanli Liu; Chunming Hu; Shixuan Lyu; Hui Lin; Xinrong Si; Feng Yan (Global and Planetary Change, 2026)

Sources, sinks, and isotopic fractionation of antimony in a karst catchment: constraints on multi-media migration and biogeochemical cycling - Yu Lin; Guangyi Sun; Xinyu Li; Yunjie Wu; Yu Cheng; Heng Yao; Xinbin Feng (Geochimica et Cosmochimica Acta, 2026)

Safety and toxicity assessment of Lactobacillus salivarius AP-32 with Probiotic potential in vivo and in vitro - Yu-Hsuan Chin; Yi-Wen Chen; Yen-Yu Huang; Ching-Min Li; Jia-Hung Lin; Yi-Wei Kuo; Chen-Yu Chen; Yen-Feng Lee; Cian-Dai Ciou; Ko-Chiang Hsia; Shin-Yu Tsai; Hsieh-Hsun Ho (Food and Chemical Toxicology, 2026)

Cation-anion synergistic interactions in ion-regulated cholesteric liquid crystal Hydroxypropyl methylcellulose coatings for lithium metal batteries - Zhanpeng Du; Yun Huang; Fengliang Wang; Lei Zhang; Jing Tao; Jin Bao; Heguo Zeng; Jiajun He; Huihui Li; Chao Zou; Chunmei Feng; Bingshu Guo; et al. (Chemical Engineering Journal, 2026)

Diurnal differences in children’s outdoor thermal comfort and adaptive behaviors during physical activity in a subtropical region - Tongye Guo; Yini Fan; Xiang Zhang; Jiahao Yang; Yu Liu; Xiwen Feng; Zhaosong Fang; Zhang Lin (Building and Environment, 2026)

Spatiotemporal relationships between mammal habitat suitability and recreational hiking intensity in Xiaowutaishan National Nature Reserve, China - Ming Yam Chan; Yue Cao; Zhicong Zhao; Pei Wang; Yunshuang Feng; Le Yu; Steve Carver; Xuehua Liu; Ruijia Zhu; Fengze Lin; Xialin Li; Yiqing Wang; et al. (Biological Conservation, 2026)

Unraveling iron and zinc efficiency in pepper: integration of root architecture, uptake kinetics, and transcriptional regulation - Cheng-Xiang Zhou; Wei Zhang; Bao-Gang Yu; Hao-Feng Yang; Yuan Wang; Kai Sun; Fu-Lin Zhao; Huai-Yu Yang; Prakash Lakshmanan; Xin-Ping Chen; Chun-Qin Zou (Plant and Soil, 2026)

REAL208, a Liposome-based Formulation of Phosphodiesterase Inhibitor, Protects Acute Kidney Deficiency in Mice - Jui-Chi Tsai; Yi-Wen Lin; Chun-Yao Huang; Chun-Ming Shih; Yu-Tse Wu; Toshio Kurosaki; Yuki Inoue; Ying-Chi Du; Feng-Yen Lin (Pharmaceutical Research, 2026)

Agroforestry balances plant–soil–microbe–enzyme interactions and improves its connectivity and homeostasis: Evidence from C:N:P stoichiometric networks - Qi-Wen Xu; Meng-Die Feng; Tian-Yang Li; Lin Xiong; Bo-Yu Ren; Yan-Zheng He; Bing-Hui He (Agriculture, Ecosystems & Environment, 2026)

Anoikis-Related Genes Can Accurately Predict the Occurrence of Endometriosis: A Retrospective Cohort Study via Machine Learning Analysis - Lin Hong; Lan Zheng; Yu-Feng He; Ya-Xing Fang; Hui Chen; Kang-Jia Chen; Shu-Guang Zhou (Biochemical Genetics, 2026)
Endometriosis is one of the most common benign gynecological disorders, characterized by persistent pain and challenges with fertility. Anoikis, a specific form of apoptosis, occurs when cells detach from the extracellular matrix. Recent researches have revealed that anoikis resistance is the most important prerequisite for endometriosis development, but it's still not entirely apparent, yet, what part anoikis plays in endometriosis pathogenesis. We obtained the GSE141549 dataset from the GEO database, which served as our training cohort. Anoikis-related genes (ANRGs), sourced from the GeneCards database, were integrated with differentially expressed genes (DEGs) identified in GSE141549. Consequently, we obtained a collection of differentially expressed anoikis-related genes (DE-ANRGs). Subsequently, we employed machine learning algorithms to screen for key diagnostic DE-ANRGs and developed a nomogram model to predict and diagnose endometriosis. Ultimately, we validated our findings through in vitro experiments and an online endometriosis database. Within the training cohort, a total of 47 DE-ANRGs were identified. Furthermore, three machine learning methods pinpointed four diagnostic genes (CAV1, PDK4, CSPG4, SERPINE1). Based on these genes, we constructed a nomogram to facilitate the prediction and clinical diagnosis of endometriosis. To assess model's predictive accuracy, clinical adaptability, and discriminative ability. We performed calibration curves, Receiver Operating Characteristic curves and decision curve analysis. All assessments demonstrated our model's outstanding performance. Ultimately, consistent expression trends of four genes were observed in GSE7305 test cohort, clinical specimens, and the Turku database when compared to the training cohort. In addition, we also have revealed the immune landscape differences, which may offer new promising immunotherapeutic targets for endometriosis patients in the future. In addition to offering novel perspectives on the role of anoikis in endometriosis pathogenesis, our analysis also identified a panel of distinctive biomarkers with significant diagnostic potential. Graphical abstract

The GATA3-RFPL3-ASK1 axis suppresses breast cancer growth and lung metastasis - Kang Li; Chang Liu; Jun-Hui Yin; Yu-Ting He; Zhi-Zhi Xu; Wen-Jing Zhang; Jian-Qi Wang; Lu-Yao Hou; Jing Feng; Le-Min Lin; Xiu-Qing Duan; Yi Zhou; et al. (Apoptosis, 2026)

Lessons learned from shield machine penetrating beneath the existing diaphragm walls using artificial ground freezing (AGF) - Yu-Yong Jiao; Jian-Feng Qi; Xue-Feng Yan; Lin-Chong Huang; Qian-Bing Zhang (Tunnelling and Underground Space Technology, 2026)

Visco-elastic interface and dynamic response of a lined tunnel in anisotropic rock mass under unloading waves - Xue-Qian Fang; Zhao-Feng Zhong; Bai-Lin Li; Xin-Yu Liu; Ya-Wen Xiong (Soil Dynamics and Earthquake Engineering, 2026)

Posttranslational regulation of TOR kinase activity controls resource allocation between plant growth and immunity in Arabidopsis - Jianwei Li; Ran Wang; Chenying Li; Xijie Guo; Qinghong Li; Zhixuan Wu; Shanshan Zeng; Fan Qi; Yuchen Wang; Zhiyi Jia; Weiwei Yu; Zeming Huang; et al. (Molecular Plant, 2026)

Sex-specific associations between exposure to metal mixtures and mitochondrial DNA copy number: A repeated-measures study - Junxiu He; Xiaoting Ge; Sencai Lin; Yu Bao; Hong Cheng; Sihan Hu; Xiuming Feng; Qinghua Fan; Ying Yang; Xiaobo Yang (Journal of Environmental Sciences, 2026)

Coated ferrous sulfate requirement for alleviating hypoxia-induced hepatopancreatic inflammation in sub-adult grass carp (Ctenopharyngodon idella) - Yu-Juan Yang; Pei Wu; Wei-Dan Jiang; Yao-Bin Ma; Hong-Yun Zhang; Yang Liu; Xiao-Wan Jin; Hong-Mei Ren; Ying-Gu Kuang; Xiao-Qiu Zhou; Lin Feng (Fish & Shellfish Immunology, 2026)

Biaxial stretching of wet-cast polyoxadiazole films for high-thermal-conductivity graphene films toward cost-effective thermal management - Hao Cheng; Weizhi Lin; Shaopeng Chen; Jing Yu; Feng Chen (Chemical Engineering Journal, 2026)

Contrasting size responses of loricate ciliates to long-term warming: agglutinated forms decrease while hyaline forms increase - Yunfan Zhang; Wenhua Bian; Hanyue Chen; Wuchang Zhang; Chaofeng Wang; Jichen Qiu; Xiaoxia Sun; Jun Lin; Ying Yu; Meiping Feng; Bingzhang Chen (Marine Biology, 2026)

Research progress on quorum-quenching strategies for membrane biofouling control - Hongwei Wu; Kuo Yang; Yifan Gao; Rui Xu; Yuzhang Feng; Yinning Wang; Huimin Lin; Siqi Hu; Gege Tian; Jiaying Li; Pingfeng Yu; Bing Zhang (ENGINEERING Environment, 2026)

On-exosome-membrane DNA polymerization-powered magneto-electrochemical aptasensing for osteosarcoma - Guang-Xian Zhong; Huang-Feng Lin; Fei-Huan Fu; Jing-Wei Zhou; Chong-Yu Chen; Chao-Yang Wu; Jian-Ping Lin; Xiong-Wei Xu; Jian-Hua Lin; Jin-Yuan Chen (Analytica Chimica Acta, 2026)

Investigation on the Fracture Characteristics and Mechanism of Hard Rock by Microwave Irradiation in Underwater Environment - Feng Lin; Xia-Ting Feng; Tian-Yang Tong; Zhen-Yu Yang; Zi-Yang Wang; Yu-Xi Liu (Rock Mechanics and Rock Engineering, 2026)

Enhancing coastal resilience with nature-based solutions: Policy-driven restoration of a high-energy beach (Changle Airport Beach, China) - Shasha Liu; Fan Yu; Feng Cai; Heshan Lin; Degang Jiang; Patryk Sitkiewicz; Yanyu He; Hang Yin; Michael Wagreich; Ivica Vilibić (Ocean & Coastal Management, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Analysis of cadmium sources in surface soil in typical karst regions: Anthropogenic input contribution and atmospheric transport impact - Zhe Liu; Guangyi Sun; Xian Wu; Weihai Yu; Heng Yao; Yu Lin; Chunlin Fu; Jinling Liu; Xinbin Feng (Journal of Hazardous Materials, 2026)

Constructing Ce–O–C covalent-bridged S-scheme heterojunction via molten-salt transformation of Ce-MOF for photocatalytic overall H2O2 synthesis - Ziying Feng; Pengjia Li; Dou Yang; Jingyi Yu; Yunyun Gui; Shao-Chuan Li; Yuan Lin; Junhua Zou; Lijun Liu (Journal of Environmental Chemical Engineering, 2026)

A liquid reactive flame retardant strategy for CF/EP composites fabricated by vacuum infusion process - Mingming Yu; Jiaying Yao; Jiaxin Ma; Zhimin Gao; Dong Feng; Hao Huang; Ousheng Zhang; Wen Ye; Wang Xie; Lin Fang; Musu Ren; Jinliang Sun (Chemical Engineering Journal, 2026)

Microbial mechanisms of arbuscular mycorrhizal fungi in mitigating nitrous oxide emissions via regulating nitrogen metabolism in constructed wetlands - Xiang-Long He; Liang-Cheng Lin; Yi-Hao Li; Yu-Quan Zhong; Hao Xu; Jing-Wen Li; Can Liu; Jun-Feng Wang (Chemical Engineering Journal, 2026)

Engineering phototrophic cyanobacteria as a robust platform for production of plant-derived bioactive terpenoids - Hui-Cheng Feng; Chun-Lin Tan; Xiang-Mei Zheng; Xin Yu; Jonathan Gershenzon; Sheng-Hong Li; Yan Liu (Chemical Engineering Journal, 2026)

Icariside II sensitizes osteosarcoma to doxorubicin through the lincROR/Wnt/β-catenin signaling regulatory axis - Shu-ting Zhou; Zhi-peng Li; Yong-xin Mai; Yu-Yan Wang; Feng-xiang Pang; Jin-fang Zhang; Xian-lin Wu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Ocean Heat Content Sets Another Record in 2025 - Yuying Pan; Lijing Cheng; John Abraham; Kevin E. Trenberth; James Reagan; Juan Du; Zhankun Wang; Andrea Storto; Karina Von Schuckmann; Yujing Zhu; Michael E. Mann; Jiang Zhu; et al. (Advances in Atmospheric Sciences, 2026)
Global ocean warming continued unabated in 2025 in response to increased greenhouse gas concentrations and recent reductions in sulfate aerosols, reflecting the long-term accumulation of heat within the climate system, with conditions evolving toward La Niña during the year. In 2025, global upper 2000 m ocean heat content (OHC) increased by ∼23 ± 8 ZJ relative to 2024 according to IAP/CAS estimates. CIGAR-RT, and Copernicus Marine data confirm the continued ocean heat gain. Regionally, about 33% of the global ocean area ranked among its historical (1958–2025) top three warmest conditions, while about 57% fell within the top five, including the tropical and South Atlantic Ocean, Mediterranean Sea, North Indian Ocean, and Southern Oceans, underscoring the broad ocean warming across basins. Multiple datasets consistently indicate ocean warming, as measured by 0–2000 m OHC, increased from 0.14 ± 0.03 W m −2 (10 yr) −1 during 1960–2025 to 0.32 ± 0.14 W m −2 (10 yr) −1 during 2005–2025 (IAP/CAS), the latter being consistent with EEI (Earth’s Energy Imbalance) estimates within uncertainties. In contrast, the global annual mean sea surface temperature (SST) in 2025 was 0.49°C above the 1981–2010 baseline and 0.12 ± 0.03°C lower than in 2024 (IAP/CAS; similar in CMA-SST, FY3 MWRI SST, ERSSTv5 and Copernicus Marine data), consistent with the development of La Niña conditions, but still ranking as the third-warmest year on record.

Disease outbreaks substantially enhance greenhouse gas emissions from Asian seabass (Lates calcarifer) aquaculture pond - Han-Yang Yeh; Chien-Wei Tu; Yi-Jung Chen; Wen-Ping Cheng; Pei-Yu Shih; Chia-Chia Yu; Wei-Sheng Zhang; Wei-En Hung; Yu-Ru Lin; Zhen Hao Liao; Wen-Chen Chou; Hsiao-Chun Tseng; et al. (Marine Pollution Bulletin, 2026)

Evaluation of MarR-deleted Streptococcus agalactiae as a live-attenuated vaccine candidate for Nile Tilapia (Oreochromis niloticus) - Tian-Yu Ma; Feng-yang Li; Chang-Song Wu; Jian-Hao Lin; Ming Chen; Yong-An Zhang; Hui Zeng (Aquaculture, 2026)

Single-cell RNA sequencing reveals the immune cell landscape of head kidney in the Perciform fish (Micropterus salmoides) - Zheng-Yang Zhou; Chen-Wang Lu; Zheng-Ran Jian; Shang-Jie Bai; Lin-Feng Kuang; Jin-Lai Gu; Ming-Zhu Liu; Peng-Fei Li; Gao-Xue Wang; Qing Yu; Fei Ling; Jorge Galindo-Villegas; et al. (Aquaculture, 2026)

ER stress disrupts MFN2-related mitophagy via HRD1-PINK1/ parkin axis in bovine embryos - Shu-Ming Shi; Li-Ying Liu; Zhi-Chao Chi; Lin-Yi Qu; Jing-Hang Li; Guan-Lin Jia; Yu-Yan He; Yong-Xun Jin; Ming-Jun Zhang; Xian-Feng Yu (Theriogenology, 2026)

Mechanisms of organic matter accumulation during Early Silurian carbon-cycle perturbations: Geochemical constraints from the inner shelf, Upper Yangtze, South China - Weizhen Chen; Jingchun Tian; Xiaobing Lin; Kailong Feng; Qingshao Liang; Wei Yu; Xing Wang; Shi Sun (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Growth phase-linked Sargassum-associated DOM structures microbial succession and carbon-nutrient coupling in a benthic Sargassum bed - Xiao-Li Ou; Long-Long Huang; Qiu-Jie Wang; Li-Li Xu; Lin-Jian Ou; Yu-Feng Yang (Marine Environmental Research, 2026)

Cadmium accumulation and isotope fractionation in soil–oilseed rape (Brassica napus L.) system in a typical Karst region - Weihai Yu; Guangyi Sun; Heng Yao; Xian Wu; Zhe Liu; Yu Lin; Yu Cheng; Jiang Li; Hua Zhang; Xinbin Feng (Journal of Hazardous Materials, 2026)

Radioactivity of 14C, OBT, and TFWT in seafood from coastal areas of Zhejiang Province: Assessment of internal exposure to the public - Hong Ren; Kaiwen Tan; Feng Lin; Taotao Zheng; Xiaoxiang Ma; Peng Wang; Shunfei Yu; Hua Zou; Xinyu Gong; Yiyao Cao (Food Control, 2026)

Seasonal modulation of the spring-neap response of Yangtze Estuary turbidity maximum: Movement, amplitude, and phase lag via remote sensing - Jie Feng; Qian Yu; Shiyi Cao; Zhiyun Du; Hangjie Lin; Ya Ping Wang; Yunwei Wang (Estuarine, Coastal and Shelf Science, 2026)

Pulsed electric fields as a green alternative to chemical treatment: Toward enhanced molecular interactions and performance in biodegradable preservation films - Rui Wang; Pei-Feng Guo; Ying Xu; Xing-Chan Xie; Dan-Dan Lin; Yu-Wei Wu; Dong-Yang Xu; Lang-Hong Wang; Xin-An Zeng (Chemical Engineering Journal, 2026)

Alternating current or direct current: Which is better for electrochemical membrane separation water purification system? - Zhen Qiu; Jiujing Xu; Cheng Chen; Wei Yu; Bisheng Li; Liguo Shen; Bing Yu; Huajun Feng; Hongjun Lin (Chemical Engineering Journal, 2026)

Genome-wide analysis of the sugarcane SUT gene family reveals ShSUT4 as a key regulator of abiotic stress responses - Xue-Ting Zhao; Ahmad Ali; Cui-Lian Feng; Ji-Shan Lin; Rui-Jie Wu; Shu-Zhen Zhang; Guang-Run Yu; Hai-Feng Jia; Yu-Qing Gong; Ting-Ting Zhao; Jun-Gang Wang (Theoretical and Applied Genetics, 2026)

A1-Reactive Astrocytes in the Posterior Part of Paraventricular Thalamic Nucleus Are Involved in Pain Modulation in Mice - Han-Xue Sun; Zhong-Yi Liu; Jia-Ni Li; Liu-Jie Zhao; Xue-Mei Wu; Chu-Han Liu; Jie Hong; Ke-Hua Zhu; Feng-Ling Wu; Si-Hai Chen; Yu-Lin Dong; Yun-Qing Li (Molecular Neurobiology, 2026)

Emerging trends and clinical challenges in AI-enhanced emotion diagnosis using physiological data - Ying-Ying Tsai; Guan-Lin Wu; Yu-Jie Chen; Yen-Feng Lin; Ju-Yu Wu; Ching-Han Hsu; Lun-De Liao (Medical & Biological Engineering & Computing, 2026)

Machine Learning Models To Characterize the Association of the Gut Microbiota with Osteopenia and Osteoporosis: A Multi-Cohort Study - Yaqi Guo; Hang Feng; Lin Du; Yanzheng Gao; Zhenghong Yu (Current Microbiology, 2026)

Strategies for Promoting Sustainable Development of Land and Water Resources in a Land Subsidence Affected Area of Taiwan - Chung‐Feng Ding; Yu‐Ching Lin; Reuy‐Chi Kao (Irrigation and Drainage, 2025)
Land subsidence has been observed in many parts of the world. In Taiwan, the main cause is the excessive extraction of groundwater in alluvial plains. For limited land and water resources, it is essential to balance the development among economics, society and conservation issues in land subsidence‐affected areas. The Taiwan government promotes ‘prevention (non‐engineering)’ and ‘reclamation (engineering)’ strategies since the 1980s, which are to increase surface and alternative water supply, decrease groundwater abstraction, strengthen groundwater recharge, enhance enforcement related to water resources utilization and management, reduce induced disasters and encourage public participation. This paper reports the framework of prevention and reclamation strategies and their relative achievements; furthermore, it recently integrated ICT technology with low‐cost devices to monitor the regional pumping behaviour related to land subsidence for groundwater management. The real‐time monitoring system enables the utilization of groundwater more effectively and sustainably in reducing land subsidence. In 2022, according to the delimited goals of each strategy in every phase, all achievements were effective in mitigating the annual subsiding rate and affected area, the former from over 20 cm/year down to 8 cm/year, the latter from 1616 to 310 km 2 .

Analytical prediction of liquefaction-induced pipeline uplift coupled with the thixotropic fluid model - Chih-Wei Lu; Yu-Feng Lin; Yohsuke Kawamata; Tetsuo Tobita; Minh-Tam Doan; Hsiu-Chen Wen (Soil Dynamics and Earthquake Engineering, 2025)

Health risk and benefit assessment methods for antibiotic resistance bacteria/genes in the environment: A critical review - Wenling Chen; Lihua Li; Xi Dai; Lin Feng; Xin Yu (Journal of Environmental Management, 2025)

A systematic review of concrete self-healing mechanism and analysis of new research directions - Quan Xue; Xianlei Feng; Yumeng Sun; Zheng Si; Liwei Zhang; Zhenhua Zhou; Yu Zhong; Kaiyuan Mei; Guanghua Lin; Huiyizhe Zhao (Journal of Environmental Chemical Engineering, 2025)

Hydrogeochemical characteristics and the monitoring from 2020 to 2023 of hot spring waters in Tatun Volcanic Group, Taiwan - Ju-lien Pi; Hsueh-Yu Lu; Hsiao-Fen Lee; Hung-Chun Chao; Chen-Feng You; Tsung-Ren Peng; Raymond Patrick R. Maximo; Chia-Tai Wu; Ya-Wen Wu; Chung Fang; Cheng-Horng Lin (Journal of Asian Earth Sciences, 2025)

A refined calibration of the Na-Li geothermometer for pelitic lithologies before and after orogenic metamorphism - Hou-Chun Liu; Chao-Chang Chen; Yi-Chia Lu; Huai-Jen Yang; Yan-Hong Chen; Yu-Feng Lu; In-Tian Lin; Sung-Ping Chang (Geothermics, 2025)

Advances in the research on phenolic acids and flavonoids in vinegar: Sources, formation and degradation mechanisms, and functional properties - Cheng-Hao Jin; Yong-Zhu Zhang; Feng-Hua Wu; Chang-Ling Wu; Peng Wang; Wei Feng; Lin-Mei Liang; Wei-Jiang Xu; Xiao-Tao Sun; Xing-Quan Liu; Guan-Yu Fang (Food Research International, 2025)

Differential modulation of aroma profiles in instant Oolong tea powder by two Aspergillus niger β-glucosidases - Ziyue Chen; Qi Lin; Cheng Peng; Kunpeng Yu; Yanling Lin; Shuyi Weng; Lijun Li; Hui Ni; Feng Chen (Food Chemistry, 2025)

Dietary prebiotics combined with iron supplementation: A two-pronged approach to reduce rice cadmium bioavailability - Rong-Yue Xue; Yao-Sheng Zhang; Jin-Feng Xi; Lei Zhou; Xin-Ying Lin; Tian-Wen Ye; Yu-Hang Bao; Dongmei Zhou; Hong-Bo Li (Food and Chemical Toxicology, 2025)

Seismic performance of precast concrete shear wall with disc spring-bolt subassembly connections - Hua-long LIU; Xun CHONG; Lin-lin XIE; Qing JIANG; Yu-long FENG; Jun-Qi HUANG (Engineering Structures, 2025)

In situ deformation of antigorite-olivine two-phase mixtures: Implications for dynamics and seismic anisotropy in the mantle wedge - Rose Hurlow; Wenhao Su; Wen-Yi Zhou; Feng Lin; Lowell Miyagi; Timothy Officer; Tony Yu; Yanbin Wang; Meiqian Wu; Qin Wang; Jin S. Zhang (Earth and Planetary Science Letters, 2025)

Engineering NK cell membrane-camouflaged copper-BODIPY nanoassembly to synergize dual-phototherapy and cuproptosis for enhanced antitumor immunity - Xuya Yu; Yushi Zhang; Zhuona Rong; Xueping Li; Lingpeng Luo; Lu Zhang; Liyu Sun; Yayue Liu; Wen Li; Lin Mei; Feng Lv; Xiaocong Pang; et al. (Chemical Engineering Journal, 2025)

Unveiling the role of Zn−N1S3 sites in atomic-precision ZnIn2S4/g-C3N4 heterostructure for highly efficient CO2-to-CO conversion - Hossam A.E. Omr; Raghunath Putikam; Mahmoud Kamal Hussien; Amr Sabbah; Tsai-Yu Lin; Kuei-Hsien Chen; Li-Chyong Chen; Heng-Liang Wu; Shien-Ping Feng; Ming-Chang Lin; Hyeonseok Lee (Chemical Engineering Journal, 2025)

A carboxymethyl chitosan/oxidized alginate hydrogel with controlled fullerenol release accelerates diabetic wound healing through cellular senescence reprogramming - Ze-Bang Du; Qi Yuan; Ke-Jian Ni; Jie He; Jia-Shen Wu; Hai-Yan Huang; Yan-Yan Zhou; Xiao-Qing Li; Chang-Feng Zhu; Xiao-Xuan Chen; Li-Li Pan; Ran An; et al. (Chemical Engineering Journal, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

Correction: Fbxw8 is involved in the proliferation of human choriocarcinoma JEG-3 cells - Ping Lin; Jiejun Fu; Binjiahui Zhao; Feng Lin; Haifeng Zou; Leiyu Liu; Cheng Zhu; Hongmei Wang; Xiaoguang Yu (Molecular Biology Reports, 2025)

Melatonin Attenuates Spinal Cord Injury by Regulating Ferroptosis Through the Nrf2/HO-1/GPX4 Pathway - Zhengxi Yu; Dingwei Wu; Tengbin Shi; Dehui Chen; Hao Feng; Huina Chen; Hailin Lin; Lei Sun; Wenge Liu (Molecular Neurobiology, 2025)

Multiple Mechanisms and Therapeutic Strategies for the Involvement of AMPK in the Development of Alzheimer’s Disease - Lin Yu; Xue Yang; Hui-Ping Lei; Yue-Ting Hu; Ling-Nan Wu; Shao-Yu Zhou; Feng Jin (Molecular Neurobiology, 2025)

Histone H3K18 lactylation-dependent epigenetic activation of RUNX2 orchestrates PI3K/AKT oncogenic signaling in laryngeal squamous cell carcinoma - Daidi Fu; Xin Huang; Ying Lin; Feng Yu; Haiwei Wu (Journal of Molecular Histology, 2025)

Distinctive mechanisms of soil priming in different stages and its response to nitrogen addition along a temperate forest elevation gradient - Qiuxiang Tian; Rudong Zhao; Qiaoling Lin; Xiaoxiang Zhao; Yu Wu; Feng Liu (Soil Ecology Letters, 2025)

Spatio-temporal heterogeneity of the estuarine turbidity maximum retreat in the Changjiang river estuary under reduced sediment supply - Jie Feng; Qian Yu; Shiyi Cao; Shiyu Zhang; Tianxu Ni; Zhiyun Du; Hangjie Lin; Yunwei Wang; Ya Ping Wang (Geo-Marine Letters, 2025)

On-off-on electrochemiluminescence biosensor with dual-cycle amplification for ultrasensitive prenatal detection of thalassemia mutations using lanthanide europium nanorods - Ya-Qian Xie; Ya-Shu Wei; Hang Du; Yu-Yi Zhou; Lin-Yi Liu; Fu-Cun Wei; Yan-Ni Luo; Xue-Cai Tan; Ke-Jing Huang; De-Fen Feng (Analytica Chimica Acta, 2025)

Comprehensive overview: QuEChERS methods for mycotoxin determination in different matrices - Ruifeng Lin; Jiandan Yuan; Huiqiang Feng; Yanling Liu; Yu Fan; Yuzhu Tan; Zhentao Tang (Food Additives & Contaminants: Part A, 2025)

Salidroside improves bovine embryo quality by mitigating oxidative stress and regulating mitochondrial lipid metabolism - Li-Ying Liu; Xian-Feng Yu; Zhi-Chao Chi; Shu-Ming Shi; Tian Lan; Jia-Hui Leng; Jing-hang Li; Yu-Yan He; Lin-Yi Qu; Guan-Lin Jia; Ilkeun Kong; Ming-Jun Zhang; et al. (Theriogenology, 2025)

Biocontrol potential and antifungal mechanism of a novel Bacillus velezensis NH-13–5 against Botrytis cinerea causing postharvest gray mold in table grapes - Lin Xiao; Jin-Tian Wang; Dong-Fang Cao; Hong Li; Hong-Yu Fang; Tian-Li Qu; Bao-Hua Zhang; Shuai-Shuai Li; Feng-Yu Du (Postharvest Biology and Technology, 2025)

Effective peroxymonosulfate activation over cobalt oxide (CoO)/nitrogen-doped graphene aerogel for rhodamine b degradation - Xian-Lun Liao; Dhayanantha Prabu Jaihindh; Tzu-Ting Chang; Yi-Feng Lin; Wei-Hung Chiang; Yu-Chun Wang (Journal of Water Process Engineering, 2025)

Using HRMS fingerprinting to elaborate the effects of reclaimed water irrigation on small-molecule distribution in rice - Keng-Jui Lin; Wen-Ling Chen; Feng-Wen Chen; Yu-Chien Cho; Jin-Jing Lee; Shan-Li Wang (Journal of Environmental Management, 2025)

Collagen peptides from Skipjack tuna (Katsuwonus pelamis) bones: Composition, characterization, and mechanism of high-fat diet-induced NAFLD amelioration - Yu-Lin Jiang; Shuang-Yi Zhang; Bin Wang; Yu-Hui Zeng; Li Xu; Chang-Feng Chi (Food Research International, 2025)

Naringenin-loaded Flammulina velutipes chitin-glucan complexes gel system: structural modulation and dual lipid-lowering mechanisms - Simin Feng; Shuqi Liang; Jianyu Yang; Jiahao Yu; Yang Lin; Yizhen Xie; Peilong Sun; Ping Shao (Food Chemistry, 2025)

A dynamic prediction model for maximum lateral displacement of foundation pit enclosure structure using multi-source fusion method - He Wei Kuang; Zhi Yong Ai; Gan Lin Gu; Hong Wei Huang; Zeng Zhi Qian; Da Xing Zhou; Yu Xin Zhai; Hai Feng Guo (Computers and Geotechnics, 2025)

Influence of prolonged exposure to acetamiprid on the toxicology of the decapod crustacean Pacific white shrimp Penaeus vannamei - Zhen-Fei Li; Zhi Luo; Zhi-Yu Lin; Zhen-Qiang Fu; Feng-Lu Han; Er-Chao Li (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

A point-of-care testing biosensing platform integrated with physiologically based pharmacokinetic model for on-site therapeutic drug monitoring of methotrexate - Feng-Feng Zhang; Mei-Juan Wu; Zi-Wei Yu; Yi-Lan Lin; Pin-Fang Huang; Meng-Meng Liu (Chemical Engineering Journal, 2025)

Synergistic spin state and geometry engineering by constructing MoFe diatomic sites to catalyze non-radical and sustained oxidation of water pollutants - Chaofa Chen; Minjia Yan; Yu Li; Feng Chen; Zhangrong Lou; Xingshuai Lv; Xi-Lin Wu (Chemical Engineering Journal, 2025)

Contrasting char-EC and soot-EC in sources, atmospheric processing, and light-absorbing capabilities: Insights from high-resolution stable carbon isotope analysis - Mingyuan Yu; Yu-Chi Lin; Feng Xie; Fang Cao; Yan-Lin Zhang (Atmospheric Research, 2025)

Identification and semi-quantification of alkylated polycyclic aromatic hydrocarbons in PM2.5 filter samples using in-injection port thermal desorption coupled with two-dimensional gas chromatography and rapid-scanning quadrupole mass spectrometry (TD-GC×GC-qMS) - Manfei Lin; Yongming Feng; Xiao He; Bin-Yu Kuang; X.H. Hilda Huang; Yongmei Liang; Jian Zhen Yu (Atmospheric Pollution Research, 2025)

Unraveling phylogenetic conflicts and adaptive evolution in Chiroptera using large-scale mitogenomes and nuclear genes - Dengfeng Guan; Xin Huang; Guangping Huang; Jiang Zhou; Lin Yang; Wenhua Yu; Weijian Guo; Jiang Feng; Yi Wu; Yibo Hu; Fuwen Wei (Science China Life Sciences, 2025)

The Double-Edged Effect of Connexins and Pannexins of Glial Cells in Central and Peripheral Nervous System After Nerve Injury - Yue-Yan Cen; Xin-Lin Gao; Yu-Heng Feng; Cheng Zhou; Chun-Jie Li; Fei Liu; Jie-Fei Shen; Yan-Yan Zhang (Molecular Neurobiology, 2025)

Predictors of mortality and progression from colonization to Stenotrophomonas maltophilia bloodstream infection in hematologic disorders: a single-center retrospective study - Hongchen Bi; Qingsong Lin; Qi Sun; Yanxia Lv; Zhiying Tian; Xue Fu; Qiushuang Yan; Yaqing Yu; Hongjing Yao; Fujun Sun; Yonghui Xia; Aiming Pang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Temporal variability of greenhouse gas fluxes in monoculture of tilapia in ponds - Yi–Jung Chen; Han–Yang Yeh; Chien-Wei Tu; Yu-Ru Lin; Zhen Hao Liao; Wen-Chen Chou; Hsiao-Chun Tseng; Ruei-Feng Shiu; Tzu-Ning Teng; Meng–Chou Lee; Fan–Hua Nan (Aquaculture International, 2025)

Two new withanolides from Physalis minima L - Li-Jie Zhang; Mei-Lin Peng; Shi-Ying Xu; Fu-Rui Wang; Lin-Lin Yu; Qin-Feng Zhu; Shang-Gao Liao; Guo-Bo Xu (Natural Product Research, 2025)

Deep learning-based species identification of gymnosperm xylem: The practice in digital forestry - Chang Zheng; Tuo He; Lichao Jiao; Yang Lu; Shoujia Liu; Tianxiao Li; Yuanyuan Miao; Dejun Feng; Jian Lin; Xian Feng; Zhonghua Huang; Min Yu; et al. (Computers and Electronics in Agriculture, 2025)

Derivation of interim guideline values for pharmaceuticals and personal care products in marine environment - Xingying Guo; Jinhui Wang; Yolina Yu Lin Wang; Tan-Duc Nguyen; Feng Hua; Wenhua Liu; Zhen Wang (Marine Pollution Bulletin, 2025)

Effects of compound probiotics on intestinal and liver transcriptome, immunity and disease resistance of zig-zag eel (Mastacembelus armatus) - Yuwei Feng; Yiman Chen; Zhiting Zuo; Xianshan Lin; Qiaoyi Chen; Along Gao; Zhide Yu; Chong Han; Hu Shu (Aquaculture, 2025)

A copper-based single-atom material effectively controls plant diseases with nearly zero soil residue and low phytotoxicity - Rui Huang; Yong Yan; Yafei Jiang; Chunyan Gu; Zhentao Ma; Lifang Xue; Yao Ma; Xingen Lin; Juan Zhang; Ran Shi; Yiwen Wang; Linjing Liu; et al. (Science Bulletin, 2025)

Leakage of composite cutoff walls through geomembrane joint defects - Lin-Feng Cao; Yu-Chao Li; Bo Huang (Geotextiles and Geomembranes, 2025)

Harnessing basic helix-loop-helix-mediated transcriptional reprogramming in mixotrophic Chlorella for synergistic carbon waste remediation and biofuel production - Yu-Feng Yang; Jin-Hua Mou; Yu-Cheng Yang; Lan-Lan Hu; Wen-Li Huang; Wei-Dong Yang; Hong-Ye Li; Carol Sze Ki Lin; Xiang Wang (Chemical Engineering Journal, 2025)

C2-symmetric chiral Pd(0) complexes bearing C2-symmetric chiral bidentate phosphine ligands with high luminescence dissymmetry factors and strong electroluminescence ability - Zhao Feng; Ruiqin Zhu; Lin Ma; Yue Yu; Daokun Zhong; Ziyi Chen; Tao Shi; Bochao Su; Xiaolong Yang; Yuanhui Sun; Guijiang Zhou (Chemical Engineering Journal, 2025)

Tribopotential mediated ferroelectric polarization for versatile reconfigurable p–n junction - Keteng Zhang; Jinran Yu; Yichen Wei; Liuqi Cheng; Zhenyu Feng; Jie Gong; Zhong Lin Wang; Qijun Sun (Chemical Engineering Journal, 2025)

Flexible chain-engineered conjugated polymers with phosphonic acid anchors for synergistic photocatalysis-adsorption uranium extraction - Yuanping Jiang; Feng Wang; Junshuo An; Xingfang Yu; Menghan Cao; Guohang He; Danning Xu; Jiajian Yang; Kai Zhang; Yunxiu Zhang; Lin Xu; Zuojia Li; et al. (Chemical Engineering Journal, 2025)

The Antimicrobial Peptide Tilapia Piscidin 4 Induced the Apoptosis of Bladder Cancer Through ERK/SIRT1/PGC-1α Signaling Pathway - Chun-Feng Chang; Po-Chih Chang; Yi-Chen Lee; Chieh-Yu Pan; Hui-Min Chang; Wan-Ju Wu; Mei-Ying Lin; Chung-Yi Chen; Zhi-Hong Wen; Chien-Hsing Lee (Probiotics and Antimicrobial Proteins, 2025)

Development and application of InDels and SNPs markers based on whole-genome resequencing in Chinese cabbage - Kai-Wen Liu; Wan-Jie Men; Jin-Xia Feng; Iqbal Hussain; Hui Sheng; Li-Wei Zhang; Zhong-Ren Dai; Hai-Jiang Hu; Jian-Hao Yang; Na Lei; Xiao-Lin Yu (Horticulture, Environment, and Biotechnology, 2025)

A precisely regulated Streptomyces expression system pTZYp facilitated by the strong promoter stnY and cmt operon - Kai Zhang; Ao-yu Wang; Qiang Zhou; Yi-feng Chen; Shuang-jun Lin; Gong-li Tang (Biotechnology Letters, 2025)

Integrin CD11b Alleviates Cerebral Ischemia/Reperfusion Injury via a Mechanism Involving Microglia/Macrophage Polarization - Gui-Nan Jiang; Qiu-Yue Lin; Xiang-Bo An; Wei-Jia Yu; Jie Bai; Xin Yu; Feng Wang; Hui-Hua Li (Journal of Molecular Neuroscience, 2025)

New perspective on mechanism of L-arginine in promoting skeletal muscle growth of grass carp (Ctenopharyngodon Idella): Via enhancing skeletal muscle functions and regulating energy metabolism - Qiu-Yan Chen; Yu-Long Ma; Wei-Dan Jiang; Pei Wu; Yang Liu; Hong-Mei Ren; Xiao-Wan Jin; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Olfactory dysfunction induced by pesticides: Adverse outcomes, emerging mechanisms, and risk for neurodegenerative diseases - Lin Wang; Si-Yang Liu; Han-Yue Zheng; Shou-Min Fang; Li Zhuo; Feng Xu; Quan-You Yu (Pesticide Biochemistry and Physiology, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Singlet oxygen-driven non-radical oxidation of phenylurea herbicides in aqueous environment: Reaction behaviors and degradation mechanisms via unactivated PMS systems - Zi-Han Feng; Lin-Hao Xu; Fu-Xiang Tian; Fan Lai; Jing Ye; Yu-Qiong Gao; Dong-Su Bi; Xiao-Jun Hu (Journal of Water Process Engineering, 2025)

Quantitative prediction and mechanistic insights into Cu(II) transport in kaolinite-coated sand columns affected by ferrihydrite nanoparticles - Lijuan Zeng; Guining Lu; Feng Jiang; Ying-Jie Zhang; Xiaohu Jin; Weilin Huang; Yu-Jung Lin; Jyh-Fu Lee; Xiaoyun Yi; Zhi Dang (Journal of Hazardous Materials, 2025)

The correlation of immunotoxicity with size and chemical properties of particulate matter within macrophages - Hsiang-Yu Kung; Yi-Shiuan Wang; Yung-Jui Chen; Ting-Hsuan Wu; Jai-Yu Chen; Yueh-Feng Wen; Yu-Cheng Chen; Hong-Lin Chan; Hsiu-Chuan Chou (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Synergistic enhancement of wetland purification performance by introducing intermittent aeration and zero-valent iron under chilling stress - Lin-Yuan Wu; Bing-Xu Guo; Ke-Jia Zhang; Jun-Yu Ai; Wei-Yi Shi; Qing-Yuan Tian; Wen-Huai Wang; Jun-Feng Li (Chemical Engineering Journal, 2025)

Enhancing high-temperature phase stability and thermal properties of 5RE(TaxNb1-x)O4 high-entropy ceramics through chemical bonding strength optimization - Mengdi Gan; Liping Lai; Xiaoyu Chong; Qianqian Jin; Wei Yu; Jiankun Wang; Jun Wang; Lin Chen; Jingjin He; Jing Feng (Chemical Engineering Journal, 2025)

Field Tests Using High-Power Microwaves to Crack Iron Ore of Different Grades - Feng Lin; Xia-Ting Feng; Shi-Ping Li; Tian-Yang Tong; Yun-Tan Ao; Yu-Xi Liu (Rock Mechanics and Rock Engineering, 2025)

Feasibility of a hybrid AHA-GPR model for predicting blasting fragmention in surface mines - Zhi Yu; Lin-Feng Du; Jian-Xing Liu; Jian Zhou; Chuan-Qi Li (Earth Science Informatics, 2025)

Develop intelligent waste bin prototype based on fusion feature recognition of sounds and RGB images - Wei-Chun Chen; Chieh-Feng Chiang; Yu-Hao Lin; Hao-Jun Hsieh (Waste Management, 2025)

Host-mediated environmental microbiome recruitment by black soldier fly (Hermetia illucens) enhances waste biotransformation - Zhe Li; Yuchen Zhou; Lin Lv; Yinguang Long; Mengyao Dong; Qi Xiao; Xianyue Jia; Dechen Ju; Xiaowen Sun; Feng Huang; Minmin Cai; Jibin Zhang; et al. (Waste Management, 2025)

A review of umami taste of Tea: Substances, perception mechanism, and physiological measurement prospects - Yashu Yu; Xiaoxiao Feng; Imre Blank; Haoli Wang; Yiwen Zhu; Zhibin Liu; Li Ni; Chih-Cheng Lin; Kequn Wang; Yuan Liu (Trends in Food Science & Technology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Adaptive fuzzy event-triggered and precision trajectory tracking control for underwater tracked robot - Xiaolong Yao; Kelin Feng; Kewen Li; Yongming Li; Yu Wang; Wenxing Sun; Yazhou Fan; Zheng Wang; Guohai Lin (Ocean Engineering, 2025)

Identification of the sources and migration of antimony in karst terraces via Sb stable isotopes - Yunjie Wu; Guangyi Sun; Yu Lin; Xinyu Li; Yu Cheng; Heng Yao; Xinbin Feng (Journal of Hazardous Materials, 2025)

A new strategy for removing insecticide etoxazole from soil using a combination of a novel Paracoccus versutus Y4 and a fungal mycelium carrier - Man Xu; Xue Luo; Xin-Li Yan; Xiao-Yu Cai; Lin-Lin Wang; Feng Ge; Hong-Wei Wang (Journal of Hazardous Materials, 2025)

Geochemistry of sulfides from massive carbonate replacement type tin ore at Gaofeng, Dachang orefield: Insights into precipitation conditions and enrichment of critical metals - Yu-Pei Liu; Pei Ni; Jun-Yi Pan; Wen-Chao Su; Stefano Albanese; Jian-Ming Cui; Yuan-Feng Cai; Ming-Sen Fan; Zhi-Lin Cheng (Journal of Geochemical Exploration, 2025)

Thick polyethylene films lessen pollution footprint while highlighting environmental merit and maize yielding in drylands - Xiao-Bin Xiong; Peng-Yang Wang; Ze-Ying Zhao; Zi-Yu Han; Yuan Song; Ying Zhu; Yi-Bo Wang; Jin-Lin Zhang; Xu-Sheng Guo; Xiao-Feng Zhang; Xiao-Yu Lu; You-Cai Xiong (Journal of Environmental Management, 2025)

Limonene-loaded nanostructured lipid carriers incorporated in hydrogels: Enhanced acid stability and controlled release properties - Simin Feng; Yitong Tian; Jiahao Yu; Yang Lin; Alan Giovanini de Oliveira Sartori; Ping Shao (Food Research International, 2025)

Plasmonic nanoheater for formaldehyde degassing - Gaopan Chen; Peng Yu; Lian Yang; Roberto Caputo; Feng Lin; Liang Pan; Yang Gao; Hongxing Xu; Alexander Govorov; Zhiming Wang (Chemical Engineering Journal, 2025)

Ecological risks under combined pollution: Toxicological effects of clothianidin and microplastics on Penaeus vannamei - Zhi Luo; Zhi-Yu Lin; Zhen-Fei Li; Zhen-Qiang Fu; Feng-Lu Han; Er-Chao Li (Aquatic Toxicology, 2025)

Polymeric immunoglobulin receptor (pIgR) in cancer progression: a critical role and potential therapeutic target - Shaoju Qian; Yeqing He; Ruixue Li; Panpan Sun; Xingyi Zhang; Lin Pan; Zhishan Xu; Zhiwei Feng; Rong Lian; Lili Yu (Apoptosis, 2025)

Air classification efficiency evaluation of landfilled municipal solid waste using experiments and a probabilistic method - Lin Feng Yu; Yu Qi Jin; Miao Xin Yuan; Fei Zhang; Jie Hu; Ji Wu Lan; Yu Fan Wei; Yun Min Chen; Han Ke (Waste Management, 2025)

Analytical estimation of liquefaction-induced building settlement - Chih-Wei Lu; Yu-Feng Lin; Wei-Lin Lee; Minh-Tam Doan (Soil Dynamics and Earthquake Engineering, 2025)

Study on the feasibility of using ZIF-8 as a carbonic anhydrase mimic to enhance CO2 absorption by K2CO3 solution in flue gas and biogas decarbonization - Yuchen Zhou; Donglin Jiang; Feng Lin; Zezhi Chen; Huijuan Gong; Huiqiang Yu; Lu Chen (Fuel, 2025)

Effect of electron beam irradiation on the quality of chicken during post-mortem ageing - Xin Wang; Linya Wang; Jiangtao Yu; Yifeng Teng; Xiaomei Xiang; Dan Zhang; Luyao Kang; Yabin Niu; Xianchao Feng; Lin Chen (Food Chemistry, 2025)

From water migration to aroma development: Revealing the influence of environmental airflow on the aroma of white tea during withering - Jiao Feng; Shuping Ye; Jinyuan Wang; Junyang Wu; Jiake Zhao; Weisu Tian; Guanjun Pan; Bugui Yu; Dongliang Qiu; Hongzheng Lin; Zhilong Hao (Food Chemistry, 2025)

Characteristics of microbial carbon pump in the sediment of kelp aquaculture zone and its contribution to recalcitrant dissolved organic carbon turnover: insights into metabolic patterns and ecological functions - Jun-Yang Ma; Ji-Hua Liu; Cheng-Zhuang Chen; Yi-Ze Zhang; Zhan-Sheng Guo; Min-Peng Song; Feng Jiang; Zi-Tong Chai; Zhu Li; Su-Xian Lv; Yu-Jiao Zhen; Lu Wang; et al. (Environmental Research, 2025)

Fabrication of graphene-PEI composite membrane by supercritical CO2 exfoliation for efficient nanofiltration performance - Lin Li; Kunpeng Yu; Jing Xie; Haixin Sun; Tong Feng; Qinqin Xu; Jianzhong Yin (Chemical Engineering Journal, 2025)

Innovative immunosonogen nanoplatform combining sonodynamic oxygenation and immunomodulation for superior cancer therapy - Jiali Tang; Yanlu Chen; Hao Lai; Qi Zeng; Yu Li; Junqi Feng; Ningjing Lin; Ronghua Jin; Junjie Liu; Tao Luo; Zixuan Liang (Chemical Engineering Journal, 2025)

Corrigendum to “Isopimaric acid, an ion channel regulator, regulates calcium and oxidative phosphorylation pathways to inhibit breast cancer proliferation and metastasis” [Toxicology and applied Pharmacology, 2023, 462:116415] - Jiacheng Li; Xiaozhen Liu; Lin Chen; Xinping Zhu; Zhihong Yu; Liyao Dong; Xinyun Zhao; Hongling Zou; Qin Wei; Yongcai Feng; Yongqiang Zhu; Kequn Chai; et al. (Toxicology and Applied Pharmacology, 2025)

The synthesis of arylmethylene bisindoles catalyzed by nickel perchlorate as potential antifungal agent against Clarireedia homoeocarpa - Ye Zhou; Ruyuan Wang; Rui Feng; Bi Wang; Shu Xu; Mei Tian; Wenhao Liang; Jin Chen; Yu Chen; Xu Feng; Li Lin; Jinyue Luo; et al. (Phytochemistry Letters, 2025)

Hetero-atom-doped biochar as a sustainable catalyst for value-added upgrading of lignin derivatives: Optimizing dopant for enhancing conversion - Vo Thi Thanh Thuy; Hua-Chen Wu; Yu-chih Tsai; Ta Cong Khiem; Yi-Feng Lin; Ha Manh Bui; Yiu Fai Tsang; Kun-Yi Andrew Lin (Journal of Environmental Chemical Engineering, 2025)

Application of gravity gradient measurement in the detection of urban underground space - Zhong-kun Qiao; Jia-jun Zhang; Peng Yuan; Lin-ling Li; Ruo Hu; Hai-xiang Yang; Kan-xing Weng; Zong-yu Zhang; Lin-fei Wang; Pei Qin; Liang-liang Hao; Chuan Yang; et al. (Journal of Applied Geophysics, 2025)

Milk peptides alleviate irritable bowel syndrome by suppressing colonic mast cell activation and prostaglandin E2 production in mice - Yu Zhang; Zhiqing Lin; Qi Yao; Jian He; Haotian Feng; Wenyi Zhang; Zhigang Liu; Tian Yuan; Xuebo Liu; Long Ding (Food Research International, 2025)

Muti-network active aerogel based on PVA, bacterial cellulose, and sodium alginate: Characterization, kinetics studies, and application for mutton preservation - Xi Zhou; Fangqu Wang; Yang Yu; Ruirui Guo; Xinran You; Xiaomei Xiang; Xiaojing Fan; Yabin Niu; Xuejiao Wang; Xianchao Feng; Lin Chen (Food Hydrocolloids, 2025)

Field tests and structural performance evaluation of existing reinforced concrete hollow slab beam bridges - Jing-Lin Xiao; Yu-Fei Liu; Hao-Long Feng; Jian-Guo Nie (Engineering Structures, 2025)

Development and full-scale cycling test of a novel rotational friction damper with response-amplification mechanism - Zhenqin Huang; Chao Zhang; Tianhao Yu; Zijian Lin; Feng Zhao (Engineering Structures, 2025)

A catalytic hairpin assembly-assisted magnetic SERS platform with core-satellite structure for ultra-sensitive circRNA detection in early lung cancer screening - Luyun Xu; Yongshi Shen; Zhizhong Lin; Jianqing Ye; Lingna Wang; Xueliang Lin; Shuhang Liu; Duo Lin; Yuanji Xu; Zongyang Yu; Rongcai Zhang; Shangyuan Feng (Chemical Engineering Journal, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

A novel deacetylase inhibitor KLX suppresses liver fibrosis by deacetylating PPARγ through promoting ubiquitination-mediated HDAC1 degradation - Feng Zhang; Jinglun Song; Han Wu; Keying Lin; Chunlei Wang; Linghua Zeng; Xue Kong; Kunkun Zou; Hongtao Diao; Zhuo Wang; Wei Si; Weitao Jiang; et al. (Science China Life Sciences, 2025)

Mitigating low-temperature frost damage in Taiwan high-altitude tea cultivation: physiological insight and protective strategies - Po-Heng Chen; Ru-Hong Lin; Chui-Feng Chiu; Yu-Sheng Lin (Planta, 2025)

Interspecific differences in nitrogen form acquisition strategies contribute to species dominance - Ming Guan; Xiao‐Cui Pan; Jian‐Kun Sun; Ji‐Xin Chen; Xiao‐Lin Wei; Bernhard Schmid; Michel Loreau; Yu‐Long Feng (Ecology, 2025)
Plant's ability to use prevalent or less prevalent soil nitrogen (N) forms may affect their dominance within vegetation types, and these partitioning‐driven changes in dominance may facilitate species co‐existence. However, the mechanisms underlying these processes remain unclear, particularly given the strong influence of altitude on soil N forms, which in turn affect plant N acquisition strategy. In this study, we first determined the effects of preference and plasticity in N form uptake on partitioning of soil N forms and species dominance, and then assessed the relative importance of these two N form use strategies for 19 dominant and non‐dominant species in three vegetation types along an altitudinal gradient on Changbai Mountain, northeast China. To achieve this, we measured dominance, the contents of different N forms in rhizosphere soils, their proportional contributions to leaf N, and N form uptake preference and plasticity for these 19 species. Our results show significant interspecific differences in the proportional contributions of different soil N forms to leaf N within all three vegetation types, providing a novel mechanism underlying niche differentiation among plants. Species dominance was positively associated with the proportional contributions of soil dissolved organic N (the most prevalent N form) and the main inorganic N form to leaf N, while negatively with that of the subordinate inorganic N. These associations were not altered by the altitude‐driven changes in the absolute and proportional contents of different soil N forms, suggesting a potentially widespread phenomenon. Both preference and plasticity in N form uptake contributed to the proportional contributions of different N forms to leaf N, and therefore to species dominance and co‐existence within vegetation types. Furthermore, N form preference was more critical for non‐dominant relative to dominant species and at high relative to low altitude, while N form uptake plasticity was more important for dominant species and at low altitude. Our study provides robust evidence for the interspecific niche differentiation in N form uptake, contributing to species dominance and co‐existence within vegetation types, and reveals the mechanisms (plasticity and preference) underlying the association between species dominance and the uptakes of different N forms.

A comparative metabolomics study of Panax ginseng infected by Fusarium oxysporum - Wenhui Lian; Chunhui Yu; Guijia Zhao; Xu Yang; Lin Feng; Jifeng Wang; Wei Liu; Yu Zhao (Journal of Plant Pathology, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Enhancing antibiotic removal in constructed wetlands: A MgFe-LDHs-based strategy for optimizing microbial communities and metabolic functions - Yu-Quan Zhong; Xiang-Long He; Yi-Hao Li; Hui Zhu; Jing-Wen Li; Hao Xu; Can Liu; Liang-Cheng Lin; Jun-Feng Wang (Journal of Hazardous Materials, 2025)

Seismic performance of grouted CFDST column base: Investigation and design method - Zhi-Cheng Yang; Wei Li; Yu-Feng Cheng; Lin-Hai Han (Engineering Structures, 2025)

Uncertainty analysis of 3D post-failure behavior in landslide and reinforced slope based on the SPH method and the random field theory - Dianlei Feng; Lin Gan; Min Xiong; Weile Li; Yu Huang (Engineering Geology, 2025)

Interfacial clustering-derived fluorescent, mechanically strong and fire-safe epoxy composites - Dong-Qing Zeng; Xin-Miao Li; Feng Chen; Wei-Bin Bai; Yu-Cai Lin; Rong-Kun Jian (Chemical Engineering Journal, 2025)

“Three-birds, one-stone” biomimetic nanozyme system based on oxygen vacancy structure-regulated cascade reaction for inflammatory bowel disease - Tianliang Li; Zhaoming Wang; Zhijie Wang; Yihuan Pu; Lixing Lin; Zeyu Li; Lifei Chen; Xinting Liu; Bin Cao; Yingying Chen; Zhenzhen Li; Zixuan He; et al. (Chemical Engineering Journal, 2025)

Enhancing ZnTPP performance as a carbonic anhydrase mimic for promoting CO2 absorption via circumferential and axial functionalization - Yuchen Zhou; Feng Lin; Zezhi Chen; Huijuan Gong; Donglin Jiang; Huiqiang Yu; Lu Chen (Chemical Engineering Journal, 2025)

Electrostatic-Induced Crystal-Rearrangement of Benzoquinones Cathode for Large-Scale All-Organic Aqueous Proton Batteries - Jianyong Zhang; Jingyuan Yu; Wenwei Zhang; Ahmed Eissa Abdelmaoula; Chunhua Han; Zhenzhen Dou; Feng Liang; Lin Xu (Chemical Engineering Journal, 2025)

Increased ZNF83 is a potential prognostic biomarker and regulates oxidative stress-induced ferroptosis in clear cell renal cell carcinoma - Zhaojie Lyu; Huming Wang; Fang Dai; Yu Lin; Hantao Wen; Xudong Liu; Xiaotong Feng; Zihan Xu; Lei Huang (Journal of Molecular Medicine, 2025)

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

Deciphering the microbiome, lipopolysaccharides, and metabolome interplay: Unveiling putrescine's mechanism for enhancing sperm quality in heat-stressed boars - Chenglong Yu; Hao Li; Lun Hua; Lianqiang Che; Bin Feng; Zhengfeng Fang; Shengyu Xu; Yong Zhuo; Jian Li; De Wu; Junjie Zhang; Yan Lin (Theriogenology, 2025)

Integrated transcriptomic and metabolomic analysis of delayed leaf yellowing in postharvest pak choi (Brassica rapa subsp. chinensis) by 2-ethylhexanol (2-EH) - Mina Wang; Xiaozhen Yue; Lingda Yu; Zixin Lin; Shuzhi Yuan; Xiaodi Xu; Jinhua Zuo; Bihong Feng; Qing Wang (Postharvest Biology and Technology, 2025)

Investigating the Sensitivity of NIPAM Gel Dosimetry in CyberKnife Systems Using MRI-based R2 Mapping - Yu-Hsuan Lin; Shih-Wei Huang; Hung-Yi Chen; Hao-Ting Lan; Feng-Yi Su; Shin-Lei Peng; Chun-Hsu Yao (Journal of Medical and Biological Engineering, 2025)
Purpose The CyberKnife delivers precise radiation with sharp dose gradients challenging to measure. N-isopropylacrylamide (NIPAM) gel phantom can capture 3D dose distributions effectively. This study investigates the feasibility of using NIPAM gel dosimetry combined with magnetic resonance imaging (MRI)-based transverse relaxation rate (R2) mapping to verify dose distributions delivered by the CyberKnife system. Methods A total of 24 gel samples were divided into 8 dose groups (0, 3, 6, 9, 12, 15, 18, and 21 Gy), with three samples per dose group for repeat measurements. The NIPAM polymer gels were irradiated by a CyberKnife ® M6 FIM system with a 6 MV x-ray beam. MR images of the NIPAM gel phantom were made 24 h after irradiation using the 3T MRI scanner. The R2 maps corresponding to dose distribution were analyzed using Matlab software. Results Our results demonstrate that R2 values increase with rising irradiation doses, confirming dose-dependent sensitivity. The dose-response curve exhibits a slope of 0.1688 Gy⁻¹ s⁻¹, reflecting the gel dosimeter’s sensitivity, with a strong correlation (R² = 0.85, p = 0.001). Additionally, R2 values vary with depth, peaking at the 30 mm dose center point (D center ) and then gradually decreasing, indicating maximum dose accumulation at D center followed by a decline with increasing depth. Conclusion This study demonstrates that NIPAM gel dosimetry with MRI-based R2 mapping effectively verifies CyberKnife dose distributions. It exhibits strong dose sensitivity and accurately captures sharp gradients, highlighting its potential as a superior alternative to conventional dosimetry methods.

Kirenol ameliorates endotoxin-induced acute lung injury by inhibiting the ERK and JNK phosphorylation–mediated NFκB pathway in mice - Frank Cheau-Feng Lin; Shih-Pin Chen; Sheng-Chien Lin; Ching-Chi Tseng; Stella Chin-Shaw Tsai; Yu-Hsiang Kuan (Inflammopharmacology, 2025)

Molecular chelating and shielding operation for organic photoelectrochemical transistor detection of chlorpyrifos - Lang Lin; Yu-Mei Li; Rui Ban; De-Man Han; Feng-Zao Chen; Wei-Wei Zhao (Analytica Chimica Acta, 2025)

Rice-fish co-culture promotes multiple ecosystem services supporting increased yields - Shuang-Xi Li; Jian Jiang; Wei-Guang Lv; Evan Siemann; Ben A. Woodcock; Yu-Quan Wang; Andrea Cavalieri; Na-Ling Bai; Juan-Qin Zhang; Xian-Qing Zheng; Han-Lin Zhang; Hai-Yun Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

The impact and mechanisms of YL-IPA08, a potent ligand for the translocator protein (18 kDa) on protection against LPS-induced depression and cognitive dysfunction in rodents - Lin-yu Cui; Jing-yao Duan; Jiao-zhao Yan; Jing-ya Wang; Peng Ren; Li-ming Zhang; Wen-zhi Guo; Wei Dai; Yun-feng Li (Metabolic Brain Disease, 2025)

A UDP-glucuronosyltransferase gene UGT379A1 involved in detoxification of lufenuron in Diaphorina citri - Ze-Hao Huang; Qi Pan; Zhen Wu; Yu-Chao Shen; Si-Chen Li; Qi-Qi Yang; Shao-Hui Zhang; Shuang Lei; Yang-Yang Cui; Li-Li Ding; Shi-Jiang Yu; Liu Liu; et al. (Pesticide Biochemistry and Physiology, 2025)

The association between anthropogenic heat and parent-report symptoms of childhood attention deficit hyperactivity disorder in China: A novel perspective reflecting climate change - Tao Yu; Yue Wen; Pei-Pei Dong; Ming-Kun Sun; Samantha E. Qian; Mario Schootman; Michael G. Vaughn; Shu-Li Xu; He-Hai Huang; Feng-Wen Shan; Shi-Fu Zhu; Jing-Yao Wang; et al. (International Journal of Hygiene and Environmental Health, 2025)

Atmospheric black carbon (BC) in Hangzhou, China: Temporal variation, source apportionment, and case study of the 19th Asian Games - Jian Lin; Deming Han; Feng Chen; Xiaorong Zhang; Yang Yang; Lin Yang; Hua Guo; Zechen Yu; Liuyan Cao; Jianbo Shi; Guibin Jiang (Environmental Pollution, 2025)

Performance evaluation of existing reinforced concrete hollow-slab beams: Experiments and fibre beam element-based model updating - Jing-Lin Xiao; Yu-Fei Liu; Hao-Long Feng; Jian-Guo Nie (Engineering Structures, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Combined exposure effects: Multilevel impact analysis of cycloxaprid and microplastics on Penaeus vannamei - Zhi-Yu Lin; Zhi Luo; Zhen-Fei Li; Zhen-Qiang Fu; Feng-Lu Han; Er-Chao Li (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Temporal dynamics of bacterial biofilms and their relationship with heavy metals on expanded polystyrene microplastics - Qun Xie; Yan Feng; Xiangrong Xu; Hengxiang Li; Lang Lin; Weiqiong Yu; Guanghui Zhu; Nenghao Zhong; Minhua Wu; Kai Zhang (Journal of Oceanology and Limnology, 2025)

AI integration into wavelength-based SPR biosensing: Advancements in spectroscopic analysis and detection - Ying-Feng Chang; Yu-Chung Wang; Tsung-Yu Huang; Meng-Chi Li; Sin-You Chen; Yu-Xen Lin; Li-Chen Su; Kwei-Jay Lin (Analytica Chimica Acta, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Plasma proteomics identifies proteins and pathways associated with incident depression in 46,165 adults - Jujiao Kang; Liu Yang; Tianye Jia; Wei Zhang; Lin-Bo Wang; Yu-Jie Zhao; Jia You; Yue-Ting Deng; Yi-Jun Ge; Wei-Shi Liu; Yi Zhang; Yi-Lin Chen; et al. (Science Bulletin, 2025)

Economic viability and overall performance analysis of optimized Cu-Fe-ZSM-5 catalyst for NOx and particulate matter removal using NH3-SCR - Shivani Shirke; Feng-Chih Chou; Yu-Zheng Wang; Yuan-Chung Lin (Fuel, 2025)

Effect of vacuum frying on the structure and bioactivity of proanthocyanidins in Chinese quince (Chaenomeles sinensis Koehne) fruit - Yu Lou; Xu Fang; Zi-Cheng Yang; Jia-Lin Fei; Yu-Ru Feng; Zhao Qin; Hua-Min Liu; Yu-Xiang Ma; Xue-De Wang (Food Chemistry, 2025)

Bromelain hydrolysis and CaCl2 coordination promote the fibrillation of quinoa protein at pH 7 - Lixiao Fu; Xiao Feng; Chaosheng Wu; Jianfeng Wei; Lin Chen; Xi Yu; Qin Liu; Xiaozhi Tang (Food Hydrocolloids, 2025)

Triptolide exposure triggers ovarian inflammation by activating cGAS-STING pathway and decrease oocyte quality in mouse - Si-Yao Cheng; Yi-Fan Yang; Ya-Long Wang; Zhao-Ping Yue; Yan-Zhu Chen; Wen-Ke Wang; Zhi-Ran Xu; Lin-Feng Li; Hao Shen; Zhi-Min Qi; Chang-Long Xu; Yu Liu (Food and Chemical Toxicology, 2025)

Elucidating contributions of meteorology and emissions to O3 variations in coastal city of China during 2019–2022: Insights from VOCs sources - Keran Zhang; Qiaoling Chen; Youwei Hong; Xiaoting Ji; Gaojie Chen; Ziyi Lin; Feng Zhang; Yu Wu; Zhigang Yi; Fuwang Zhang; Mazhan Zhuang; Jinsheng Chen (Environmental Pollution, 2025)

Digital transformation of mental health therapy by integrating digitalized cognitive behavioral therapy and eye movement desensitization and reprocessing - Ju-Yu Wu; Ying-Ying Tsai; Yu-Jie Chen; Fan-Chi Hsiao; Ching-Han Hsu; Yen-Feng Lin; Lun-De Liao (Medical & Biological Engineering & Computing, 2025)

Analysis of serotype distribution and characteristics of nonhemolytic and nonpigmented strains among group B Streptococcus isolates in a southern Taiwan local hospital - Hui-Fang Cheng; Zhe-Yu Kuo; Ching-Chiang Lin; Ho-Feng Chen; Horng-Ren Lo; Huey-Wen Shyu; Yi-Fen Wang (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Role of MFN2 in bovine embryonic development and the mitigation of ER stress - Shu-Ming Shi; Bing Hu; Zhi-Chao Chi; Lin-Yi Qu; Li-Ying Liu; Yu-Yan He; Guan-Lin Jia; Jing-Hang Li; Ilkeun Kong; Yong-Xun Jin; Xian-Feng Yu (Animal Reproduction Science, 2025)

Petrogenesis of late Cretaceous high Ba–Sr granodiorites, SE Lhasa block, China: implications for the reworking of juvenile crust and continental growth - Li-Hang Lin; Ren-Zhi Zhu; Shao-Cong Lai; Jiang-Feng Qin; Yu Zhu; Shao-Wei Zhao; Min Liu (Acta Geochimica, 2025)

Dietary lecithin attenuates adverse effects of high fat diet on growth performance, lipid metabolism, endoplasmic reticulum stress and antioxidant capacity in the intestine of largemouth bass (Micropterus salmoides) - Hua Zheng; Biao Wang; Qing-Lin Li; Tao Zhao; Peng-Cheng Xu; Yu-Feng Song; Zhi Luo (Aquaculture, 2025)

Integrated transcriptomic and proteomic analysis unravels the response mechanisms of Saccharina japonica to heat stress - Zhongyuan Lin; Xuelian Liu; Jinbin Lin; Feng Lin; Yijuan Han; Huibin Xu; Hongmei Lin; Weiqi Tang; Yu Qin; Yanbing Zhu; Hui Ni; Jianjun Lu; et al. (Aquaculture, 2025)

Enhancing porcine oocyte quality and embryo development through natural antioxidants - Zheng Feng; Jia Song; Chenghong Lin; Siyu Wu; Yu Wang; Qingyuan Hui; Yinting Pan; Yiman Zou; Chaofeng Zeng; Jinbiao Guo; Yangli Pei (Theriogenology, 2025)

Strategies for crop straw management in China's major grain regions: Yield-driven conditions and factors influencing the effectiveness of straw return - Jia Cheng; Bai-Jian Lin; Jin-Sai Chen; Hong-Xuan Duan; Yuan-Feng Sun; Xin Zhao; Yash Pal Dang; Zhi-Yu Xu; Hai-Lin Zhang (Resources, Conservation and Recycling, 2025)

Recent progress on triterpenoid derivatives and their anticancer potential - Zi-Xuan Zhao; Qiong-Yu Zou; Ying-Hong Ma; Susan L. Morris‐Natschke; Xiang-Yuan Li; Lin-Chun Shi; Guo-Xu Ma; Xu‐Dong Xu; Mei‐Hua Yang; Zi-Jian Zhao; Yuan-Xiang Li; Jing Xue; et al. (Phytochemistry, 2025)

Novel antibody- and aptamer-based approaches for sensitive detection of mycotoxin fusaric acid in cereal - Shih-Wei Wu; Chia-Yu Hsieh; Biing-Hui Liu; Xin-Jie Lin; Feng-Yih Yu (Food Chemistry, 2025)

Synergistic effects of accompanying heterotrophic bacteria on sulfide-based autotrophic denitrification - Yu-Lin Han; Zhen-Chuan Wu; Feng Jiang; He-Ping Zhao (Chemical Engineering Journal, 2025)

GWAS analysis revealed genomic loci and candidate genes associated with the 100-seed weight in high-latitude-adapted soybean germplasm - Javaid Akhter Bhat; Hui Yu; Lin Weng; Yilin Yuan; Peipei Zhang; Jiantian Leng; Jingjing He; Beifang Zhao; Moran Bu; Songquan Wu; Deyue Yu; Xianzhong Feng (Theoretical and Applied Genetics, 2025)

Low temperature-mediated changes in soil free-living nitrogen fixation functional groups in tree species at different successional stages in subtropical forests - Feng Sun; Wei Lin; Guangyan Deng; Linan Fan; Hanxia Yu; Zhengchao Yu; Changlian Peng (Plant and Soil, 2025)

CircHAT1 regulates the proliferation and phenotype switch of vascular smooth muscle cells in lower extremity arteriosclerosis obliterans through targeting SFRS1 - Xian-ying Huang; Fang-yong Fu; Kai Qian; Qiao-li Feng; Sai Cao; Wei-yu Wu; Yuan-lin Luo; Wei-jie Chen; Zhi Zhang; Shui-chuan Huang (Molecular and Cellular Biochemistry, 2025)

The link between eye movements and cognitive function in mild to moderate Alzheimer’s disease - Xiao-ting Ma; Lin-lin Yao; Shan-wen Liu; Xiao-fen Weng; Run-ying Bao; Yi-fan Yang; Yi-feng Li; Yan-yun Sun; Dan Xu; Zhen-yu Jia; Hua Hu (Experimental Brain Research, 2025)

Cross-sectional and Longitudinal Associations Between Metal Mixtures and Serum C3, C4: Result from the Manganese‑exposed Workers Healthy Cohort - Sencai Lin; Junxiu He; Yinghua Zhou; Yu Bao; Xiuming Feng; Hong Cheng; Haiqing Cai; Sihan Hu; Lin Wang; Yuan Zheng; Mengdi Zhang; Qinghua Fan; et al. (Biological Trace Element Research, 2025)

The Genetic Architecture of Local Adaptation and Reproductive Character Displacement in Scutiger boulengeri Complex (Anura: Megophryidae) - Xiuqin Lin; Chaochao Yan; Yuanfei Wang; Sining Huang; Haoqi Yu; Chungkun Shih; Jianping Jiang; Feng Xie (Molecular Ecology, 2025)
Speciation is a continuous process driven by barriers to gene flow. Based on genome‐wide SNPs (single nucleotide polymorphisms) of 190 toads from 31 sampling sites of Scutiger boulengeri complex, we found evidence for monophyly which represented a continuous speciation process of at least six lineages in S. boulengeri , which radiated and exhibited varying degrees of divergence and gene flow. The SNP‐based phylogenetic tree was largely discordant with the multilocus mitochondrial tree (i.e., S. mammatus and S. glandulatus nested in the lineages of S. boulengeri ) published before. The Min Mountains (MM) and Qinghai‐Tibet Plateau (QTP) lineages differ fundamentally in habitat (i.e., elevation) and morphology (i.e., SVL), we detected signatures of potential high‐altitude and cold adaptation genes in QTP (vs. MM). We found the evidence of reproductive trait disparity (i.e., SVL and nuptial pads) is key to promoting sympatric rather than allopatric species pairs. In addition, we identified selection signals for genes related to sympatric character displacement, genes linked to obesity‐related traits, nuptial spines morphology and enlarged chest nuptial pads in S. mammatus (vs. QTP group of S. boulengeri ). Our study provided new insight and paradigm for a varied speciation pattern from local adaptation of allopatry to sympatric character displacement in the S. boulengeri complex.

Effects of hypoxia and reoxygenation on energy metabolism, immune response, and apoptosis in orange-spotted grouper (Epinephelus coioides) - Yuxin Wu; Yiran Lin; Bing Lin; Yukun Huang; Zhide Yu; Yonghao Ma; Yuwei Feng; Qiaoyi Chen; Along Gao; Hu Shu (Frontiers in Marine Science, 2024)
Hypoxia is an unfavorable environmental condition that produces diverse negative effects in fish. High-density cultures of Epinephelus coioides are more likely to experience hypoxic conditions than those in natural environments. To assess the effects of hypoxia on E. coioides , we examined the related enzyme activities and gene expression after 48 h of hypoxia and 24 h of dissolved oxygen (DO) recovery. Under hypoxic stress (DO: 1.2 ± 0.1 mg/L), the energy supply mode of fish changed from aerobic metabolism to anaerobic metabolism, and the serum glucose content and lactate dehydrogenase activity were significantly upregulated. Total protein, hepatic glycogen, and two key regulatory enzymes (i.e., hexokinase and pyruvate kinase) were differentially expressed in the liver, and mRNA expression of three genes (i.e., LDHA , GLUT1 , and MCT2 ) also showed a high expression trend. In serum, three immune-related enzymes (i.e., alanine aminotransferase, aspartate aminotransferase, and alkaline phosphatase) were found to be involved in regulation by hypoxia and showed different levels of changing patterns. Expression of inflammatory genes (i.e., IL-8 , IFNγ , MyD88 , and NF-kB ) were significantly regulated in liver. With prolongation of hypoxic stress, high expression of apoptotic genes (i.e., p53 , Bax , Bcl-2 , and Caspase-9 ) was closely related to the degree of apoptosis in the liver. Our investigation of the changes in energy metabolism, immune response, and apoptosis of E. coioides under hypoxia and reoxygenation (DO, 6.0 ± 0.1 mg/L) provides a theoretical bases for healthy aquaculture and selection of varieties with tolerance to hypoxia.

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

Protective Effects of Antcin H Isolated from Antrodia cinnamomea Against Neuroinflammation in Huntington’s Disease via NLRP3 Inflammasome Inhibition - Yu-Jun Chang; Cheng-Hsu Chen; Yi-Chen Chen; Ming-Tse Wu; Ting-Yu Lin; Kuo-Feng Hua; Tz-Chuen Ju (Journal of Neuroimmune Pharmacology, 2024)

Bioavailability of dissolved organic matter (DOM) derived from seaweed Gracilaria lemaneiformis meditated by microorganisms - Xiao-Li Ou; Lin-Jian Ou; Yu-Feng Yang (Marine Pollution Bulletin, 2024)

Fecal microbiota transplantation as an effective way in treating methylmercury-poisoned rats - Yanfei Zhang; Qingxuan Liu; Hongxin Xie; Wei Zhang; Xiaoying Lin; Huifeng Zhang; Huan Yu; Yinghui Ma; Chuang Zhang; Hao Geng; Nianqiu Shi; Liwei Cui; et al. (Science of The Total Environment, 2024)

First direct measurements of the nitrogen isotopic composition of vehicle tailpipe-emitted NH3 and implications for the source apportionment of NH3 in urban atmosphere - Yu-Ning Feng; Yunhua Chang; Lin Cheng; Haifeng Yu; Jinling Lv; Wendell W. Walters (Science of The Total Environment, 2024)

Environmental contamination and risks of organic UV filters: Source, discharge, analytical methods and implications for ecological and human health - Yue-hong Sun; Heng-Yu Wu; Feng-Qi Xie; Jia-Ru Ma; Qin-Lin Tang; Yan-Fen Chen; Hao Li; You-Sheng Liu; Guang-Guo Ying (Science of The Total Environment, 2024)

Identification of BpEXP family genes and functional characterization of the BpEXPA1 gene in the stems development of Betula platyphylla - Yao Chi; Zihan Wang; Shizhong Chen; Lin Feng; Meiqi Zhou; Yang Li; Ying Yu; Caiqiu Gao; Chao Wang (Journal of Plant Physiology, 2024)

The rational design of ratiometric probe based on fluorescence carbon dots and its PVA film platform for the detection of Hg2+: Tunable mechanism and the performance - Qiuyan Hu; Haiying Lin; Qingge Feng; Xianghua Wu; Lixin Huang; Yu Duan; Wenlu Lan; Zixuan Chen; Lianghong Li; Jiatong Lv; Jie He; Chun Lv; et al. (Journal of Environmental Chemical Engineering, 2024)

Mechanism and controlling factors of mass transport complexes migration: A case study of the mass transport complexes in the taranaki deep water basin, New Zealand - Yongsheng Zhou; Wei Wu; Jianwei Feng; Guangxu Wang; Aihua Fu; Shiqin Liang; Lulu Wu; Qingchao Li; Weiqing Liu; Zhendong Feng; Changsong Lin; Panpan Chen; et al. (Geomorphology, 2024)

The mining of thermostable β-glucosidase for tea aroma enhancement under brewing conditions - Qi Lin; Cheng Peng; Kunpeng Yu; Yanling Lin; Yongquan Xu; Lijun Li; Hui Ni; Feng Chen (Food Chemistry, 2024)

A ratiometric fluorescent biosensor based on catalytic hairpin assembly reaction for ultrasensitive detection of aflatoxin-producing genes - Tao Yu; Xin Chen; Danni Sun; Dezhao Kong; Zhirong Wang; Feng Lin; Yaqi Li (Food Bioscience, 2024)

Deep insights into the assembly mechanisms, co-occurrence patterns, and functional roles of microbial community in wastewater treatment plants - Zi-Yan Wei; Min Feng; Ding-Xi Zhang; Cheng-Ying Jiang; Ye Deng; Zhu-Jun Wang; Kai Feng; Yang Song; Nan Zhou; Yu-Lin Wang; Shuang-Jiang Liu (Environmental Research, 2024)

Unappreciated role of secondary metabolism-derived small mediators in degrading bisphenol A and antibiotics by a laccase-expressing fungus - Kai Sun; Zi-Hao Wu; Jie Liu; Zhou-Hua Cheng; Dong-Feng Liu; Hui Lin; Han-Qing Yu (Environmental Pollution, 2024)

A zircon petrochronologic perspective on raising the central Tibetan crust - Shu-Hui Ren; Yun-Chuan Zeng; Roberto Weinberg; Ji-Feng Xu; Jian-Lin Chen; Bao-Di Wang; Feng Huang; Xi-Jun Liu; Hong-Xia Yu; Ming-Jian Li (Chemical Geology, 2024)

Cross-Scale Quantitative and Qualitative Study of Grotto Sandstone Under Salt Weathering - Sicheng Lin; Luqi Wang; Wengang Zhang; Shuo Wang; Kaiqiang Zhang; Yu Lei; Siwei Jiang; Huili Chen; Gang Zhao; Xuemei Feng (Rock Mechanics and Rock Engineering, 2024)

The role of Nocardia seriolae-induced autophagy in the development of chronic inflammation in the liver and the formation of granulomas in largemouth bass (Micropterus salmoides) - Shang-Jie Bai; Zheng-Ran Jian; Sheng-Yu He; Lin-Feng Kuang; Zheng-Yang Zhou; Chen-Wang Lu; Zhen-Dong Zhong; Jie He; Quan-Xin Xiong; Shuang-Yan Xiao; Peng-Fei Li; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Alendronate sodium induces G1 phase arrest and apoptosis in human umbilical vein endothelial cells by inhibiting ROS-mediated ERK1/2 signaling - Yi Feng; Shao-Qin Tu; Yu-Luan Hou; Yi-Ting Shao; Lin Chen; Zhi-Hui Mai; Yu-Xuan Wang; Jia-Ming Wei; Sai Zhang; Hong Ai; Zheng Chen (Toxicology, 2024)

Phylogenetic relationships and historical biogeography of silkmoths (Lepidoptera: Bombycidae) suggest an origin in Southern Gondwana - Rung-Juen Lin; Yu-Chi Lin; Michael F. Braby; Andreas Zwick; Yu-Feng Hsu (Molecular Phylogenetics and Evolution, 2024)

Improved identification and monitoring of meteorological, agricultural, and hydrological droughts using the modified nonstationary drought indices in the Yellow River Basin of China - Ben Niu; Yi Li; De Li Liu; Lulu Xie; Lei Wang; Xiaohui Jiang; Hao Feng; Qiang Yu; Jianqiang He; Haixia Lin (Journal of Hydrology, 2024)

Force mechanism analysis of composite microbial dust suppressants based on extracellular polymeric substances (EPS) mode components - Mei-Xuan Ha; Yu Liu; Yue Feng; Xiang-Ming Hu; Yan-Yun Zhao; Jin-Di Liu; Li Chen; Yan-Lin Qu (Journal of Environmental Management, 2024)

Exploration of the flavor diversity of oolong teas: A comprehensive analysis using metabolomics, quantification techniques, and sensory evaluation - Xiaoxiao Feng; Haoli Wang; Yashu Yu; Yiwen Zhu; Jingke Ma; Zhibin Liu; Li Ni; Chih-Cheng Lin; Kequn Wang; Yuan Liu (Food Research International, 2024)

Acrolein exposure affects ovarian function by interfering with glycolysis and mitochondrial energy metabolism in mouse - Yan-Zhu Chen; Wen-Ke Wang; Yi-Fan Yang; Si-Yao Cheng; Lin-Feng Li; Hao Shen; Zhi-Min Qi; Yu Liu (Environmental Pollution, 2024)

Creating smart chlorine-resistant polyamide reverse osmosis membranes via self-healing temperature-responsive nanocontainer functionalization - Qian Yang; Lin Zhang; Yanzhuang Jiang; Song Xu; Beili Pang; Qiong Sun; Na Song; Jianguang Feng; Liyan Yu; Lifeng Dong (Chemical Engineering Journal, 2024)

Pyrene-encapsulated light-emitting π-conjugated polymer with excellent ozone tolerance capacity for large-area and flexible ultra-deep-blue PLEDs with CIEy = 0.08 - Hao Li; Mengna Yu; Yang Li; Manman Luo; Jingyao Ma; Yahui Zhang; Yeyang Wang; Yunlong Zhang; Yan Ma; Lubing Bai; Qiujing Bao; Jiabin Gu; et al. (Chemical Engineering Journal, 2024)

A surfactant-mediated dynamic protection strategy for 100% waterborne fabrication of durable superhydrophobic coatings - Rong-Gang Zhang; Rui Feng; Fang Wang; Hang-Lin Li; Ren-Yi Sun; Hui-Hui Gao; Chun-Bo Li; Yu-Zhong Wang; Fei Song (Chemical Engineering Journal, 2024)

Robust self-healing ion-conductive interlocking dual-network binder based on gradient dynamic bonding for advanced SiO anodes in Li-Ion batteries - De He Weng; Liu Zhen Wu; Zi Feng He; Dong Yu Zhu; Yuan Li; Bole Ma; Qiyu Liu; Liheng Chen; Zhan Lin; Xueqing Qiu (Chemical Engineering Journal, 2024)

A poly (L-glutamic acid)-based porous scaffold with controllable and sequential release of kartogenin for enhanced cartilage regeneration - Xi Yu; Feng Lin; Yaling Zhuang; Shifeng Yan; Kunxi Zhang; Wenguo Cui; Jingbo Yin (Chemical Engineering Journal, 2024)

Discovery of ElABCG39: a key player in ingenol transmembrane efflux identified through genome-wide analysis of ABC transporters in Euphorbia lathyris L. - Guyin Lin; Pirui Li; Linwei Li; Ruyuan Wang; Wanli Zhao; Mei Tian; Junzhi Wu; Shu Xu; Yu Chen; Xu Feng (Plant Cell Reports, 2024)

Prim-O-glucosylcimifugin alleviates influenza virus-induced pneumonia in mice by inhibiting the TGF-β1/PI3KCD/MSK2/RELA signalling pathway - Yu-Jia Wu; Wen-Wen Feng; Zhen-Lin Wu; Yue-Yao Zhang; Jin-Yuan Liu; Pei-Ping Xu (Archives of Virology, 2024)

A study on the transfer of radionuclides and of the resulting radiation dose assessment for marine organisms on the eastern coast of Yantai city - Jialin Ni; Dongjun Chen; Zhen Qian; Jing Lin; Feng Lin; Jianda Ji; Dekun Huang; Tao Yu (Frontiers in Marine Science, 2024)
Oceans are repositories of radionuclides. Radionuclides are transferred through the food chain and cause ionizing radiation hazards for marine organisms. In this study, the transfer characteristics of 226 Ra, 40 K, 14 C, 3 H, 137 Cs and 90 Sr in organisms at different trophic levels in the eastern coast of Yantai city were investigated. The risk of ionizing radiation to organisms was assessed using the ERICA Tool 2.0. The results show no significant changes in the concentration of any of the nuclides in the coastal area compared to the preoperation period of the nuclear power plant. The transfer factor of 137 Cs, 40 K, 226 Ra, 14 C, 90 Sr and 3 H at the different trophic levels of marine organisms were 2.09, 1.29, 1.17, 1.15, 1.06 and 0.74, respectively. The dose rates of ionizing radiation to organisms from six radionuclides ranged from 32.02 nGy·h -1 to 195.49 nGy·h -1 and had a mean value of 102.86 ± 57.30 nGy·h -1 . The main artificial radionuclides ( 14 C, 3 H, 90 Sr, 137 Cs) released by nuclear power plants in the study area produced negligible radiation doses to marine organisms. However, other artificial radionuclides present in the effluents of nuclear power plants ( 99 Tc, 110m Ag and 131 I) as well as other natural radionuclides (includes 210 Po, 210 Pb, etc) were not included, and further evaluation of these is recommended.

Integrated induction of silver resistance determinants and production of extracellular polymeric substances in Cupriavidus metallidurans BS1 in response to silver ions and silver nanoparticles - Jia-Xin Dai; Yanshuang Yu; Le-Xing You; Hong-Lin Zhong; Yuan-Ping Li; Ai-Jun Wang; Jon Chorover; Ren-Wei Feng; Hend A. Alwathnani; Martin Herzberg; Christopher Rensing (Chemosphere, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Malachite green and related substances in environmental samples: Updates on pretreatment and analysis methods - Zu-Yi Chen; Bing-lin He; Yu Bian; Yuan Zhang; Xue-song Feng (Journal of Environmental Chemical Engineering, 2024)

Unraveling the mechanism of selective dissolution in anthracite coal for enhanced permeability through sodium hypochlorite oxidation treatment - Yu Lu; Yili Kang; Zhigang Li; Ming Yue; Teng Zhang; Feng He; Chong Lin; Yue Hu; Ying Li; Zhenjiang You (Fuel, 2024)

Reducing target reliability index of concrete bridge beams through compression yielding - Lin Feng; Yu-Fei Wu; Bing-Cheng Guo; Xiao-Xu Huang (Engineering Structures, 2024)

Dual-Salt aqueous electrolyte for enhancing Charge-Storage properties of VO2 polymorphic cathodes for Zn-Ion batteries - Jing-Hong Huang; Xu-Feng Luo; Tzu-Yu Kuo; Yu-Hua Lai; Purna Chandra Rath; Chun-Wei Huang; Ming-Hsien Lin; An-Yuan Hou; Ju Li; Yu-Sheng Su; Wen-Wei Wu; Jeng-Kuei Chang (Chemical Engineering Journal, 2024)

Neural substrates for regulating self-grooming behavior in rodents - Guanqing Li; Chanyi Lu; Miaomiao Yin; Peng Wang; Pengbo Zhang; Jialiang Wu; Wenqiang Wang; Ding Wang; Mengyue Wang; Jiahan Liu; Xinghan Lin; Jian-Xu Zhang; et al. (Journal of Zhejiang University-SCIENCE B, 2024)

Development of Quantitative Norms for Normal Lung Uptake Based on Three-Dimensional Gallium-67 Single Photon Emission Computed Tomography/Computed Tomography - Tzyy-Ling Chuang; Wei-Lin Li; Yu-Ching Hs; Jyh-Cheng Chen; Yuh-Feng Wang (Journal of Medical and Biological Engineering, 2024)
Purpose Gallium-67 (Ga-67) lung scans assess alveolitis and interstitial lung disease, with Ga-67 accumulation correlating with inflammation intensity as seen in lung biopsy sections. Both semi-quantitative and quantitative methods have been used, with the latter providing an inflammatory activity index linked to lung lavage and histopathological scores. However, differing reference points result in varying outcomes. This study aimed to establish standard Ga-67 index parameters using semi-quantitative analysis and a linear regression model based on planar and SPECT/CT images. Methods Twenty subjects without lung disease received a 5–6 mCi Ga-67 injection via the ankle. Both planar and SPECT/CT images were analyzed, with semi-quantitative values assessed using GraphPad Prism 9.5.1. Results Compared to planar images, SPECT/CT acquisitions for the lung-to-arm uptake ratio proved the most reliable indicator for assessing lung inflammation. Increased lung Ga-67 uptake was defined as greater than 2 standard deviations from the average Ga-67 uptake for healthy subjects. The normal range was 0.065 ± 0.049 for the right side and 0.076 ± 0.070 for the left side. Conclusion Lung-to-arm ratios in SPECT/CT images are more accurate than those in planar images. This method should be adopted as a standard clinical practice, providing more reliable diagnostic information and improving patient management. Future studies should compare patients without lung disease to those with lung disease to determine the diagnostic benefit of these norms.

Functional connectivity of EEG motor rhythms after spinal cord injury - Jiancai Leng; Xin Yu; Chongfeng Wang; Jinzhao Zhao; Jianqun Zhu; Xinyi Chen; Zhaoxin Zhu; Xiuquan Jiang; Jiaqi Zhao; Chao Feng; Qingbo Yang; Jianfei Li; et al. (Cognitive Neurodynamics, 2024)

Rock abrasiveness prediction based on multi-source physical, mechanical and mineralogical properties - Yun Wu; Long-Chuan Deng; Xiao-Zhao Li; Li-Yuan Yu; Jiang-Feng Liu; Jian Lin (Bulletin of Engineering Geology and the Environment, 2024)

Cuproptosis-Associated lncRNA Gene Signature Establishes New Prognostic Profile and Predicts Immunotherapy Response in Endometrial Carcinoma - Xi-Ya Jiang; Jing-Jing Hu; Rui Wang; Wei-Yu Zhang; Qin-Qin Jin; Yin-Ting Yang; Jie Mei; Lin Hong; Hui Yao; Feng Tao; Jie-Jie Li; Yu Liu; et al. (Biochemical Genetics, 2024)
Uterine corpus endometrial carcinoma (UCEC), a prevalent kind of cancerous tumor in female reproductive system that has a dismal prognosis in women worldwide. Given the very limited studies of cuproptosis-related lncRNAs (CRLs) in UCEC. Our purpose was to construct a prognostic profile based on CRLs and explore its assess prognostic value in UCEC victims and its correlation with the immunological microenvironment.Methods: 554 UCEC tumor samples and 23 normal samples’ RNA-seq statistics and clinical details were compiled from data in the TCGA database. CRLs were obtained using Pearson correlation analysis. Using LASSO Cox regression, multivariate Cox regression, and univariate Cox regression analysis, six CRLs are confirmed to develop a risk prediction model at last.We identified two main molecular subtypes and observed that multilayer CRLs modifications were related to patient clinicopathological features, prognosis, and tumor microenvironment (TME) cell infiltration characteristics, and then we verified the prognostic hallmark of UCEC and examined its immunological landscape.Finally, using qRT-PCR, model hub genes’ expression patterns were confirmed. Results: A unique CRL signature was established by the combination of six differently expressed CRLs that were highly linked with the prognosis of UCEC patients. According to their CRLs signatures, the patients were divided into two groups: the low-risk and the high-risk groups. Compared to individuals at high risk, patients at low risk had higher survival rates ( p

Ozone sensitivity regimes vary at different heights in the planetary boundary layer - Xin Li; Wenjie Wang; Suding Yang; Yafang Cheng; Limin Zeng; Xuena Yu; Sihua Lu; Ying Liu; Min Hu; Shaodong Xie; Xiaofeng Huang; Jun Zhou; et al. (Science of The Total Environment, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Saline-alkali land reclamation boosts topsoil carbon storage by preferentially accumulating plant-derived carbon - Lin Chen; Guixiang Zhou; Biao Feng; Chao Wang; Yu Luo; Fang Li; Congcong Shen; Donghao Ma; Congzhi Zhang; Jiabao Zhang (Science Bulletin, 2024)

Solidago canadensis enhances its invasion by modulating prokaryotic communities in the bulk soil - Wen-Tao Qiao; Yong-Feng Wang; Xue-Yan Hou; Dao-Lin Du; Ze-Yu Li; Xin-Yu Wang (International Biodeterioration & Biodegradation, 2024)

Effective stress analysis for repeated shake-consolidation process of multi-story buildings in liquefiable soils during sequential earthquakes - Chih-Wei Lu; Minh-Tam Doan; Shi-Shuenn Chen; Yu-Feng Lin (Computers and Geotechnics, 2024)

Rational design of robust Cu@Ag core-shell nanowires for wearable electronics applications - Yu-Chieh Kuo; Jiajun Fan; Lingqing Zong; Fandi Chen; Ziheng Feng; Chao Liu; Tao Wan; Zi Gu; Long Hu; Peiyuan Guan; Chun-Ho Lin; Mengyao Li; et al. (Chemical Engineering Journal, 2024)

A high-entropy strategy for stable structure of sodium ion batteries: From fundamentals to applications - Xu Liu; Xin-Yu Liu; Nan Zhang; Peng-Fei Wang; Zong-Lin Liu; Jun-Hong Zhang; Jie Shu; Yan Sun; Chun-Sheng Li; Ting-Feng Yi (Chemical Engineering Journal, 2024)

Glucoconjugated monoterpene indole alkaloids with xanthine oxidase inhibitory activity from Ophiorrhiza japonica - Bao-Bao Shi; Fan Xu; Guang-Ru Zhang; Yu He; Qing Liu; Meng-Lin Feng; Zheng-Hui Li; Ji-Kai Liu (Phytochemistry, 2024)

Three new chemical constituents of Senecio raphanifolius - Shu-Wen Huang; Huan He; Zhi-Qiang Li; Yu-Wei Wang; Yuan-Ying Fang; Yu-Lin Feng; Zhi-Feng Li; Qi Wang (Phytochemistry Letters, 2024)

Developmental toxicity of the neonicotinoid pesticide clothianidin to the larvae of the crustacean Decapoda, Penaeus vannamei - Zhi Luo; Zhi-Yu Lin; Zhen-Fei Li; Zhen-Qiang Fu; Feng-Lu Han; Er-Chao Li (Journal of Hazardous Materials, 2024)

Energy-economy-environment assessment of key feedstock production for ternary lithium-ion batteries via hydrometallurgical recycling and natural exploitation - Kai Wang; Quanshui Huang; Ran Feng; Shaojun Liu; Peng Xing; Zi-Tao Yu; Qingyang Lin; Xiang Gao (Journal of Cleaner Production, 2024)

The mitigation of citric acid on cadmium toxicity in Iris tectorum and its effects on the composition of cell walls - Xiao-Fang Yu; Zhi-Wen Wang; Feng-Lian Chen; Mao-Lin Chen; Xin-Yu Zhang; Jun-Rui Zhang; Wen-Yu Ji; Xue Xiao; Li-Juan Yang; Ting Lei; Xi Li; Ming-Yan Jiang (International Biodeterioration & Biodegradation, 2024)

Sulfur and phosphorus co-doped FeCoNiCrMn high-entropy alloys as efficient sulfion oxidation reaction catalysts enabling self-powered asymmetric seawater electrolysis - Zhipeng Yu; Danil W. Boukhvalov; Hao Tan; Dehua Xiong; Chuangshi Feng; Jingwei Wang; Wei Wang; Yang Zhao; Kaiyang Xu; Weifeng Su; Xinyi Xiang; Fei Lin; et al. (Chemical Engineering Journal, 2024)

Inhibition of ER stress using tauroursodeoxycholic acid rescues obesity-evoked cardiac remodeling and contractile anomalies through regulation of ferroptosis - Feng-Juan Li; Miyesaier Abudureyimu; Zeng-Hui Zhang; Jun Tao; Asli F. Ceylan; Jie Lin; Wei Yu; Russel J. Reiter; Milad Ashrafizadeh; Jun Guo; Jun Ren (Chemico-Biological Interactions, 2024)

High dimensional proteomic mapping of bone marrow immune characteristics in immune thrombocytopenia - Feng-Qi Liu; Qing-Yuan Qu; Ying Lei; Qi Chen; Yu-Xiu Chen; Meng-Lin Li; Xue-Yan Sun; Ye-Jun Wu; Qiu-Sha Huang; Hai-Xia Fu; Yuan Kong; Yue-Ying Li; et al. (Science China Life Sciences, 2024)

A Test System for Microwave-Assisted Dual-Mode Mechanical Cutting of Hard Rock Under True Triaxial Compression - Xia-Ting Feng; Xiang-xin Su; Cheng-xiang Yang; Feng Lin; Shi-ping Li; Jiu-yu Zhang; Tian-yang Tong (Rock Mechanics and Rock Engineering, 2024)
This paper introduces a test system for microwave-assisted dual-mode mechanical cutting of hard rock under true triaxial compression. The test system was developed by Northeastern University, China, to simulate the cutting and breaking of hard rock by a tunnel boring machine (TBM). The test system is mainly composed of a dual-mode mechanical cutting subsystem, a true triaxial loading subsystem and a high-power microwave presplitting subsystem. The system performs dual-mode cutting under true triaxial stress, applies a single sensor to monitor the three-dimensional force of the cutter head, and integrates the reduction in the vibration and resistance to torsion during the cutting process. Mechanical cutting tests of basalt under different amounts of microwave irradiation and true triaxial stress conditions were conducted in Chifeng, Inner Mongolia, China. The results showed that microwave radiation presplitting effectively improved the efficiency of mechanical rock breaking. However, after 180 s of microwave irradiation, true triaxial high stress inhibited the mechanical breaking of basalt in terms of the overall excavation depth. During the tests, each system performed stably. The test results verified the reliability of the test system.

Repeated Ketamine Anesthesia during the Neonatal Period Impairs Hippocampal Neurogenesis and Long-Term Neurocognitive Function by Inhibiting Mfn2-Mediated Mitochondrial Fusion in Neural Stem Cells - He Huang; Ning Wang; Jia-Tao Lin; Yong-Kang Qiu; Wei-Feng Wu; Qiang Liu; Chen Chen; Hai-Bi Wang; Yan-Ping Liu; Wei Dong; Jie Wan; Hui Zheng; et al. (Molecular Neurobiology, 2024)

Fluvoxamine Exerts Sigma-1R to Rescue Autophagy via Pom121-Mediated Nucleocytoplasmic Transport of TFEB - Chun-Yu Lin; Hsiang-En Wu; Eddie Feng-Ju Weng; Hsuan-Cheng Wu; Tsung-Ping Su; Shao-Ming Wang (Molecular Neurobiology, 2024)
Expansion of the GGGGCC-RNA repeat is a known cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD), which currently have no cure. Recent studies have indicated the activation of Sigma-1 receptor plays an important role in providing neuroprotection, especially in ALS and Alzheimer’s disease. Nevertheless, the mechanisms underlying Sigma-1R activation and its effect on (G 4 C 2 )n-RNA-induced cell death remain unclear. In this study, we demonstrated that fluvoxamine is a Sigma-1R agonist that can increase chaperone activity and stabilize the protein expression of Pom121 in (G 4 C 2 ) 31 -RNA-expressing NSC34 cells, leading to increased colocalization at the nuclear envelope. Interestingly, fluvoxamine treatment increased Pom121 protein expression without affecting transcription. In C9orf72 -ALS, the nuclear translocation of TFEB autophagy factor decreased owing to nucleocytoplasmic transport defects. Our results showed that pretreatment of NSC34 cells with fluvoxamine promoted the shuttling of TFEB into the nucleus and elevated the expression of LC3-II compared to the overexpression of (G 4 C 2 ) 31 -RNA alone. Additionally, even when used alone, fluvoxamine increases Pom121 expression and TFEB translocation. To summarize, fluvoxamine may act as a promising repurposed medicine for patients with C9orf72 -ALS, as it stabilizes the nucleoporin Pom121 and promotes the translocation of TFEB in (G 4 C 2 ) 31 -RNA-expressing NSC34 cells.

Fungal composition associated with host tree identity mediates nutrient addition effects on wood microbial respiration - Zhenhong Hu; Marcos Fernández‐Martínez; Qinsi He; Zhiyuan Xu; Lin Jiang; Guiyao Zhou; Ji Chen; Ming Nie; Qiang Yu; Hao Feng; Zhiqun Huang; Sean T. Michaletz (Ecology, 2024)
Fungi are key decomposers of deadwood, but the impact of anthropogenic changes in nutrients and temperature on fungal community and its consequences for wood microbial respiration are not well understood. Here, we examined how nitrogen and phosphorus additions (field experiment) and warming (laboratory experiment) together influence fungal composition and microbial respiration from decomposing wood of angiosperms and gymnosperms in a subtropical forest. Nutrient additions significantly increased wood microbial respiration via fungal composition, but effects varied with nutrient types and taxonomic groups. Specifically, phosphorus addition significantly increased wood microbial respiration (65%) through decreased acid phosphatase activity and increased abundance of fast‐decaying fungi (e.g., white rot), while nitrogen addition marginally increased it (30%). Phosphorus addition caused a greater increase in microbial respiration in gymnosperms than in angiosperms (83.3% vs. 46.9%), which was associated with an increase in Basidiomycota:Ascomycota operational taxonomic unit abundance in gymnosperms but a decrease in angiosperms. The temperature dependencies of microbial respiration were remarkably constant across nutrient levels, consistent with metabolic scaling theory hypotheses. This is because there was no significant interaction between temperature and wood phosphorus availability or fungal composition, or the interaction among the three factors. Our results highlight the key role of tree identity in regulating nutrient response of wood microbial respiration through controlling fungal composition. Given that the range of angiosperm species may expand under climate warming and forest management, our data suggest that expansion will decrease nutrient effects on forest carbon cycling in forests previously dominated by gymnosperm species.

Mitochondrial damage and activation of NLRP3 induced by Yersinia ruckeri infection play an important role in the occurrence of diffuse acute inflammation of channel catfish (Ictalurus punctatus) - Chen-Wang Lu; Jie He; Quan-Xin Xiong; Zhen-Dong Zhong; Bin Yang; Sheng Lian; Meng-Meng Wang; Shang-Jie Bai; Lin-Feng Kuang; Zheng-Yang Zhou; Zheng-Ran Jian; Yuan-Chang Gao; et al. (Aquaculture, 2024)

Buried interface modification and light outcoupling strategy for efficient blue perovskite light-emitting diodes - Shuxin Wang; Zhiqiu Yu; Jiajun Qin; Guoyi Chen; Yongjie Liu; Shuaiwei Fan; Chao Ma; Fang Yao; Hongsen Cui; Shun Zhou; Kailian Dong; Qianqian Lin; et al. (Science Bulletin, 2024)

Dynamic changes and the effects of key procedures on the characteristic aroma compounds of Lu’an Guapian green tea during the manufacturing process - Jieyao Yu; Jingzhe Li; Zhi Lin; Yin Zhu; Zhihui Feng; Dejiang Ni; Shengchun Zeng; Xuehong Zeng; Yijun Wang; Jingming Ning; Liang Zhang; Xiaochun Wan; et al. (Food Research International, 2024)

The effect of maturity of tea leaves and processing methods on the formation of milky flavor in white tea - A metabolomic study - Jiao Feng; Jiayun Zhuang; Qianlian Chen; Hongzheng Lin; Qiang Chu; Ping Chen; Fang Wang; Bugui Yu; Zhilong Hao (Food Chemistry, 2024)

Combined dilute alkali and milling process enhances the functionality and gut microbiota fermentability of insoluble corn fiber - Qing Jin; Yiming Feng; Xavier Cabana-Puig; Tran N. Chau; Ronnie Difulvio; Dajun Yu; Anyang Hu; Song Li; Xin M. Luo; Jactone Ogejo; Feng Lin; Haibo Huang (Food Chemistry, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Next-generation neonicotinoid: The impact of cycloxaprid on the crustacean decapod Penaeus vannamei - Zhi Luo; Zhi-Yu Lin; Zhen-Fei Li; Zhen-Qiang Fu; Feng-Lu Han; Er-Chao Li (Chemosphere, 2024)

Infection by virulent wMelPop Wolbachia improves learning and memory capacity in Drosophila melanogaster - Meng-Yan Chen; Dong Li; Zhi-Ning Wang; Feng-Zhen Xu; Yi-Wei Feng; Qiong-Lin Yu; Ying-Ying Wang; Shu Zhang; Yu-Feng Wang (Animal Behaviour, 2024)

Influence of ground-motion duration on seismic performance of shallow-founded buildings in liquefiable soils: An effective stress analysis approach - Chih-Wei Lu; Minh-Tam Doan; Shi-Shuenn Chen; Yu-Feng Lin (Soil Dynamics and Earthquake Engineering, 2024)

Optimizing the rate of straw returning to balance trade-offs between carbon emission budget and rice yield in China - Ruo-Chen Li; Yu-Gang Tian; Fan Wang; Yuan-Feng Sun; Bai-Jian Lin; Yash Pal Dang; Xin Zhao; Hai-Lin Zhang; Zhi-Yu Xu (Sustainable Production and Consumption, 2024)

Congener-specific fate and impact of microcystins in the soil-earthworm system - Bai-Lin Liu; Peng-Fei Yu; Jing-Jie Guo; Li-Si Xie; Xiang Liu; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Nai-Xian Feng; Quan-Ying Cai; Ce-Hui Mo; Qing X. Li (Journal of Hazardous Materials, 2024)

Dynamic changes of microbiota and metabolite of traditional Hainan dregs vinegar during fermentation based on metagenomics and metabolomics - Xiaohan Yu; Chunhe Gu; Xiaoxue Guo; Ruijia Guo; Lin Zhu; Xinrong Qiu; Jun Chai; Fei Liu; Zhen Feng (Food Chemistry, 2024)

Improving cotton productivity and nitrogen use efficiency through late nitrogen fertilization: Evidence from a three-year field experiment in the Xinjiang - Yu Tian; Feng Shi; Xiaojuan Shi; Humei Zhang; Zemin Li; Hairong Lin; Honghai Luo; Karine Chenu (Field Crops Research, 2024)

Design and experiment of an innovative rotational two-level friction damper - Zhenqin Huang; Weiyuan Huang; Chao Zhang; Tianhao Yu; Zijian Lin; Wenchen Lie; Feng Zhao (Engineering Structures, 2024)

3D Visualization of Whole Brain Vessels and Quantification of Vascular Pathology in a Chronic Hypoperfusion Model Causing White Matter Damage - Yang Wu; Jia Ke; Song Ye; Li-Li Shan; Shuai Xu; Shu-Fen Guo; Meng-Ting Li; Tian-Ci Qiao; Zheng-Yu Peng; Yi-Lin Wang; Ming-Yuan Liu; He Wang; et al. (Translational Stroke Research, 2024)

Therapeutic effects and mechanisms of isoxanthohumol on DSS-induced colitis: regulating T cell development, restoring gut microbiota, and improving metabolic disorders - Ya-Na Yang; Bing Han; Mao-Qing Zhang; Na-Nan Chai; Feng-Lin Yu; Wen-Hui Qi; Meng-Yuan Tian; Dong-Zhi Sun; Ying Huang; Qing-Xin Song; Yan Li; Mao-Cui Zhu; et al. (Inflammopharmacology, 2024)

Waste treats waste: Facile fabrication of porous adsorbents from recycled PET and sodium alginate for efficient dye removal - Jing Yu; Lan Bai; Zijun Feng; Lin Chen; Shimei Xu; Yuzhong Wang (Chemosphere, 2024)

New sight in arginine-improved flesh quality: Role of MRFs, cyclins, and WNT signaling in grass carp (Ctenopharyngodon idellus) - Yu-Long Ma; Xiao-Qiu Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Hong-Mei Ren; Rui-Nan Zhang; Shu-Wei Li; Ling Tang; Lin Feng (Aquaculture, 2024)

An analytical model for liquefaction-induced manhole uplifting - Chih-Wei Lu; Yu-Feng Lin; Wei-Lin Lee (Soil Dynamics and Earthquake Engineering, 2024)

Corrigendum to “Arsenic exposure and pulmonary function decline: Potential mediating role of TRAIL in chronic obstructive pulmonary disease patients” [J. Trace Elem. Med. Biol. 83 (2024) 127415] - Ying Liu; Feng-Min Zhu; Juan Xu; You-Peng Deng; Jing Sun; Qi-Yuan He; Zhen-Yu Cheng; Min-Min Tang; Jin Yang; Lin Fu; Hui Zhao (Journal of Trace Elements in Medicine and Biology, 2024)

Arsenic exposure and pulmonary function decline: Potential mediating role of TRAIL in chronic obstructive pulmonary disease patients - Ying Liu; Feng-Min Zhu; Juan Xu; You-Peng Deng; Jing Sun; Qi-Yuan He; Zhen-Yu Cheng; Min-Min Tang; Jin Yang; Lin Fu; Hui Zhao (Journal of Trace Elements in Medicine and Biology, 2024)

PHB2 inhibits WSSV replication by promoting the nuclear translocation of STAT - Jia-Yu Si; Lian-Jie Wu; Feng-Lin Xu; Xiao-Tong Cao; Jiang-Feng Lan (Fish & Shellfish Immunology, 2024)

Geochemical indications of hydrothermal fluid through sediments within the Geolin Mounds and Mienhua Volcano hydrothermal fields, southernmost Okinawa Trough - Feng-Hsin Hsu; Chih-Chieh Su; Yu-Shih Lin; Hsiao-Fen Lee; Mei-Fei Chu; Tefang Lan; Shein-Fu Wu; Song-Chuen Chen (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

In-situ reactivation and reuse of micronsized sulfidated zero-valent iron using SRB-enriched culture: A sustainable PRB technology - Yanduo Yang; Chungeng Zhan; Yu Li; Jiajia Zeng; Keyue Lin; Jianliang Sun; Feng Jiang (Water Research, 2024)

Application of data-driven mixing parameterization scheme in a regional ocean model - Qingfeng Feng; Guoqing Han; Yu Liu; Xiayan Lin; Bo Li; Xiaoqian Gao; Changming Dong; Yinghui He; Haili Wang (Ocean Modelling, 2024)

The study on the shortcut approach for cooperative disposal of arsenic-rich copper dust and waste acid to prepare high-purity copper - Feng Yan; Hongkun Dai; Yu Wang; Maoguang Ruan; Shanrong Zhao; Xiaohua Yu; Yan Lin (Journal of Cleaner Production, 2024)

Self-synthesis and performance analysis of a Cu-Fe composite ZSM-5 zeolitic catalyst for NOx reduction and particulate matter removal using NH3 SCR - Shivani Shirke; Feng-Chih Chou; Yu-Zheng Wang; Pei-Cheng Cheng; Shang-Cyuan Chen; Yuan-Chung Lin (Journal of Environmental Chemical Engineering, 2024)

Enhancing acid stability of citral through internal structure modulation in nanostructured lipid carriers with solid lipids and phospholipids - Simin Feng; Jialu Sheng; Jiahao Yu; Yang Lin; Ping Shao (Food Research International, 2024)

PM2.5 exposure-induced senescence-associated secretory phenotype in airway smooth muscle cells contributes to airway remodeling - Pei-Pei Cheng; Fan Yu; Shuai-Jun Chen; Xiao Feng; Zi-Heng Jia; Shi-He Hu; Xiao-Lin Cui; Ya-Ya Zhou; Qian Niu; Li-Mei Liang; Meng Wang; Lin-Jie Song; et al. (Environmental Pollution, 2024)

Heteroatom doping-induced Pt dispersion and electronic effect for boosting the catalytic performance in the hydrogenation of nitrobenzene to p-aminophenol - Chong Yao; Jiwei Wu; Limei Pan; Lu Yu; Jie Luo; Jinjin Shan; Jie Liu; Chunshan Lu; Feng Feng; Xiaoliang Xu; Lili Lin; Yuxue Yue; et al. (Chemical Engineering Journal, 2024)

Performance boosting by induction heating for hydrolysis of carbonyl sulfide using magnetic ordered mesoporous alumina as catalyst - Chao Huang; Yunchuan Hong; Binchen Wu; Hongchao Yu; Xiangqian Du; Min Pan; Weiyi Fan; Fei Gao; Feng Wu; Yixin Zhong; Lin Li; Guoshu Deng; et al. (Chemical Engineering Journal, 2024)

Research on satellite data-driven algorithm for ground-level ozone concentration inversion: case of Yunnan, China - Weiqiang Yu; Tao Feng; Xingwei Man; Huan Lin; Haonan Zhang; Rui Liu (Earth Science Informatics, 2024)

Long Non-coding RNA LINC00342 Promotes the Proliferation, Invasion, and Migration of Primary Hepatocellular Carcinoma Cells by Regulating the Expression of miRNA-19a-3p, miRNA-545-5p, and miRNA-203a-3p - Zong-Xi Yao; Jun-Hao Tu; Yu-Lin Liu; Xiao-Feng Xue; Lei Qin (Biochemical Genetics, 2024)

Ecosystem services in the typical black soil region of Northeastern China: implications for the optimal land use pattern - Lin Feng; Ziyang Yu; Guoping Lei (Environment, Development and Sustainability, 2024)

Toward sustainable development of tuna longline fishery in Taiwan: Value chain analysis - Wen-Hong Liu; Chih-Cheng Lin; Cheng-Feng Lee; Chien-Shu Tsai; Tsung-Yu Yang (Marine Policy, 2024)

Long-term biogas slurry application increases microbial necromass but not plant lignin contribution to soil organic carbon in paddy soils as regulated by fungal community - Zhaoming Chen; Jinchuan Ma; Junwei Ma; Jing Ye; Qiaogang Yu; Ping Zou; Wanchun Sun; Hui Lin; Feng Wang; Xinlin Zhao; Qiang Wang (Waste Management, 2024)

The paradigm for exceptional iodine capture by nonporous amorphous electron-deficient cyclophanes - Baoqi Wu; Zhi-Wei Li; Feng Lin; Rongzhi Tang; Wanqing Zhang; Hongwei Liu; Gangfeng Ouyang; Yu Tan (Journal of Hazardous Materials, 2024)

A versatile CuCo@PDA nanozyme-based aptamer-mediated lateral flow assay for highly sensitive, on-site and dual-readout detection of Aflatoxin B1 - Xu Zhu; Jing Tang; Xilian Ouyang; Yibo Liao; Haopeng Feng; Jiangfang Yu; Li Chen; Yating Lu; Yuyang Yi; Lin Tang (Journal of Hazardous Materials, 2024)

Antimicrobial resistance characteristics and phylogenetic relationships of pleuromutilin-resistant Enterococcus isolates from different environmental samples along a laying hen production chain - Cong Lin; Yuxuan Feng; Xianjun Xie; Haoyu Zhang; Jie Wu; Yixiao Zhu; Jing Yu; Jingyi Feng; Wen Su; Shanming Lai; Anyun Zhang (Journal of Environmental Sciences, 2024)

Ethylene thiourea exposure induces neurobehavioral toxicity in zebrafish by disrupting axon growth and neuromuscular junctions - Jingming Wang; Zhiquan Yu; Yongfeng Wang; Yuanyao Chen; Lin Xiao; Yanjun Zong; Qiyuan Feng; Lianqi Peng; Huiping Zhang; Chunyan Liu (Journal of Environmental Sciences, 2024)

Analyzing the correlation between quinolone-resistant Escherichia coli resistance rates and climate factors: A comprehensive analysis across 31 Chinese provinces - Yi-Chang Zhao; Zhi-Hua Sun; Ming-Xuan Xiao; Jia-Kai Li; Huai-yuan Liu; Hua-Lin Cai; Wei Cao; Yu Feng; Bi-Kui Zhang; Miao Yan (Environmental Research, 2024)

Impact of urban land development on carbon emission performance based on a multidimensional framework - Xinhui Feng; Xinle Lin; Yan Li; Jiayu Yang; Er Yu; Congying He; Kaige Lei; Weiming Gao (Environmental Impact Assessment Review, 2024)

A global synthesis of the patterns of genetic diversity in endangered and invasive plants - Zhi-Zhou He; Gisela C. Stotz; Xiang Liu; Jia-Jia Liu; Yu-Guo Wang; Ji Yang; Lin-Feng Li; Wen-Ju Zhang; Peng Nan; Zhi-Ping Song (Biological Conservation, 2024)

Optimization of Microwave Presplitting Iron Ore to Improve Mechanical Mining Efficiency - Feng Lin; Xia-ting Feng; Shi-ping Li; Jiu-yu Zhang; Xiang-xin Su; Tian-yang Tong (Rock Mechanics and Rock Engineering, 2024)

The Alasu rock avalanche in the Tianshan Mountains, China: fragmentation, landforms, and kinematics - Qi-wen Lin; Yu-feng Wang; Qian-gong Cheng; Jing Huang; Hao-ran Tian; Guo-xiang Liu; Ke He (Landslides, 2024)

Nocardia seriolae mediates granulomatous chronic inflammation of spleen in Micropterus salmoides through necroptosis - Zheng-Yang Zhou; Sheng-Yu He; Chen-Wang Lu; Shang-Jie Bai; Lin-Feng Kuang; Bin Yang; Sheng Lian; Zheng-Ran Jian; Meng-Meng Wang; Shuang-Yan Xiao; Qing Yu; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Long-term stable and efficient degradation of ornidazole with minimized by-product formation by a biological sulfidogenic process based on elemental sulfur - Jiajia Zeng; Shuqun Xu; Keyue Lin; Si Yao; Bin Yang; Zhanhui Peng; Tianwei Hao; Xiaoyu Yu; Tingting Zhu; Feng Jiang; Jianliang Sun (Water Research, 2024)

Overdose with the anesthetic propofol causes hematological cytotoxicity and immune cell alteration in an experimental ex vivo whole blood culture model - Chung-Hsi Hsing; Yu-Ping Hung; Ming-Chung Lin; Chia-Ling Chen; Yung-Ting Wang; Po-Chun Tseng; Rahmat Dani Satria; Chiou-Feng Lin (Toxicology in Vitro, 2024)

Tri-objective Stochastic Model to Optimize Location and Sizing of Scooter Battery Swapping Station - Yu-Hao Lin; Ping-Yu Liu; Chieh-Feng Chiang (Sustainable Cities and Society, 2024)

Physiological and transcriptomic analysis reveals the toxic and protective mechanisms of marine microalga Chlorella pyrenoidosa in response to TiO2 nanoparticles and UV-B radiation - Lin Zhu; Sulan Feng; Yu Li; Xuemei Sun; Qi Sui; Bijuan Chen; Keming Qu; Bin Xia (Science of The Total Environment, 2024)

Direct and indirect consumption activities drive distinct urban-rural inequalities in air pollution-related mortality in China - Jingxu Wang; Jintai Lin; Yu Liu; Feng Wu; Ruijing Ni; Lulu Chen; Fangxuan Ren; Mingxi Du; Zhongyi Li; Haoyu Zhang; Zhengzhong Liu (Science Bulletin, 2024)

Sustainable paramylon production from food waste by Euglena gracilis using a waste-based cell immobilisation technique - Jin-Hua Mou; Si-Fen Liu; Li-Li Yang; Zi-Hao Qin; Yu-Feng Yang; Zhen-Yao Wang; Hong-Ye Li; Carol Sze Ki Lin; Xiang Wang (Chemical Engineering Journal, 2024)

Unraveling fluorescent mechanism of biomass-sourced carbon dots based on three major components: Cellulose, lignin, and protein - Tian-xiang Li; De-fang Zhao; Lin Li; Yang Meng; Yu-hui Xie; Dong Feng; Feng Wu; Delong Xie; Yuxin Liu; Yi Mei (Bioresource Technology, 2024)

Peroxisome Proliferator-Activated Receptor-γ Coactivator-1α in the Spotlight with Multiple Sclerosis - Ya-Na Yang; Mao-Qing Zhang; Feng-Lin Yu; Bing Han; Ming-Yue Bao; Yan He; Xing Li; Yuan Zhang (Neuroscience Bulletin, 2024)

Breaking prolonged sitting increases 24-h physical activity and self-perceived energy levels but does not acutely affect cognition in healthy adults - Feng-Chih Kuo; Yun-Ting Lin; Ting-Yu Chueh; Yu-Kai Chang; Tsung-Min Hung; Yung-Chih Chen (European Journal of Applied Physiology, 2024)

Exploring the potential of the nano-based sunscreens and antioxidants for preventing and treating skin photoaging - Chih-Hung Lin; Ming-Hsien Lin; Yu-Kuo Chung; Ahmed Alalaiwe; Chi-Feng Hung; Jia-You Fang (Chemosphere, 2024)

Effects of sub-chronic exposure to microcystin-LR on the endocrine system of male rats - Yu-Ting Wang; Qian-Hui Wu; Liang Chen; John P. Giesy; Lin-Lin Xu; Wen-Li Xu; Jun He; Ting Shi; Yi-Qing Liu; Shi-Man Xiao; Ye-Ke Wang; Feng Chen; et al. (Science of The Total Environment, 2024)

Lignan glucosides from Gentiana macrophylla with potential anti-arthritis and hepatoprotective activities - Pei-Qi Huang; Kai-Wen Kang; Dan-Yu Huang; Chun-Lin Zhao; Hao Zheng; Yong-Xin Luo; Yan Wen; Ming-Feng Zou; Dong-Li Li; Ri-Hui Wu; Yun-Cai Tian; Yong Tian; et al. (Phytochemistry, 2024)

Rare 7,9′-dinorlignans with neuroprotective activity from the roots of Lindera aggregata (Sims) Kosterm - Qian-Qing Liu; Lin-An Xiong; Jia-Yu Qian; Ting-Ting Gong; Lie-Feng Ma; Luo Fang; Zha-Jun Zhan (Phytochemistry, 2024)

Gaseous signaling molecule H2S as a multitasking signal molecule in ROS metabolism of Oryza sativa under thiocyanate (SCN−) pollution - Yu-Xi Feng; Peng Tian; Yu-Juan Lin; Dan-Yang Cao; Cheng-Zhi Li; Abid Ullah (Environmental Pollution, 2024)

Identification and fine-mapping of QYrAS286-2BL conferring adult-plant resistance to stripe rust in cultivated emmer wheat - Yuqin Li; Yanling Hu; Yun Jiang; Qiang Zhou; Yu He; Jingshu He; Xuejiao Chen; Xue Chen; Bo Jiang; Ming Hao; Shunzong Ning; Zhongwei Yuan; et al. (Theoretical and Applied Genetics, 2024)

Technological diversity in the tropical-subtropical zone of Southwest China during the terminal Pleistocene: excavations at Fodongdi Cave - Fa-Xiang Huan; Shi-Xia Yang; Feng Gao; Xin-Ying Zhou; Jian-Ping Yue; Yu-Xiu Zhang; Jin-Xu Wu; Qi-Jun Ruan; Kai-Wei Qiu; Jing-wen Xu; Nai-Ru Lin; Yi-Ren Wang; et al. (Archaeological and Anthropological Sciences, 2024)

Isalo scorpion Cytotoxic peptide (IsCT) improved the physical barrier of the intestine on on-growing grass carp (Ctenopharyngodon idella) - Chong Zhang; Qi-Yu Hu; Lin Feng; Pei Wu; Yang Liu; Sheng-Yao Kuang; Ling Tang; Jiang Li; Xiao-Qiu Zhou; Wei-Dan Jiang (Aquaculture, 2023)

Toxic vascular effects of polystyrene microplastic exposure - Jianlong Yan; Yanbin Pan; Junbo He; Xinli Pang; Wenming Shao; Caiping Wang; Rongning Wang; Yaqiong He; Min Zhang; Juheng Ye; Chaolan Lin; Feng Lin; et al. (Science of The Total Environment, 2023)

Ioxynil and diethylstilbestrol impair cardiac performance and shell growth in the mussel Mytilus coruscus - Yi-Feng Li; Yue-Tong Lin; Yu-Qing Wang; Ji-Yue Ni; Deborah M. Power (Science of The Total Environment, 2023)

Non-steroidal anti-inflammatory drugs (NSAIDs) in the environment: Recent updates on the occurrence, fate, hazards and removal technologies - Jia-yuan Lin; Yuan Zhang; Yu Bian; Yi-xin Zhang; Rong-zhu Du; Ming Li; Yue Tan; Xue-song Feng (Science of The Total Environment, 2023)

Preclinical evaluation of RQ3013, a broad-spectrum mRNA vaccine against SARS-CoV-2 variants - Shudan Tan; Jinghua Zhao; Xue Hu; Yufeng Li; Zihan Wu; Guoliang Lu; Zhaoli Yu; Binhe Du; Yan Liu; Li Li; Yuchen Chen; Ye Li; et al. (Science Bulletin, 2023)

Evaluating the toxic mechanism of 1,2-diacetylbenzene in neural cells/tissues: The favorable impact of silibinin - Li-Yu Fay; Jun-Yi Chien; Ching-Feng Weng; Huai-Sheng Kuo; Dann-Ying Liou; Wei-Hao Weng; Chi-Hung Lin; Ya-Tzu Chen; Wen-Hung Huang; Wen-Cheng Huang; May-Jywan Tsai; Henrich Cheng (NeuroToxicology, 2023)

Hydraulic circulation technology remediates the contaminated groundwater with petroleum hydrocarbon: Evidence from laboratory and field tests - Zhan Chen; Yu-Lin Wu; Tao Li; Yi-Xiang Wang; Ling-Kang Xuan; Shi-Feng Lu (Journal of Cleaner Production, 2023)

A crosslinked waterborne poly(vinyl acetate) for greenhouse gas fixation with improved elastomeric properties, shape-memory ability, and recyclability - Yen-Chuan Chen; Ying-Chi Huang; Yi-Hua Huang; Ying-Feng Lin; Ho-Ching Huang; Ru-Jong Jeng; Yu-Wei Cheng; Chien-Hsin Wu (Journal of Environmental Chemical Engineering, 2023)

Encapsulation and release of citral using nanostructured lipid carriers: A study on the impact of different preparation methods - Simin Feng; Jialu Sheng; Jiahao Yu; Yang Lin; Ping Shao (Food Bioscience, 2023)

Side chain modulated carbazole-based bifunctional hole-shuttle interlayer simultaneously improves interfacial energy level alignment and defect passivation in high-efficiency perovskite solar cells - Yuan-Yu Chiu; Shih-Hsuan Chen; Kun-Mu Lee; Tz-Feng Lin; Ming-Chung Wu (Chemical Engineering Journal, 2023)

Low-dose IL-2 Treatment Rescues Cognitive Deficits by Repairing the Imbalance Between Treg and Th17 Cells at the Middle Alzheimer’s Disease Stage - Lin Yuan; Lei Xie; Hao Zhang; Yu Zhang; Yunbo Wei; Jinhong Feng; Li Cui; Rui Tian; Jia Feng; Di Yu; Cui Lv (Journal of Neuroimmune Pharmacology, 2023)

Practically Feasible Sensor-Embedded Kinetic Assessment Piano System for Quantifying Striking Force of Digits During Piano Playing - Kuan-Yin Lai; Chieh-Hsiang Hsu; Yu-Chen Lin; Chung-Hung Tsai; Cheng-Feng Lin; Li-Chieh Kuo; Fong-Chin Su (Journal of Medical and Biological Engineering, 2023)
Purpose Understanding the pathogenesis of playing-related hand disorders through investigations based on coordination and biomechanical perspectives is indispensable. This study aimed to establish a sensor-embedded kinetic assessment piano system (SeKAPS) and conduct reliability and validity tests for this system. In addition, the differences in digit coordination between professional pianists and non-musicians were investigated. Methods Twelve subminiature load cells were embedded in the middle of the 12 corresponding keys of an upright piano. A customized calibrated system with a load cell was used to establish the criterion-related validity of the SeKAPS. The reliability of the SeKAPS was determined by 22 volunteer pianists. The other ten professional pianists and ten non-musicians were recruited to indicate the feasibility of the SeKAPS to distinguish the performing differences between groups. Results The R 2 values of regression analyses for the load cells were 0.993–0.999 ( p < 0.001), indicating high validity. The ICC values of the modified keys were 0.82–0.93, indicating high reliability. The results indicate that SeKAPS is accurate in detecting the striking force of digits during piano playing. Significant differences existed in the mean peak force and mean CVs of the peak force of the specific digits between the two groups. The results showed differences in finger control strategies between the pianists and non-musicians. Conclusion The SeKAPS may provide a valuable assessment for assisting pianists in understanding digit force control and movement strategies to achieve efficient digit coordination.

Anti-complement factor H (CFH) autoantibodies could delay pristane-induced lupus nephritis - Lin-Lin Li; Zhong-qiu Luan; Ying Tan; Hui Wang; Xiao-Juan Yu; Zhen Qu; Feng Yu; Min Chen (Immunologic Research, 2023)
Purpose Anti-complement factor H (CFH) autoantibodies could be detected in lupus and its significance remained to be elucidated. Herein, we aimed to explore the roles of anti-CFH autoantibodies based on pristane-induced lupus mice. Methods Twenty-four female Balb/c mice were randomly divided into four groups, with one group injected with pristane (pristane group), one group with pristane and then human CFH (hCFH) (pristane-CFH group) 3 times, and the other two as vertical controls, PBS group and PBS-CFH group. Histopathological analysis was performed six months after pristane administration. Levels of hCFH, anti-CFH autoantibodies and anti-dsDNA antibody were detected. Murine IgG (mIgG) were purified and cross-reactivity, epitopes, subclasses and functional analysis were further evaluated in vitro. Results Immunization with hCFH and subsequent development of anti-CFH autoantibodies significantly attenuated nephritis of pristane-induced lupus, including lower levels of urinary protein and serum creatinine, decreased levels of serum anti-dsDNA antibody, greatly ameliorated renal histopathologic damage, decreased IgG, complements (C1q, C3) deposits and lower inflammatory factor (IL-6) expression in glomerulus. Furthermore, the purified mIgG (contained anti-CFH autoantibodies) could recognize both hCFH and murine CFH, and the epitopes were predominantly located in hCFH short consensus repeats (SCRs) 1–4, 7 and 11–14. The IgG subclasses were predominant IgG1. The autoantibodies could enhance the binding between hCFH and C3b, and increase factor I mediated-C3b lysis in vitro. Conclusion Our results suggested that anti-CFH autoantibodies could attenuate pristane-induced lupus nephritis by increasing bio-functions of CFH on regulating complement activation and controlling inflammation.

CDK6 is a novel predictive and prognosis biomarker correlated with immune infiltrates in multiple human neoplasms, including small cell lung carcinoma - Guo-Sheng Li; Zhi-Guang Huang; Dong-Ming Li; Yu-Lu Tang; Jin-Hua Zheng; Lin Yang; Yue Feng; Jun-Xi Peng; Jing-Xiao Li; Yu-Xing Tang; Neng-Yong Zeng; Mei-Hua Jin; et al. (Functional & Integrative Genomics, 2023)

Nanoplastic-Induced Biological Effects In Vivo and In Vitro: An Overview - Hongxin Xie; Xue Tian; Xiaoying Lin; Rui Chen; Saima Hameed; Liming Wang; Yong-Liang Yu; Bai Li; Yu-Feng Li (Reviews of Environmental Contamination and Toxicology, 2023)

Comparison of demineralized bone matrix with different cycling crushing times in posterolateral fusion model of athymic rats - Shao-Lin Ji; Xiao-Dan Zhao; Li-Min Wang; Cheng-Gang Pang; Wen-Jing Li; Kun-Xiu Song; Rong-Xing Ma; Rui-Feng Li; Jing-Yu Zhang; Yong-Cheng Hu (Cell and Tissue Banking, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Miticidal activity of Photorhabdus luminescens for controlling two spider mites, Tetranychus urticae and Tetranychus kanzawai, in Carica papaya - Tzay-Tien Hsieh; Ju-Chun Chang; Chienyan Hsieh; Jui-Tang Tseng; Show-Jow Lin; Cheng-Ju Yang; Feng-Chia Hsieh; Yu-Shin Nai (BioControl, 2023)

SIRT3-dependent mitochondrial redox homeostasis mitigates CHK1 inhibition combined with gemcitabine treatment induced cardiotoxicity in hiPSC-CMs and mice - Jia-Wen Chen; Tian-Kai Shan; Tian-Wen Wei; Qi-Qi Jiang; Chong Du; Ling-Feng Gu; Tong-Tong Yang; Liu-Hua Zhou; Si-Bo Wang; Yu-Lin Bao; Hao Wang; Yong Ji; et al. (Archives of Toxicology, 2023)

A machine-learning assisted multi-cluster assessment for decarbonization in the chemical fiber industry toward net-zero: A case study in a Chinese province - Ran Feng; Xu Xu; Zi-Tao Yu; Qingyang Lin (Journal of Cleaner Production, 2023)

Polyphenols modulate microalgae metabolism with a particular increment in lipid accumulation - Li-Gong Zou; Dan-Lin Zheng; Yi-Tong Yao; Fu-Fang Wen; Da-Wei Li; Yu-Feng Yang; Wei-Dong Yang; Srinivasan Balamurugan; Hang Fai Kwok; Hong-Ye Li (Fuel, 2023)

Oxidation of Sb(III) by Shewanella species with the assistance of extracellular organic matter - Kai-Li Wang; Di Min; Guan-Lin Chen; Dong-Feng Liu; Han-Qing Yu (Environmental Research, 2023)

Active subduction and strain partitioning in western Myanmar revealed by a dense survey GNSS network - Eric O. Lindsey; Yu Wang; Lin Thu Aung; Jeng-Hann Chong; Qiang Qiu; Rishav Mallick; Lujia Feng; Pyae Sone Aung; Tha Zin Htet Tin; Saw Myat Min; Kyle Bradley; Oo Than; et al. (Earth and Planetary Science Letters, 2023)

Fabrication of diamond/copper composite thin plate based on a single-layer close packed diamond particles network for heat dissipation - Jia-wan Peng; Feng-lin Zhang; Yu-mei Zhou; Ling-kang Xiong; Yao-jie Huang; Hong-qun Tang (Chemical Engineering Journal, 2023)

Utilization of lipidic food waste as low-cost nutrients for enhancing the potentiality of biofuel production from engineered diatom under temperature variations - Yu-Feng Yang; Guang-Bin Ye; Hua-Jun Wang; Hong-Ye Li; Carol Sze Ki Lin; Xiao-Fei Zheng; Arivalagan Pugazhendhi; Xiang Wang (Bioresource Technology, 2023)

The modification of meteorological factors on the relationship between air pollution and periodontal diseases: an exploration based on different interaction strategies - Kai Huang; Lin-Fei Feng; Zhe-Ye Liu; Zhen-Hua Li; Yi-Cheng Mao; Xin-Qiang Wang; Jia-Wen Zhao; Kang-Di Zhang; Ying-Qing Li; Jie Wang; Wen-Jie Yu; Xin Cheng; et al. (Environmental Geochemistry and Health, 2023)

Contrasting laboratory and field outcomes of bat–moth interactions - Aiqing Lin; Jiqian Li; Yinli Hu; Maojun Zhong; Minglun Yu; Nina Ma; Tingting Wei; Jinhong Luo; Jiang Feng (Molecular Ecology, 2023)
Predator–prey interactions are important but difficult to study in the field. Therefore, laboratory studies are often used to examine the outcomes of predator–prey interactions. Previous laboratory studies have shown that moth hearing and ultrasound production can help prey avoid being eaten by bats. We report here that laboratory behavioural outcomes may not accurately reflect the outcomes of field bat–moth interactions. We tested the success rates of two bat species capturing moths with distinct anti‐bat tactics using behavioural experiments. We compared the results with the dietary composition of field bats using next‐generation DNA sequencing. Rhinolophus episcopus and Rhinolophus osgoodi had a lower rate of capture success when hunting for moths that produce anti‐bat clicks than for silent eared moths and earless moths. Unexpectedly, the success rates of the bats capturing silent eared moths and earless moths did not differ significantly from each other. However, the field bats had a higher proportion of silent eared moths than that of earless moths and that of clicking moths in their diets. The difference between the proportions of silent eared moths and earless moths in the bat diets can be explained by the difference between their abundance in bat foraging habitats. These findings suggest that moth defensive tactics, bat countertactics and moth availability collectively shape the diets of insectivorous bats. This study illustrates the importance of using a combination of behavioural experiments and molecular genetic techniques to reveal the complex interactions between predators and prey in nature.

Functional-structural decoupling in visual network is associated with cognitive decline in patients with type 2 diabetes mellitus: evidence from a multimodal MRI analysis - Min-Hua Ni; Ying Yu; Yang Yang; Ze-Yang Li; Teng Ma; Hao Xie; Si-Ning Li; Pan Dai; Xin-Yu Cao; Yan-Yan Cui; Jun-Ling Zhu; Guang-Bin Cui; et al. (Brain Imaging and Behavior, 2023)

One-step synthesis of thiol-functionalized metal coordination polymers: effective and superfast removal of Hg (II) in the different matrices to ppb level - Mingzhi Li; Yongjie Tuo; Qiuxia Wu; Haiying Lin; Qingge Feng; Yu Duan; Junqi Wei; Zixuan Chen; Jiatong Lv; Lianghong Li (Chemosphere, 2023)

Mechanisms of high ammonium loading promoted phosphorus release from shallow lake sediments: A five-year large-scale experiment - Shuo-Nan Ma; Yuan-Feng Xu; Hai-Jun Wang; Hong-Zhu Wang; Yan Li; Xu-Meng Dong; Ji-Lin Xu; Qing Yu; Martin Søndergaard; Erik Jeppesen (Water Research, 2023)

Genome-centric metagenomics provides new insights into metabolic pathways of polyhydroxyalkanoates biosynthesis and functional microorganisms subsisting on municipal organic wastes - Ruo-hong Li; Jin Huang; Cheng-xi Liu; Ke Yu; Feng Guo; You Li; Zuo-hong Chen; Xuan Wang; Ren-xin Zhao; Jia-yu Zhang; Jia-jin Liang; Yun Li; et al. (Water Research, 2023)

Efficacy of a porcine reproductive and respiratory syndrome virus 1 (PRRSV-1) natural recombinant against a heterologous PRRSV-1 isolate both clustered within the subgroup of BJEU06-1-like isolates - Chen Li; Shuai Li; Shubin Li; Ming Qiu; Hong Lin; Zhe Sun; Yuejia Qiu; Wenhao Qi; Binghui Feng; Jixiang Li; Wanglong Zheng; Xiuling Yu; et al. (Veterinary Microbiology, 2023)

Using drone soundings to study the impacts and compositions of plumes from a gigantic coal-fired power plant - Yen-Chen Chen; Jia-Lin Wang; Chih-Yuan Chang; Ming-Tung Chuang; Charles C.-K. Chou; Xiang-Xu Pan; Yu-Jui Ho; Chang-Feng Ou-Yang; Wen-Tzu Liu; Chih-Chung Chang (Science of The Total Environment, 2023)

Energy optimal depth control for multimodal underwater vehicles with a high accuracy buoyancy actuated system - Junjun Cao; Rui Lin; Chunhu Liu; Hao Feng; Caoyang Yu; Baoheng Yao; Lian Lian (Ocean Engineering, 2023)

Host-derived peptide signals regulate Pseudomonas aeruginosa virulence stress via the ParRS and CprRS two-component systems - Ning-Lin Zhao; Zi-Qi Zhu; Han-Zhong Feng; Ying-Jie Song; Qin Huang; Xing-Yu Mou; Cheng Nong; Yong-Xing He; Rui Bao (Journal of Hazardous Materials, 2023)

Regulation on copper-tolerance in Citrus sinensis seedlings by boron addition: Insights from root exudates, related metabolism, and gene expression - Huan-Huan Chen; Zhi-Chao Zheng; Wen-Shu Chen; Rong-Yu Rao; Xu-Feng Chen; Xin Ye; Jiuxin Guo; Lin-Tong Yang; Li-Song Chen (Journal of Hazardous Materials, 2023)

Convergence of soil bacterial communities with time and reduction of bacterial interaction complexity in response to meso- and microplastic stress - Lin Yue; Yangbo Liu; Guanhui Li; Hui Deng; Yuanyuan Zhao; Dan Feng; Hongfei Sun; Huamei Yu; Chengjun Ge; Haiying Chen (Journal of Environmental Chemical Engineering, 2023)

Combining HUMSC secretome and a conductive hydrogel enhances angiogenesis and electrical transmission at myocardial infarct sites to support cardiac repair - Shu-yi He; Lin-yu Long; Zhi-cun Wang; Wen-qi Liu; Wen Zhang; Cheng Hu; Xiao-feng Wu; Ruiqi Dong; Hong-song Fan; Qing-Jiang; Ying-ying Tong; Guang-hua Yang; et al. (Chemical Engineering Journal, 2023)

Advanced electrooxidation of florfenicol using 3D printed Nb2O5/Ti electrodes: Degradation efficiency, dehalogenation performance, and toxicity reduction - Yun-fei Zhang; Jia-le Gao; Shen-gui Chen; Lei Li; Jian-hui Xu; Dan Li; Yu-feng Liu; Xin Quan; Xin Fu; Ya-zi Xie; Jing-nan Wu; Dan-ying Lin; et al. (Chemical Engineering Journal, 2023)

Heart valve-inspired self-lubricating anticoagulant surfaces - Yang Cheng; Zhiwei Yang; Xiaodan Gou; Qing Yang; Zichen Zhang; Shiyu Cui; Yuhua Ren; Lihong Fan; Haifeng Zhang; Zheng Fang; Yu Lu; Lin Kai; et al. (Chemical Engineering Journal, 2023)

Aflatoxin B1 affects porcine alveolar macrophage growth through the calcium signaling pathway mediated by the ceRNA regulatory network - Yu Tian; Pei-Yu Dong; Sheng-Lin Liang; Long Li; Shu-Er Zhang; Francesca Gioia Klinger; Wei Shen; You-Yu Yan; Xi-Feng Zhang (Molecular Biology Reports, 2023)

Effects of submergence stress on germination and seedling growth of direct-seeded rice and evaluation of submergence tolerance - Rongping Zhang; Ningning Zhou; Lin Zhou; Rigui Ashi; Tingyu Feng; Keyuan Zhang; Xuehuan Liao; Lise Aer; Xia Wu; Kangning Yu; Jianchao Shu; Xuewu He; et al. (Paddy and Water Environment, 2023)

Plant selection and ecological microhabitat drive the shrub-associated microbiome selection in revegetated shrub ecosystems - Zongrui Lai; Yanfei Sun; Yang Yu; Zhen Liu; Yuxuan Bai; Yangui Qiao; Lin Miao; Weiwei She; Shugao Qin; Wei Feng (Applied Soil Ecology, 2023)

Associations of metal mixtures with thyroid function and potential interactions with iodine status: results from a cross-sectional study in MEWHC - Xiaoting Ge; Junxiu He; Sencai Lin; Yu Bao; Yuan Zheng; Hong Cheng; Haiqing Cai; Xiuming Feng; Wenjun Yang; Sihan Hu; Lin Wang; Qijing Liao; et al. (Environmental Science and Pollution Research, 2023)

Neurobehavioral disorders induced by environmental zinc in female zebrafish (Danio rerio): Insights from brain and intestine transcriptional and metabolic signatures - Fan Yu; Zhi-Shuai Hou; Hong-Rui Luo; Hong-Xia Li; Xue-Fan Cui; Jian-Lin Li; Wen-Rong Feng; Yong-Kai Tang; Sheng-Yan Su; Qin-Feng Gao; Jun Xiao; Pao Xu (Chemosphere, 2023)

PM10 and PM2.5 chemical source profiles of road dust over China: Composition, spatio-temporal distribution, and source apportionment - Zi Lin; Yaqin Ji; Yu Lin; Yi Yang; Yuzong Gao; Miao Wang; Yang Xiao; Jingqi Zhao; Yinchang Feng; Wen Yang; Baoqing Wang (Urban Climate, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Metabolomic profiling of Panax ginseng in response to Fusarium solani infection - Guijia Zhao; Shuyang Xing; Yang Wang; Xu Yang; Ru Sun; Lin Feng; Jifeng Wang; Tianxia Sun; Wenhui Lian; Yu Zhao (Physiological and Molecular Plant Pathology, 2023)

CDN1163, a SERCA activator, causes intracellular Ca2+ leak, mitochondrial hyperpolarization and cell cycle arrest in mouse neuronal N2A cells - Yi-Ping Huang; Wen-Wei Huang; Kun-Feng Tsai; Lian-Ru Shiao; Zih-He Yang; Shao-Yun Tseng; Yu-Hsien Lin; Cing-Yu Chen; Paul Chan; Yuk-Man Leung (NeuroToxicology, 2023)

Investigation of the fall armyworm (Spodoptera frugiperda) gut microbiome and entomopathogenic fungus-induced pathobiome - Yao-Chia Liu; Tzu-Han Chen; Yu-Feng Huang; Chang-Lin Chen; Yu-Shin Nai (Journal of Invertebrate Pathology, 2023)

Open-framework hybrid zinc/tin selenide as an ultrafast adsorbent for Cs+, Ba2+, Co2+, and Ni2+ - Yang Liu; Feng-Qi Shi; Xin Hao; Meng-Yu Li; Lin Cheng; Cheng Wang; Kai-Yao Wang (Journal of Hazardous Materials, 2023)

Conjugated polymers S-scheme homojunction with large internal electric field and matching interface for efficient visible light photocatalytic degradation of ciprofloxacin - Mingjuan Zhang; Lin Tang; Yuan Zhu; Yi Zhang; Junli Liu; Jiajia Wang; Chengyang Feng; Lu Qiao; Yu Chen (Journal of Cleaner Production, 2023)

Emulsions containing composite (clove, oregano, and cinnamon) essential oils: Phase inversion preparation, physicochemical properties and antibacterial mechanism - Jiajie Hu; Hangxin Zhu; Yuwei Feng; Mijia Yu; Yueqiang Xu; Yadong Zhao; Bin Zheng; Jiheng Lin; Wenhua Miao; Rusen Zhou; Patrick J. Cullen (Food Chemistry, 2023)

Combination of surfactants and enzyme cocktails for enhancing woody biomass saccharification and bioethanol production from lab-scale to pilot-scale - Wei Qi; Qifa Feng; Wen Wang; Yu Zhang; Yunzi Hu; Usama Shakeel; Lin Xiao; Lan Wang; Hongzhang Chen; Cuiyi Liang (Bioresource Technology, 2023)

Evolutionary roles of polyploidization‐derived structural variations in the phenotypic diversification of Panax species - Yu‐Xin Zhang; Xin‐Feng Wang; Yu‐Qian Niu; Yu‐Guo Wang; Wen‐Ju Zhang; Zhi‐Ping Song; Ji Yang; Lin‐Feng Li (Molecular Ecology, 2023)
Genomic structural variations (SVs) are widespread in plant and animal genomes and play important roles in phenotypic novelty and species adaptation. Frequent whole genome duplications followed by (re)diploidizations have resulted in high diversity of genome architecture among extant species. In this study, we identified abundant genomic SVs in the Panax genus that are hypothesized to have occurred through during the repeated polyploidizations/(re)diploidizations. Our genome‐wide comparisons demonstrated that although these polyploidization‐derived SVs have evolved at distinct evolutionary stages, a large number of SV‐intersecting genes showed enrichment in functionally important pathways related to secondary metabolites, photosynthesis and basic cellular activities. In line with these observations, our metabolic analyses of these Panax species revealed high diversity of primary and secondary metabolites both at the tissue and interspecific levels. In particular, genomic SVs identified at ginsenoside biosynthesis genes, including copy number variation and large fragment deletion, appear to have played important roles in the evolution and diversification of ginsenosides. A further herbivore deterrence experiment demonstrated that, as major triterpenoidal saponins found exclusively in Panax , ginsenosides provide protection against insect herbivores. Our study provides new insights on how polyploidization‐derived SVs have contributed to phenotypic novelty and plant adaptation.

Influence of cyclic hardening characteristic on seismic performance of welded austenitic stainless steel H-section beam-column - Yu Chen; Feng Zhou; Shuai Zheng; Jianquan Li; Chengzhi Shang; Xingxin Lin (Engineering Structures, 2023)

30 Years of Climate Change before and after the Impoundment of the Three Gorges Reservoir - Junqi Liu; Chen Lin; Shan Dong; Ruixue Feng; Aijun Su; Jinghui Cui; Shupeng Yu (Journal of Earth Science, 2023)

Estimating arsenic biotransfer factors from feed to chicken: a viable approach to animal feed risk assessment - Ching-Chi Hung; Hsin-Tang Lin; Ching-Yi Chen; Kuan-Yi Chen; Tsung-Yu Lee; Chow-Feng Chiang (Food Additives & Contaminants: Part A, 2023)

An electronic sense-based machine learning model to predict formulas and processes for vegetable-fruit beverages - Hai-Bin Ren; Bao-Long Feng; Hong-Yue Wang; Jing-Jian Zhang; Xiao-Sen Bai; Fei Gao; Yan Yang; Qi Zhang; Ye-Hui Wang; Li-Li Wang; Ya-Ting Rong; Yu-Lin Sun; et al. (Computers and Electronics in Agriculture, 2023)

Magnetic anaerobic granular sludge for sequestration and immobilization of Pb - Rui Zhou; Han Li; Chengshuai Liu; Yizhang Liu; Jyh-Fu Lee; Yu-Jung Lin; Zhang Yan; Zhangyi Xu; Xiaoyun Yi; Chunhua Feng (Water Research, 2023)

Kinetics and mechanism study of dyes degradation in electric field-promoting catalytic wet air oxidation process - Lin-Feng Zhai; Yi Hu; Shu-Ya Xu; He-You Guo; Min Sun; Jun Yu; Yan Wang (Journal of Environmental Management, 2023)

Variation in microbiological heterogeneity in Chinese strong-flavor Baijiu fermentation for four representative varieties of sorghum - Mao-Ke Liu; Yu-Ming Tang; Cheng-Yuan Liu; Xin-Hui Tian; Ji-Wei Zhang; Xiao-Li Fan; Kai-Feng Jiang; Xian-Lin Ni; Xin-Yu Zhang (International Journal of Food Microbiology, 2023)

Gut microbiota and ionizing radiation-induced damage: Is there a link? - Yueqiu Yu; Xiang Lin; Feiyang Feng; Yuanyun Wei; Shuang Wei; Yaqi Gong; Caimao Guo; Qingyu Wang; Peimeng Shuai; Tiantian Wang; Hui Qin; Guoqing Li; et al. (Environmental Research, 2023)

Navigating practical applications of food waste valorisation based on the effects of food waste origins and storage conditions - Jin-Hua Mou; Zi-Hao Qin; Yu-Feng Yang; Si-Fen Liu; Wei Yan; Lan Zheng; Ya-Hui Miao; Hong-Ye Li; Patrick Fickers; Carol Sze Ki Lin; Xiang Wang (Chemical Engineering Journal, 2023)

Root-derived C distribution drives N transport and transformation after 13C and 15 N labelling on paddy and upland soils - Xiaoting Wang; Ruirui Chen; Evangelos Petropoulos; Bingqian Yu; Xiangui Lin; Youzhi Feng (Biology and Fertility of Soils, 2023)

Environmental quality mediates the ecological dominance of cooperatively breeding birds - Yu‐Heng Lin; Ying‐Yu Chen; Dustin R. Rubenstein; Ming Liu; Mark Liu; Sheng‐Feng Shen (Ecology Letters, 2023)
Although social species as diverse as humans and ants are among the most abundant organisms on Earth, animals cooperate and form groups for many reasons. How these different reasons for grouping affect a species' ecological dominance remains unknown. Here we use a theoretical model to demonstrate that the different fitness benefits that animals receive by forming groups depend on the quality of their environment, which in turn impacts their ecological dominance and resilience to global change. We then test the model's key predictions using phylogenetic comparative analysis of >6500 bird species. As predicted, we find that cooperative breeders occurring in harsh and fluctuating environments have larger ranges and greater abundances than non‐cooperative breeders, but cooperative breeders occurring in benign and stable environments do not. Using our model, we further show that social species living in harsh and fluctuating environments will be less vulnerable to climate change than non‐social species.

A coupled electrochemical process for schwertmannite recovery from acid mine drainage: Important roles of anodic reactive oxygen species and cathodic alkaline - Ziyuan Huang; Huanxin Ma; Chengshuai Liu; Fangyuan Meng; Jyh-Fu Lee; Yu-Jung Lin; Xiaoyun Yi; Zhi Dang; Chunhua Feng (Journal of Hazardous Materials, 2023)

Efficient adsorption and photocatalytic degradation of water emerging contaminants through nanoarchitectonics of pore sizes and optical properties of zirconium-based MOFs - Jia-Xuan Tan; Zih-Yu Chen; Celine H. Chen; Ming-Feng Hsieh; Angela Yu-Chen Lin; Season S. Chen; Kevin C.-W. Wu (Journal of Hazardous Materials, 2023)

The efficiency of full-scale subsurface constructed wetlands with high hydraulic loading rates in removing pharmaceutical and personal care products from secondary effluent - Jiaxi Wang; Xia Yu; Hui Lin; Jiusi Wang; Liping Chen; Yanzhou Ding; Shuai Feng; Jingjing Zhang; Beibei Ye; Xiping Kan; Qian Sui (Journal of Hazardous Materials, 2023)

Off-design characteristics of energy conversion equipment in integrated energy systems - Yu Fu; Haiyang Lin; Biao Feng; Cuiping Ma; Qie Sun; Ronald Wennersten (Journal of Cleaner Production, 2023)

Cues of intraguild predators (Harmonia axyridis) and different temperatures alter foraging and oviposition strategies of the parasitoid Aphidius gifuensis - Xing-Lin Yu; Yi Feng; Tong-Xian Liu; Bao-Li Qiu (Journal of Asia-Pacific Entomology, 2023)

Sex-specific effect of perfluoroalkyl substances exposure on liver and thyroid function biomarkers: A mixture approach - Ze Yang; Ruifang Liu; Hongbo Liu; Jiemin Wei; Xiaohui Lin; Mingyue Zhang; Yu Chen; Jingyun Zhang; Meiqing Sun; Zhe Feng; Jian Liu; Xiangyang Liu; et al. (International Journal of Hygiene and Environmental Health, 2023)

Gestational cadmium exposure disrupts fetal liver development via repressing estrogen biosynthesis in placental trophoblasts - Yi-Ting Fu; Jin Zhang; Wei-Bo Liu; Yu-Feng Zhang; Shuang Zhang; Lu-Lu Tan; Qing Lin; Kong-Wen Ou-Yang; Yong-Wei Xiong; Wei Chang; Hao Li; Jun-Ying Yu; et al. (Food and Chemical Toxicology, 2023)

Improved bioremediation of PCDD/Fs contaminated soil by mycelium-free liquids induced by agro-industrial residues - Chih-Yu Cheng; Zhi-Feng Zhang; Acharee Kaewlaoyoong; Jing-Ting Huang; Nicholas Kiprotich Cheruiyot; Chitsan Lin; Hung-Chou Huang (Bioresource Technology Reports, 2023)

Countering beta-cypermethrin: partitioning roles of the insect gut and its bacteria - Li Bai; Xiao-Lin Cai; Man-Yu Li; Fu-Xiao Wang; Chuan-Shan Zou; Jun-Sheng Zhang; Ming-Yu Xie; Feng-Hui Qi; Tian-Zhong Jing (Journal of Pest Science, 2023)

Distribution of polycyclic aromatic hydrocarbons in indoor/outdoor window films and the indoor film/air partition of northeastern Chinese college dormitories - Yu Sun; Li-Yan Liu; Lin-Lin Lv; Xi-Xi Zhou; Yu-Yan Luo; Jin-Ze Qu; Wan-Li Ma; Zi-Feng Zhang; Li Song; Li Wang; Yi-Fan Li (Chemosphere, 2023)

Synergistic effect of intercalation and EDLC electrosorption of 2D/3D interconnected architectures to boost capacitive deionization for water desalination via MoSe2/mesoporous carbon hollow spheres - Jiaxin Du; Wenle Xing; Jiaqi Yu; Jing Feng; Lin Tang; Wangwang Tang (Water Research, 2023)

Metabolic and transcriptional responses demonstrating enhanced thermal tolerance in domesticated abalone - Feng Yu; Yawei Shen; Wenzhu Peng; Nan Chen; Yang Gan; Qizhen Xiao; Junyu Liu; Yisha Lu; Weihong Lin; Zhaofang Han; Xuan Luo; Weiwei You; et al. (Science of The Total Environment, 2023)

Polyethylene and polypropylene microplastics reduce chemisorption of cadmium in paddy soil and increase its bioaccessibility and bioavailability - Jing-Jie Guo; Fen Li; Hai-Chuan Xiao; Bai-Lin Liu; Lin-Nan Feng; Peng-Fei Yu; Can Meng; Hai-Ming Zhao; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Lei Xiang; et al. (Journal of Hazardous Materials, 2023)

Development and application of an in-situ shipboard device for the measurement of gamma-ray emitters in seawater - Jianhua He; Christos Tsabaris; Wen Yu; Feng Lin (Journal of Environmental Radioactivity, 2023)

Improving the biodegradation of chicken feathers by a Bacillus licheniformis ZSZ6 mutant and application of hydrolysate - Chunhong Cui; Liqiong Sun; Xuelian Chen; Yu Zhu; Zhi Zheng; Dongmei Mao; Mingxu Li; Yuxin Li; Yajun Cao; Bing Feng; Hui Wang; Lin Wang; et al. (International Biodeterioration & Biodegradation, 2023)

Evolution characteristic of atmospheric black carbon particles at a coastal site in the Pearl River Delta, China - Jing Wei; Xiao-Feng Huang; Yan Peng; Xiao-Yu Lin; Zhen-Hua Lei; Li-Ming Cao; Wen-Fei Zhu; Song Guo; Ling-Yan He (Environmental Pollution, 2023)

QTL-seq and transcriptomic integrative analyses reveal two positively regulated genes that control the low-temperature germination ability of MTP–maize introgression lines - Ru-Yu He; Jun-Jun Zheng; Yu Chen; Ze-Yang Pan; Tao Yang; Yang Zhou; Xiao-Feng Li; Xinyi Nan; Ying-Zheng Li; Ming-Jun Cheng; Yan Li; Yang Li; et al. (Theoretical and Applied Genetics, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Failure mechanism of a large-scale composite deposits caused by the water level increases - Xin Zhang; Guo-xiang Tu; Qi-feng Luo; Hao Tang; Yu-lin Zhang; An-run Li (Journal of Mountain Science, 2023)

Genomic architecture underlying morphological and physiological adaptation to high elevation in a songbird - Chia‐Wei Lu; Shih‐Ting Huang; Shun‐Jen Cheng; Chen‐Tau Lin; Yu‐Cheng Hsu; Cheng‐Te Yao; Feng Dong; Chih‐Ming Hung; Hao‐Chih Kuo (Molecular Ecology, 2023)
Organisms often acquire physiological and morphological modifications to conquer ecological challenges when colonizing new environments which lead to their adaptive evolution. However, deciphering the genomic mechanism of ecological adaptation is difficult because ecological environments are often too complex for straightforward interpretation. Thus, we examined the adaptation of a widespread songbird—the rufous‐capped babbler ( Cyanoderma ruficeps )—to a relatively simple system: distinct environments across elevational gradients on the mountainous island of Taiwan. We focused on the genomic sequences of 43 birds from five populations to show that the Taiwan group split from its sister group in mainland China around 1–2 million years ago (Ma) and colonized the montane habitats of Taiwan at least twice around 0.03–0.22 Ma. The montane and lowland Taiwan populations diverged with gene flow between them, suggesting strong selection associated with different elevations. We found that the montane babblers had smaller beaks than the lowland ones, consistent with Allen's rule, and identified candidate genes— COL9A1 and SOX11 —underlying the beak size changes. We also found that altitudinally divergent mutations were mostly located in noncoding regions and tended to accumulate in chromosomal inversions and autosomes. The altitudinally divergent mutations might regulate genes related to haematopoietic, metabolic, immune, auditory and vision functions, as well as cerebrum morphology and plumage development. The results reveal the genomic bases of morphological and physiological adaptation in this species to the low temperature, hypoxia and high UV light environment at high elevation. These findings improve our understanding of how ecological adaptation drives population divergence from the perspective of genomic architecture.

Punctiform Breakup and Initial Oceanization in the Central Red Sea Rift - Ya-Di Sang; Bakhit M. T. Adam; Chun-Feng Li; Liang Huang; Yong-Lin Wen; Jia-Ling Zhang; Yu-Tao Liu (Journal of Marine Science and Engineering, 2023)
The Central Red Sea Rift is a natural laboratory to study the transition from rifting to spreading. Based on new reflection seismic profiles and gravity modeling, we examined the crustal structure, tectonic evolution, breakup mechanism, and future evolution of the Central Red Sea Rift. Along this rift axis, the breakup of continental lithosphere is discontinuous and the oceanic crust is limited to the axial deeps. The punctiform breakup and formation of deeps is assisted by mantle upwelling and topographic uplift, but the nucleation is directly controlled by the normal-fault system. The discontinuities spaced between axial deeps within the relatively continuous central troughs are presently axial domes or highs and will evolve into new deeps with tectonic subsidence. Isolated deeps will grow and connect with each other to become a continuous central trough, before transitioning into a unified spreading center.

Two new germacrane sesquiterpenoids from the inflorescences of Mikania micrantha - Tao Lou; Qiao-Lin Xu; Yu-Ling Tan; Shao-Bo Liu; Shan-Xuan Zhang; Ying Zeng; Feng-Qiang Jiang; Jian-Wen Tan (Phytochemistry Letters, 2023)

The ability of pre-magnetized zero-valent iron for peroxymonosulfate activation to remove ofloxacin - Yang Wu; Jing-ying Zhu; Jia-wen Bai; Li-feng Lin; Chang-ping Yu (Chemical Engineering Journal, 2023)

Effectiveness of Combined Exercise and Physiotherapy Intervention in Improving Functional Activity of Patients with Knee Osteoarthritis in Muslim Pray Movements - Rakhmad Rosadi; Po-Ting Wu; Yu-Lin You; Li-Chieh Kuo; Cheng-Feng Lin (Journal of Medical and Biological Engineering, 2023)

Changes in the Microbiota and their Roles in Patients with Type 2 Diabetes Mellitus - Qiao-ling He; Hui-chao Wang; Yu-ke Ma; Rui-lin Yang; Zhi-feng Dai; Jing-nan Yang; Yao Xu; Dan-dan Wei; Li-ping Zhu; Xu-hong Lin (Current Microbiology, 2023)

Deciphering basic and key traits of antibiotic resistome in influent and effluent of hospital wastewater treatment systems - Lin Zhu; Ling Yuan; Xin-Yi Shuai; Ze-Jun Lin; Yu-Jie Sun; Zhen-Chao Zhou; Ling-Xuan Meng; Feng Ju; Hong Chen (Water Research, 2023)

Photoinduced transformation of ferrihydrite in the presence of aqueous sulfite and its influence on the repartitioning of Cd - Jinwen Qiu; Xiaokang Hou; Yuan Ren; Chengshuai Liu; Fangyuan Meng; Jyh-Fu Lee; Yu-Jung Lin; Ziyuan Huang; Huanxin Ma; Zhenqing Shi; Chunhua Feng (Water Research, 2023)

Isopimaric acid, an ion channel regulator, regulates calcium and oxidative phosphorylation pathways to inhibit breast cancer proliferation and metastasis - Jiacheng Li; Xiaozhen Liu; Lin Chen; Xinping Zhu; Zhihong Yu; Liyao Dong; Xinyun Zhao; Hongling Zou; Qin Wei; Yongcai Feng; Yongqiang Zhu; Kequn Chai; et al. (Toxicology and Applied Pharmacology, 2023)

Environmentally-friendly biorecovery of manganese from electrolytic manganese residue using a novel Penicillium oxalicum strain Z6-5-1: Kinetics and mechanism - Shuai Zhao; Bo-Wen Zheng; Yu-Cang Wang; Fei He; Li-Juan Wang; Xiong Lin; Xue-Mei Luo; Jia-Xun Feng (Journal of Hazardous Materials, 2023)

Microbiological quality of roof tank water in an urban village in southeastern China - Dong Hu; Jie Zeng; Jing Chen; Wenfang Lin; Xinyan Xiao; Mingbao Feng; Xin Yu (Journal of Environmental Sciences, 2023)

Dynamic change of oligopeptides and free amino acids composition in five types of tea with different fermentation degree processed from the same batch of fresh tea (Camelilia Sinensis. L.) leaves - Feng Zhao; Wenxi Wu; Chi Wang; Xiaojuan Wang; Hui Liu; Jiang Qian; Chunping Cai; Yong Xie; Yu Lin (Food Chemistry, 2023)

Expired yogurt-derived, three-dimensional water evaporator with sustainable self-cleaning and high mechanical properties for the desalination and purification of oil-contaminated seawater - Yahui Liu; Yitong Cui; Chunyu Yang; Huiming Lin; Feng Zhang; Kai Yu; Wei Guo; Fengyu Qu (Desalination, 2023)

A self-powered wearable piezoelectric nanogenerator for physiological monitoring based on lead zirconate titanate/microfibrillated cellulose@polyvinyl alcohol (PZT/MFC@PVA) composition - Yanfang Guan; Mingyang Bai; Qilong Wang; Lei Liu; Shaobo Yu; Bingru Kong; Feng Lv; Mingshuo Guo; Guangyu Liu; Lingfeng Li; Lin Zhang; Yang Lin; et al. (Chemical Engineering Journal, 2023)

Rising temperatures affect the interspecific interference competition between Harmonia axyridis and Propylea japonica, and their predation rate on Myzus persicae - Xing-Lin Yu; Yu-Jie Zhang; Jun-Feng Zuo; Xun Luo; Long Zhang; Zhuo-Ma Danzeng; Bo Wang; Peng-Liang Xia; Shi-Ze Zhang; Tong-Xian Liu; Yi Feng (Journal of Pest Science, 2023)

Dynamic changes in cell wall-degrading enzymes and physio-biochemistry of ginseng in response to fusarium oxysporum infection - Lin Feng; Guijia Zhao; Ru Sun; Jifeng Wang; Tianxia Sun; Shuyang Xing; Wenhui Lian; Yu Zhao (European Journal of Plant Pathology, 2023)

A critical thermal transition driving spring phenology of Northern Hemisphere conifers - Jian‐Guo Huang; Yaling Zhang; Minhuang Wang; Xiaohan Yu; Annie Deslauriers; Patrick Fonti; Eryuan Liang; Harri Mäkinen; Walter Oberhuber; Cyrille B. K. Rathgeber; Roberto Tognetti; Václav Treml; et al. (Global Change Biology, 2023)
Despite growing interest in predicting plant phenological shifts, advanced spring phenology by global climate change remains debated. Evidence documenting either small or large advancement of spring phenology to rising temperature over the spatio‐temporal scales implies a potential existence of a thermal threshold in the responses of forests to global warming. We collected a unique data set of xylem cell‐wall‐thickening onset dates in 20 coniferous species covering a broad mean annual temperature (MAT) gradient (−3.05 to 22.9°C) across the Northern Hemisphere (latitudes 23°–66° N). Along the MAT gradient, we identified a threshold temperature (using segmented regression) of 4.9 ± 1.1°C, above which the response of xylem phenology to rising temperatures significantly decline. This threshold separates the Northern Hemisphere conifers into cold and warm thermal niches, with MAT and spring forcing being the primary drivers for the onset dates (estimated by linear and Bayesian mixed‐effect models), respectively. The identified thermal threshold should be integrated into the Earth‐System‐Models for a better understanding of spring phenology in response to global warming and an improved prediction of global climate‐carbon feedbacks.

Effects of habitat usage on hypoxia avoidance behavior and exposure in reef-dependent marine coastal species - Haolin Yu; Guangjie Fang; Kenneth A. Rose; Jiazheng Lin; Jie Feng; Haiyan Wang; Qingxian Cao; Yanli Tang; Tao Zhang (Frontiers in Marine Science, 2023)
Reef habitat in coastal ecosystems is increasingly being augmented with artificial reefs (ARs) and is simultaneously experiencing increasing hypoxia due to eutrophication and climate change. Relatively little is known about the effects of hypoxia on organisms that use complex habitat arrangements and how the presence of highly preferred AR habitat can affect the exposure of organisms to low dissolved oxygen (DO). We performed two laboratory experiments that used video recording of behavioral movement to explore 1) habitat usage and staying duration of individuals continuously exposed to 3, 5, and 7 mg/L dissolved oxygen (DO) in a complex of multiple preferred and avoided habitat types, and 2) the impact of ARs on exposure to different DO concentrations under a series of two-way replicated choice experiments with or without AR placement on the low-oxygen side. Six common reef-dependent species found in the northeastern sea areas of China were used (i.e., rockfish Sebastes schlegelii and Hexagrammos otakii , filefish Thamnaconus modestus , flatfish Pseudopleuronectes yokohamae , sea cucumber Stichopus japonicus , and crab Charybdis japonica ). Results showed that lower DO levels decreased the usage of preferred habitats of the sea cucumber and the habitat-generalist filefish but increased the habitat affinity to preferred habitat types for the two habitat-specific rockfishes. Low DO had no effect on the crab’s habitat usage. In the choice experiment, all three fish species avoided 1 mg/L, and the rockfish S. schlegelii continued to avoid the lower DO when given choices involving pairs of 3, 5, and 7 mg/L, while H. otakii and the flatfish showed less avoidance. The availability of ARs affected exposure to low DO for the habitat-preferring rockfishes but was not significant for the flatfish. This study provides information for assessing the ecological effects and potential for adaptation through behavioral movement for key reef-dependent species under the increasing overlap of ARs and hypoxia anticipated in the future.

A Novel Variable Weight VIKOR Grade Assessment Method for Waterway Navigation Safe Routes Selection - Gao-Feng Yu; Yu-Jin Lin; Xiao-Mei Luo (Journal of Marine Science and Engineering, 2023)
According to the characteristics of waterway navigation safe routes selection, and considering the individual feelings and group benefits of information, as well as no-compensation information between indexes, this paper describes the safe rating of waterway navigation routes, and then puts forward an evaluation model of and method for waterway navigation safe route selection based on variable weight VIKOR. First of all, from the concept and connotation of grade assessment, this paper describes the safe rating of waterway navigation routes, so as to avoid confusing the two essential different problems of safe rating and ranking. Then, the evaluation indexes and membership function of the appropriate grade of the safe rating of waterway navigation route are constructed, and the weights of an evaluation index based on entropy are proposed. Secondly, a variable weight VIKOR evaluation model and a binary semantic evaluation method for the safe grading of waterway navigation safe routes are proposed. Finally, through case study and comparative analysis, the rationality and feasibility of the model and method proposed in this paper are illustrated. This model can better reflect the connotation and characteristics of the appropriate grade assessment of waterway navigation safe routes, and provides new approaches and methods to support the development and management of waterway navigation safe route selection.

Perfluorooctanoic acid and perfluorooctanesulfonic acid induce immunotoxicity through the NF-κB pathway in black-spotted frog (Rana nigromaculata) - Zhiquan Liu; Huikang Lin; Yueyue Zheng; Yixuan Feng; Chaoli Shi; Ruoxin Zhu; Xingyao Shen; Yu Han; Hangjun Zhang; Yuchi Zhong (Chemosphere, 2023)

Development of a low-density SNP genotyping panel by a novel technology mGPS and its application in germplasm identification of abalone - Weihong Lin; Qizhen Xiao; Feng Yu; Zhaofang Han; Junyu Liu; Wenzhu Peng; Zekun Huang; Yuting Lei; Weiguo Li; Weiwei You; Xuan Luo; Caihuan Ke (Aquaculture, 2023)

Investigating the evolution of the Guangdong-Hong Kong-Macao Greater Bay Area (GBA) multi-port system: The multi-faced perspectives - Yu Fu; Qin Lin; Manel Grifoll; Jasmine Siu Lee Lam; Hongxiang Feng (Ocean & Coastal Management, 2023)

Rural-urban disparities in the associations of residential greenness with diabetes and prediabetes among adults in southeastern China - Wanqi Yu; Xiaoqing Li; Wenling Zhong; Shu Dong; Chuanteng Feng; Bin Yu; Xi Lin; Yanrong Yin; Tiehui Chen; Shujuan Yang; Peng Jia (Science of The Total Environment, 2023)

ARSCP: An antimicrobial residue surveillance cloud platform for animal-derived foods - Jun-Jun Yu; Ya-Lin Hu; Cheng-Zheng Liu; Shuai-Bin Wu; Zi-Jian Zheng; Ze-Hua Cui; Li Chen; Tian Wei; Shi-Kai Sun; Jun Ning; Xiang Wen; Qiu-Yue Diao; et al. (Science of The Total Environment, 2023)

Estimation of the soil arsenic concentration using a geographically weighted XGBoost model based on hyperspectral data - Miao Ye; Lin Zhu; Xiaojuan Li; Yinghai Ke; Yong Huang; Beibei Chen; Huilin Yu; Huan Li; Hui Feng (Science of The Total Environment, 2023)

The toxicity of nano polyethylene terephthalate to mice: Intestinal obstruction, growth retardant, gut microbiota dysbiosis and lipid metabolism disorders - Xiaoying Lin; Hongxin Xie; Yanfei Zhang; Xue Tian; Liwei Cui; Nianqiu Shi; Liming Wang; Jiating Zhao; Lihui An; Jing Wang; Bai Li; Yu-Feng Li (Food and Chemical Toxicology, 2023)

Acute exposure to microcystins affects hypothalamic-pituitary axes of male rats - Ting Shi; Lin-Lin Xu; Liang Chen; Jun He; Ye-Ke Wang; Feng Chen; Yang Chen; John P. Giesy; Yu-Ting Wang; Qian-Hui Wu; Wen-Li Xu; Jun Chen; et al. (Environmental Pollution, 2023)

Marangoni-driven biomimetic salt secretion evaporator - Yu Chen; Jin Yang; Lin Zhu; Sizhe Wang; Xiaohua Jia; Yong Li; Dan Shao; Lei Feng; Haojie Song (Desalination, 2023)

A conductive hydrogel based on nature polymer agar with self-healing ability and stretchability for flexible sensors - Zhen Nie; Kelin Peng; Lizhi Lin; Jueying Yang; Zhekun Cheng; Qiang Gan; Yu Chen; Changgen Feng (Chemical Engineering Journal, 2023)

Superior performances via designed multiple embossments within interfaces for flexible pressure sensors - Yujing Zhang; Yuheng Wang; Chenying Wang; Yifan Zhao; Weixuan Jing; Song Wang; Yaxin Zhang; Xiangyue Xu; Fuzheng Zhang; Kaige Yu; Qi Mao; Qijing Lin; et al. (Chemical Engineering Journal, 2023)

Regulating desolvation and homogenized ion flux towards highly reversible dendrite-free zinc anode - Xin Qi; Fuli Xie; Yu-Ting Xu; Hai Xu; Cheng-Lin Sun; Sheng-Han Wang; Jian-Yong Hu; Xiao-Feng Wang (Chemical Engineering Journal, 2023)

Source-specific health risk analysis on atmospheric hazardous volatile organic compounds (HVOCs) in Nanjing, East China - Yu-Chi Lin; Zi-Jin Zhang; Meng-Yao Cao; Mei-Yi Fan; Ahsan Mozaffar; Ming-Yuan Yu; Feng Xie; Yan-Lin Zhang (Atmospheric Environment, 2023)

The onset process of the 2018/2019 Indonesian–Australian summer monsoon: The importance of the air–sea interaction - Yongliang Duan; Hongwei Liu; Ming Feng; Xiangzhou Song; Kuiping Li; Lin Liu; Baochao Liu; Guang Yang; Weidong Yu (Frontiers in Marine Science, 2023)
The Madden–Julian oscillation (MJO) and its associated air–sea interactions during the onset process of the 2018/2019 Indonesian–Australian summer monsoon (IASM) are investigated based on the in situ data from a moored buoy off the coast of northwest Australia, along with ERA5 reanalysis and satellite data. The results verify that the IASM onset in mid-December 2018 was triggered by the first-branch eastward-propagating MJO (FEMJO) originating from the tropical Indian Ocean. However, the strong negative SST anomaly (SSTA) was evident off northwest Australia, which weakens FEMJO over northern Australia and shifts the convective center further northward. The mixed layer heat budget analysis based on the buoy observations reveals that the increased latent heat loss that occurred before the arrival of the FEMJO convection was primarily attributed to the large air–sea temperature difference and strong winds, resulting in the pronounced SSTA.

Using colloidal AFM probe technique and XDLVO theory to predict the transport of nanoplastics in porous media - Li-Juan Feng; Zong-Lin Shi; Jian-Lu Duan; Yi Han; Xiao-Dong Sun; Jing-Ya Ma; Xiao-Yu Liu; Huan-Xin Zhang; Ning Guo; Chao Song; Wan-Song Zong; Xian-Zheng Yuan (Chemosphere, 2023)

Gut as the target tissue of mercury and the extraintestinal effects - Xue Tian; Xiaoying Lin; Jiating Zhao; Liwei Cui; Yuxi Gao; Yong-Liang Yu; Bai Li; Yu-Feng Li (Toxicology, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Seasonal variations of low molecular alkyl amines in PM2.5 in a North China Plain industrial city: Importance of secondary formation and combustion emissions - Xiao-Ying Yang; Fang Cao; Mei-Yi Fan; Yu-Chi Lin; Feng Xie; Yan-Lin Zhang (Science of The Total Environment, 2023)

Hemin protects UVB-induced skin damage through inhibiting keratinocytes apoptosis and reducing neutrophil infiltration - Fang Bai; Chen Fan; Xi Lin; Hao-Yu Wang; Bing Wu; Chun-Lan Feng; Rong Zhou; Yan-Wei Wu; Wei Tang (Journal of Photochemistry and Photobiology B: Biology, 2023)

The largest rock avalanche in China at Iymek, Eastern Pamir, and its spectacular emplacement landscape - An-Wen Shi; Yu-Feng Wang; Qian-Gong Cheng; Qi-Wen Lin; Tian-Hua Li; Bernd Wünnemann (Geomorphology, 2023)

Residential greenness and dyslipidemia risk: Dose-response relations and mediation through BMI and air pollution - Qinjian Wang; Xiaoqing Li; Wenling Zhong; Hongyun Liu; Chuanteng Feng; Chao Song; Bin Yu; Yao Fu; Xi Lin; Yanrong Yin; Tiehui Chen; Jan D. Reinhardt; et al. (Environmental Research, 2023)

Hollow Co-CeO2@PEG nanospheres: Ultrasound enhanced cascade-nanozyme for synergetic anticancer - Miao Wang; Stephen Choi; Qingchen Bai; Kai Yu; Wei Guo; Feng Zhang; Ran Jia; Fengyu Qu; Huiming Lin (Chemical Engineering Journal, 2023)

Dual-site oxygen activation for enhanced photocatalytic aerobic oxidation by S-scheme Ni2P/Bi3O4Br-OVs heterojunction - Weijie Yang; Kailong Sun; Jun Wan; Yang-Ai Ma; Yu Wang; Lin Liu; Bicheng Zhu; Feng Fu (Chemical Engineering Journal, 2023)

Shanghai Autism Early Development: An Integrative Chinese ASD Cohort - Yuan Dai; Yuqi Liu; Lingli Zhang; Tai Ren; Hui Wang; Juehua Yu; Xin Liu; Zilin Chen; Lin Deng; Minyi Tao; Hangyu Tan; Chu-Chung Huang; et al. (Neuroscience Bulletin, 2022)

An association study on the risk, glucocorticoids effectiveness, and prognosis of systemic lupus erythematosus: insight from mitochondrial DNA copy number - Zhen Li; Qi-Qun Zong; Chun-Xia Zhai; Guang-Hui Yu; Wan-Qin Hu; Yu-Hua Wang; Lin-Lin Wang; Zi-Ye Yan; Ting-Yu Zhang; Ying Teng; Shuang Liu; Jing Cai; et al. (Immunologic Research, 2022)

Regulation of enzymatic and non-enzymatic antioxidants in rice seedlings against chromium stress through sodium hydrosulfide and sodium nitroprusside - Yu-Juan Lin; Xing-Hui Feng; Yu-Xi Feng (Environmental Science and Pollution Research, 2022)

Ginsenoside Rb1 inhibits oxidative stress-induced ovarian granulosa cell injury through Akt-FoxO1 interaction - Ping Zhou; Feng Deng; Zi Yang; Canhui Cao; Hongcui Zhao; Fenting Liu; Ke Zhong; Lin Fu; Tianliu Peng; Di Sun; Hui Liu; Rong Li; et al. (Science China Life Sciences, 2022)

The Influence of the Rotary Speed of a Microwave Applicator on Hard-Rock Fracturing Effect - Xia-ting Feng; Shi-ping Li; Cheng-xiang Yang; Feng Lin; Tian-yang Tong; Xiang-xin Su; Jiu-yu Zhang (Rock Mechanics and Rock Engineering, 2022)

Local temperature increases reduce soil microbial residues and carbon stocks - Xiao‐Min Zeng; Jiao Feng; Dai‐Lin Yu; Shu‐Hai Wen; Qianggong Zhang; Qiaoyun Huang; Manuel Delgado‐Baquerizo; Yu‐Rong Liu (Global Change Biology, 2022)
Warming is known to reduce soil carbon (C) stocks by promoting microbial respiration, which is associated with the decomposition of microbial residue carbon (MRC). However, the relative contribution of MRC to soil organic carbon (SOC) across temperature gradients is poorly understood. Here, we investigated the contribution of MRC to SOC along two independent elevation gradients of our model system (i.e., the Tibetan Plateau and Shennongjia Mountain in China). Our results showed that local temperature increases were negatively correlated with MRC and SOC. Further analyses revealed that rising temperature reduced SOC via decreasing MRC, which helps to explain future reductions in SOC under climate warming. Our findings demonstrate that climate warming has the potential to reduce C sequestration by increasing the decomposition of MRC, exacerbating the positive feedback between rising temperature and CO 2 efflux. Our study also considered the influence of multiple environmental factors such as soil pH and moisture, which were more important in controlling SOC than microbial traits such as microbial life‐style strategies and metabolic efficiency. Together, our work suggests an important mechanism underlying long‐term soil C sequestration, which has important implications for the microbial‐mediated C process in the face of global climate change.

Surfactin isoforms isolated from a mushroom derived Bacillus halotolerans DMG-7-2 - Guo-Feng Zhou; Lin Yang; Shu-Hua Zhang; Yi Wang; Yu Yang; Rui Xu; Xue Zhao; Dan Nie; Junjie Shan; Cheng-Bin Cui; Chang-Wei Li (Natural Product Research, 2022)

Bifunctional Ni@NiO catalyst supported on loofah sponge-derived carbon for electrocatalytic air oxidation of biorefractory pollutant in a coupling system - Min Sun; Xiong-Fei Tao; Sheng-Nan Tang; Jun Yu; Yan Wang; Lin-Feng Zhai (Environmental Science and Pollution Research, 2022)

Construction of a core germplasm bank of upland cotton (Gossypium hirsutum L.) based on phenotype, genotype and favorable alleles - Peng Han; Xiaomin Tian; Ying Wang; Cong Huang; Yizan Ma; Xiaofeng Zhou; Yu Yu; Dawei Zhang; Haijiang Xu; Yang Cao; Bo Zhu; Zhenxiu Feng; et al. (Genetic Resources and Crop Evolution, 2022)

Proline-mediated modulation on DNA repair pathway in rice seedlings under chromium stress by integrating gene chip and co-expression network analysis - Yu-Juan Lin; Yu-Xi Feng; Qing Zhang; Xiao-Zhang Yu (Ecotoxicology, 2022)

Altered Retinal Dopamine Levels in a Melatonin-proficient Mouse Model of Form-deprivation Myopia - Kang-Wei Qian; Yun-Yun Li; Xiao-Hua Wu; Xue Gong; Ai-Lin Liu; Wen-Hao Chen; Zhe Yang; Ling-Jie Cui; Yun-Feng Liu; Yuan-Yuan Ma; Chen-Xi Yu; Furong Huang; et al. (Neuroscience Bulletin, 2022)

Natural variation of the BRD2 allele affects plant height and grain size in rice - Jinpeng Huang; Zhiming Chen; Jiajia Lin; Jinwen Chen; Menghao Wei; Liang Liu; Feng Yu; Zesen Zhang; Fangyu Chen; Liangrong Jiang; Jingsheng Zheng; Tiansheng Wang; et al. (Planta, 2022)

A strategy for establishing an efficient somatic embryo regeneration system in Castanea mollissima Blume - Xiao-wei Li; Zhi-lin Sun; Yue-rong Gao; Jing-yi Ge; Yu-zhen Tian; Bing Liu; Shi-kan Sun; Ke-feng Fang; Ling Qin; Qing-qin Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Identification of the Largest SCA36 Pedigree in Asia: with Multimodel Neuroimaging Evaluation for the First Time - Yue Xie; Zhao Chen; Zhe Long; Rui-Ting Chen; Yi-Zheng Jiang; Ming-Jie Liu; Lin-Liu Peng; Hui-Rong Peng; Na Wan; Guangdong Zou; Chun-Rong Wang; Yu-Ting Shi; et al. (The Cerebellum, 2022)

Investigation on long-term progressive deformation of engineering slope based on comprehensive monitoring - Shi-shu Zhang; Song-feng Guo; Sheng-wen Qi; Feng-jiao Tang; Jin-shan Hu; Xiao-ping Zhao; Cong-yan Ran; Xin Wang; Yu Zou; Xiao-lin Huang; Bo-wen Zheng; Ning Liang (Journal of Mountain Science, 2022)

Flow-slide characteristics and failure mechanism of shallow landslides in granite residual soil under heavy rainfall - Hui-lin Bai; Wen-kai Feng; Shuang-quan Li; Long-zhen Ye; Zhong-teng Wu; Rui Hu; Hong-chuan Dai; Yun-peng Hu; Xiao-yu Yi; Peng-cheng Deng (Journal of Mountain Science, 2022)

Massive Heat Shock Protein 70 Genes Expansion and Transcriptional Signatures Uncover Hard Clam Adaptations to Heat and Hypoxia - Zhi Hu; Hao Song; Jie Feng; Cong Zhou; Mei-Jie Yang; Pu Shi; Zheng-Lin Yu; Yong-Ren Li; Yong-Jun Guo; Hai-Zhou Li; Tao Zhang (Frontiers in Marine Science, 2022)
Heat shock protein 70 (HSP70) members participate in a wide range of housekeeping and stress-related activities in eukaryotic cells. In marine ecosystems, bivalves encounter abiotic stresses, including high temperatures and low dissolved oxygen. Here, 133 MmHSP70 genes were identified through combined methods including Blastp, HMM and manual filtration, based on the whole Mercenaria mercenaria genome. The MmHSP70 genes were unevenly distributed, and 41 genes (33.08%) were located on Chr 7. Phylogenetic analyses indicated that the MmHSP70 gene family mainly consisted of two clusters and the Hspa12 subfamily underwent lineage-specific expansion. A high-density collinear gene block was observed between M. mercenaria Chr 7 and Cyclina sinensis Chr 14. Tandem duplication MmHSP70 gene pairs experienced different levels of purifying selection, which could be an important source of sequence and functional constraints. MmHSP70 genes showed tissue-specific and stress-specific expression. Most tandem duplication HSP70 gene pairs had high expression under hypoxia stress. HSP70 B2 tandem duplication gene pairs showed significantly increased expression under heat plus severe hypoxia stress. This study provided a comprehensive understanding of the MmHSP70 gene family in the M. mercenaria and laid a significant foundation for further studies on the functional characteristics of MmHSP70 genes during exposure to heat and hypoxia stress.

Metabolic tuning of a stable microbial community in the surface oligotrophic Indian Ocean revealed by integrated meta-omics - Zhang-Xian Xie; Ke-Qiang Yan; Ling-Fen Kong; Ying-Bao Gai; Tao Jin; Yan-Bin He; Ya-Yu Wang; Feng Chen; Lin Lin; Zhi-Long Lin; Hong-Kai Xu; Zong-Ze Shao; et al. (Marine Life Science & Technology, 2022)
Understanding the mechanisms, structuring microbial communities in oligotrophic ocean surface waters remains a major ecological endeavor. Functional redundancy and metabolic tuning are two mechanisms that have been proposed to shape microbial response to environmental forcing. However, little is known about their roles in the oligotrophic surface ocean due to less integrative characterization of community taxonomy and function. Here, we applied an integrated meta-omics-based approach, from genes to proteins, to investigate the microbial community of the oligotrophic northern Indian Ocean. Insignificant spatial variabilities of both genomic and proteomic compositions indicated a stable microbial community that was dominated by Prochlorococcus , Synechococcus , and SAR11. However, fine tuning of some metabolic functions that are mainly driven by salinity and temperature was observed. Intriguingly, a tuning divergence occurred between metabolic potential and activity in response to different environmental perturbations. Our results indicate that metabolic tuning is an important mechanism for sustaining the stability of microbial communities in oligotrophic oceans. In addition, integrated meta-omics provides a powerful tool to comprehensively understand microbial behavior and function in the ocean.

Dissecting the Neural Circuitry for Pain Modulation and Chronic Pain: Insights from Optogenetics - Fang Guo; Yu Du; Feng-Hui Qu; Shi-Da Lin; Zhong Chen; Shi-Hong Zhang (Neuroscience Bulletin, 2022)
Pain is an unpleasant sensory and emotional experience associated with, or resembling that associated with, actual or potential tissue damage. The processing of pain involves complicated modulation at the levels of the periphery, spinal cord, and brain. The pathogenesis of chronic pain is still not fully understood, which makes the clinical treatment challenging. Optogenetics, which combines optical and genetic technologies, can precisely intervene in the activity of specific groups of neurons and elements of the related circuits. Taking advantage of optogenetics, researchers have achieved a body of new findings that shed light on the cellular and circuit mechanisms of pain transmission, pain modulation, and chronic pain both in the periphery and the central nervous system. In this review, we summarize recent findings in pain research using optogenetic approaches and discuss their significance in understanding the pathogenesis of chronic pain.

Heat Shock Procedure Affects Cell Division-Associated Genes in Gynogenetic Manipulation - Fan Yu; Jian-Lin Li; Wen-Rong Feng; Yong-Kai Tang; Sheng-Yan Su; Pao Xu; Huan Zhong (Marine Biotechnology, 2022)

Production of sesquiterpene patchoulol in mitochondrion-engineered Saccharomyces cerevisiae - Xin-Yi Tao; Yang-Chen Lin; Feng-Qing Wang; Qing-Hai Liu; Yu-Shu Ma; Min Liu; Dong-Zhi Wei (Biotechnology Letters, 2022)

Application of Soil and Water Assessment Tool (SWAT) to evaluate the fates of nitrogenous fertilizer in subtropical mountainous watershed tea farms - Guan-Zhou Lin; Shao-Yiu Hsu; Chia-Chun Ho; Chi-Feng Chen; Jr-Chuan Huang; Tsung-Yu Lee (Environmental Monitoring and Assessment, 2022)

Enhancement of oral bioavailability and anti-hyperuricemic activity of aloe emodin via novel Soluplus®—glycyrrhizic acid mixed micelle system - Feng Shi; Lin Chen; Yaping Wang; Jing Liu; Michael Adu-Frimpong; Hao Ji; Elmurat Toreniyazov; Qilong Wang; Jiangnan Yu; Ximing Xu (Drug Delivery and Translational Research, 2022)

Oxygen Metabolism-induced Stress Response Underlies Heart–brain Interaction Governing Human Consciousness-breaking and Attention - Xiao-Juan Xue; Rui Su; Ze-Feng Li; Xiao-Ou Bu; Peng Dang; Si-Fang Yu; Zhi-Xin Wang; Dong-Mei Chen; Tong-Ao Zeng; Ming Liu; Hai-Lin Ma; De-Long Zhang (Neuroscience Bulletin, 2022)

Research on hoop capacity of composite foundation of discarded rubber tires - Feng-Chi Wang; Jun Li; Zhen-Huan Lin; Pei-Pei Tian; Han-Yu Zhao (European Journal of Environmental and Civil Engineering, 2022)

LncRNA NRON negatively regulates cisplatin-induced cell apoptosis via downregulating miR-31 in esophageal squamous cell carcinomas - Bo Liu; Xu Li; Jinbao Xie; Zhi Feng; Nanlong Lin; Minjie Yu (In Vitro Cellular & Developmental Biology - Animal, 2022)

Regulatory role of miR-129 and miR-384-5p on apoptosis induced by oxygen and glucose deprivation in PC12 cell - Hui-Lin Guan; Yue Guan; Wen-Yuan Li; Jia-Wei Liu; Yu-Jia Zheng; Yan-Zhong Guan; Hong-Feng Liu; Li-Xin Guan; Feng-Guo Zhai (Experimental Brain Research, 2022)

The importance of utilizing nitrate (NO3−) over ammonium (NH4+) as nitrogen source during detoxification of exogenous thiocyanate (SCN-) in Oryza sativa - Yu-Juan Lin; Yu-Xi Feng; Xiao-Zhang Yu (Environmental Science and Pollution Research, 2022)

Nakamurella leprariae sp. nov., isolated from a lichen sample - De-Feng An; Shao-Juan Yang; Long-Qian Jiang; Xin-Yu Wang; Xiao-Yu Huang; Lei Lang; Xue-Mei Chen; Ming-Qun Fan; Gui-Ding Li; Ming-Guo Jiang; Li-Song Wang; Cheng-Lin Jiang; et al. (Archives of Microbiology, 2022)

Kinetics and Size Effects on Adsorption of Cu(II), Cr(III), and Pb(II) Onto Polyethylene, Polypropylene, and Polyethylene Terephthalate Microplastic Particles - Xiaoxin Han; Shiyu Wang; Xue Yu; Rolf D. Vogt; Jianfeng Feng; Lifang Zhai; Weiqi Ma; Lin Zhu; Xueqiang Lu (Frontiers in Marine Science, 2021)
Due to its small size, large specific surface area and hydrophobicity, microplastics, and the adsorbed contaminants may together cause potential negative effects on ecosystems and human beings. In this study, kinetics and size effects on adsorption of Cu(II), Cr(III), and Pb(II) onto PE, PP and PET microplastic particles were explored. Results indicated that the PE and PET microplastics have the higher adsorption capacity for Cu(II), Cr(III), and Pb(II) than that for PP microplastic. The adsorption capacity was affected by microplastic types and metal species. Among the three metals, Pb(II) had the largest adsorption amount on microplastic particles, especially on PET particles. Moreover, the adsorption capacities of microplastics increase with the decrease of particle size. The metal adsorption capacity of <0.9 mm microplastics is greater than that of 0.9–2 mm and 2–5 mm microplastics. The size effect on metal adsorption was largest for PE microplastic. More attention should be paid in case of the coexistence of heavy metals and tiny PE and PET microplastics in the environment.

Measuring Heterogeneity in 18F-Fluorodeoxyglucose Positron Emission Tomography Images for Classifying Metastatic and Benign Bone Lesions in Patients with Cervical Cancer - Feng-Yuan Liu; Gigin Lin; Jing-Ren Tseng; Angel Chao; Huei-Jean Huang; Hung-Hsueh Chou; Yu-Chen Chang; Tzu-Chen Yen; Chyong-Huey Lai (Journal of Medical and Biological Engineering, 2021)
Purpose Heterogeneity assessment can be applied for medical imaging analysis. Here, we evaluated first-order and texture analysis (TA) metrics in 18 F-fluorodeoxyglucose ( 18 F-FDG) positron emission tomography (PET) imaging for classification of metastatic and benign bone lesions in patients with cervical cancer. Methods The data of 18 F-FDG PET studies performed on a specific PET/CT system from 2016 to 2018 in patients with cervical cancer were retrieved. The data of bone lesions extracted from studies over 2016–2017 and 2018 were used as training and validation datasets, respectively. Metastatic bone lesions were identified in each dataset, with an equal number of benign bone lesions selected. Cuboid volume of interest (VOI) consisting of 3 × 3 × 5 reconstructed voxels was applied for first-order metrics, and cubic VOI consisting of smaller voxels with trilinear interpolation of standardized uptake value (SUV) was adopted for TA metrics. First-order metrics included the maximum SUV (SUVmax) of lesions and the mean voxel SUV and its standard deviation (SUVsd), skewness, and kurtosis in VOI. In total, 4464 TA metrics based on 62 texture features were evaluated. Logistic regression was used for classification with area under the receiver operating characteristic curve (AUC) as the performance measure. Results From the training and validation datasets, 98 and 42 metastatic bone lesions were identified, respectively. SUVsd demonstrated higher performance than did SUVmax in both the training (AUC .798 vs .732, P = .001) and validation (AUC .786 vs .684, P < .001) datasets. Top-performing TA metrics demonstrated significantly higher performance in the training dataset, but not in the validation dataset. Conclusion A simple first-order measure of heterogeneity, SUVsd, was found to be superior to SUVmax for the classification of metastatic and benign bone lesions. Multiple hypothesis testing can result in false-positive findings in TA with multiple features and parameters; careful validation is required.

Optimizing the Wheat Seeding Rate for Wide-Space Sowing to Improve Yield and Water and Nitrogen Utilization - Zhixin Wang; Shahbaz Khan; Min Sun; Aixia Ren; Wen Lin; Pengcheng Ding; Hafeez Noor; Shaobo Yu; Yu Feng; Qiang Wang; Zhiqiang Gao (International Journal of Plant Production, 2021)

The Beneficial Role of Exercise on Treating Alzheimer’s Disease by Inhibiting β-Amyloid Peptide - Zi-Xuan Tan; Fang Dong; Lin-Yu Wu; Ya-Shuo Feng; Feng Zhang (Molecular Neurobiology, 2021)

Development and validation of gene-specific KASP markers for YrAS2388R conferring stripe rust resistance in wheat - Yanling Hu; Xuhui Huang; Fang Wang; Yu He; Lihua Feng; Bo Jiang; Ming Hao; Shunzong Ning; Zhongwei Yuan; Jiajie Wu; Lianquan Zhang; Bihua Wu; et al. (Euphytica, 2021)

The Decision Strategies of Adolescents with Different Emotional Stabilities in Unfair Situations - Yajing Si; Lin Jiang; Chanlin Yi; Qi Zhang; Cunbo Li; Jing Yu; Peiyang Li; Qiang Liu; Feng Wan; Fali Li; Dezhong Yao; Peng Xu (Neuroscience Bulletin, 2021)

Chronic Exposure to Hypoxia Inhibits Myelinogenesis and Causes Motor Coordination Deficits in Adult Mice - Lin Chen; Shu-Yu Ren; Rui-Xue Li; Kun Liu; Jing-Fei Chen; Yu-Jian Yang; Yong-Bin Deng; Han-Zhi Wang; Lan Xiao; Feng Mei; Fei Wang (Neuroscience Bulletin, 2021)
Exposure to chronic hypoxia is considered to be a risk factor for deficits in brain function in adults, but the underlying mechanisms remain largely unknown. Since active myelinogenesis persists in the adult central nervous system, here we aimed to investigate the impact of chronic hypoxia on myelination and the related functional consequences in adult mice. Using a transgenic approach to label newly-generated myelin sheaths ( NG2-CreER TM ; Tau-mGFP ), we found that myelinogenesis was highly active in most brain regions, such as the motor cortex and corpus callosum. After exposure to hypoxia (10% oxygen) 12 h per day for 4 weeks, myelinogenesis was largely inhibited in the 4-month old brain and the mice displayed motor coordination deficits revealed by the beam-walking test. To determine the relationship between the inhibited myelination and functional impairment, we induced oligodendroglia-specific deletion of the transcription factor Olig2 by tamoxifen ( NG2-CreER TM ; Tau-mGFP; Olig2 fl/fl ) in adult mice to mimic the decreased myelinogenesis caused by hypoxia. The deletion of Olig2 inhibited myelinogenesis and consequently impaired motor coordination, suggesting that myelinogenesis is required for motor function in adult mice. To understand whether enhancing myelination could protect brain functions against hypoxia, we treated hypoxic mice with the myelination-enhancing drug-clemastine, which resulted in enhanced myelogenesis and improved motor coordination. Taken together, our data indicate that chronic hypoxia inhibits myelinogenesis and causes functional deficits in the brain and that enhancing myelinogenesis protects brain functions against hypoxia-related deficits.

Anti-miR33 therapy improved hepatopancreatic lipid and immune metabolism disorders in grass carp, Ctenopharyngodon idella - Rong-Hua Lu; Meng-Jun Lin; Feng Yang; Shen-zong Jia; Yu-Ru Zhang; Chao-Bin Qin; Xiao-Lin Meng; Guo-Xing Nie (Fish Physiology and Biochemistry, 2021)

Sandaracinobacteroides hominis gen. nov., sp. nov., isolated from human skin - Ping-Hua Qu; Hai-Min Luo; Jun-Hui Feng; Song Li; Cha Chen; Lei Dong; Yu-Zhen Ming; Wen-Jun Li; Ying Lin (Archives of Microbiology, 2021)

Wogonin Accelerates Hematoma Clearance and Improves Neurological Outcome via the PPAR-γ Pathway After Intracerebral Hemorrhage - Jianfeng Zhuang; Yucong Peng; Chi Gu; Huihui Chen; Zheng Lin; Hang Zhou; Xiao Wu; Jianru Li; Xiaobo Yu; Yang Cao; Hanhai Zeng; Xiongjie Fu; et al. (Translational Stroke Research, 2021)

Dicer Deletion in Astrocytes Inhibits Oligodendroglial Differentiation and Myelination - Kun Liu; Bin Yu; Jing-Fei Chen; Rui-Xue Li; Lin Chen; Shu-Yu Ren; Fei Wang; Feng Mei; Lan Xiao (Neuroscience Bulletin, 2021)
Increasing evidence has shown that astrocytes are implicated in regulating oligodendrocyte myelination, but the underlying mechanisms remain largely unknown. To understand whether microRNAs in astrocytes function in regulating oligodendroglial differentiation and myelination in the developing and adult CNS, we generated inducible astrocyte-specific Dicer conditional knockout mice (hGFAP-CreERT; Dicer fl/fl). By using a reporter mouse line (mT/mG), we confirmed that hGFAP-CreERT drives an efficient and astrocyte-specific recombination in the developing CNS, upon tamoxifen treatment from postnatal day 3 (P3) to P7. The Dicer deletion in astrocytes resulted in inhibited oligodendroglial differentiation and myelination in the developing CNS of Dicer cKO mice at P10 and P14, and did not alter the densities of neurons or axons, indicating that Dicer in astrocytes is required for oligodendrocyte myelination. Consequently, the Dicer deletion in astrocytes at P3 resulted in impaired spatial memory and motor coordination at the age of 9 weeks. To understand whether Dicer in astrocytes is also required for remyelination, we induced Dicer deletion in 3-month-old mice and then injected lysolecithin into the corpus callosum to induce demyelination. The Dicer deletion in astrocytes blocked remyelination in the corpus callosum 14 days after induced demyelination. Together, our results indicate that Dicer in astrocytes is required for oligodendroglia myelination in both the developing and adult CNS.

Refractory organic compounds in coal chemical wastewater treatment by catalytic ozonation using Mn-Cu-Ce/Al2O3 - Kang-He Zhao; Yu-Long Ma; Feng Lin; Shao-Ying Ge; Li Zhu (Environmental Science and Pollution Research, 2021)

RSF1 requires CEBP/β and hSNF2H to promote IL-1β-mediated angiogenesis: the clinical and therapeutic relevance of RSF1 overexpression and amplification in myxofibrosarcomas - Chien-Feng Li; Ti-Chen Chan; Cheng-I. Wang; Fu-Min Fang; Po-Chun Lin; Shih-Chen Yu; Hsuan-Ying Huang (Angiogenesis, 2021)

Geographic and subsequent biotic isolations led to a diversity anomaly of section Heterotropa (genus Asarum : Aristolochiaceae) in insular versus continental regions of the Sino‐Japanese Floristic Region - Daiki Takahashi; Shota Sakaguchi; Yu Feng; Yuji Isagi; Ying‐Xiong Qiu; Pan Li; Rui‐Sen Lu; Chang‐Tse Lu; Shih‐Wen Chung; Yang‐Shan Lin; Yun‐Chao Chen; Atsushi J. Nagano; et al. (Journal of Biogeography, 2021)
Aim The Sino‐Japanese Floristic Region has extremely high species diversity with respect to temperate plants; however, the reasons for this diversity are poorly understood because most studies have only considered geographic isolation caused by climatic oscillations. In some plant groups, high floral trait diversity and uneven species diversity between insular systems and the continental area suggest other factors may have important roles too. The primary purpose of this study is to reveal how abiotic and biotic factors have shaped the species diversity anomaly of Heterotropa between the insular systems and the continental area. Location The Sino‐Japanese Floristic Region. Taxon Section Heterotropa (genus Asarum ; Aristolochiaceae). Methods Using ddRAD‐seq and chloroplast genome data, we built a time‐calibrated phylogenetic tree including 79 species. We estimated the patterns of floral traits (flowering time and floral size) evolution using macroevolutionary modelling, and tested the correlation of speciation rate with the trait evolution rates. Finally, we estimated the isolation factors of all taxa pairs and sister‐taxa pairs based on distribution range and floral traits. Results Phylogenetic analysis indicated that Heterotropa was diverged into two clades (continental clade and insular clade) in the Miocene, and the major subclades corresponded to geographic entities. Most rate shifts accelerating floral trait's evolution occurred during the Pleistocene period. Evolution rate of floral traits showed positive correlation with the speciation rate. Large proportion of taxa in the insular clade are distributed allopatrically. Several sister pairs showed floral trait divergence with geographic overlap. Main Conclusions The diversification of Heterotropa appears to have been triggered by geographic and climatic events, and subsequent repeated floral trait evolution with and without geographic isolation. Furthermore, the high species diversity in the insular systems would have been formed by the repeated range fragmentations and contractions. Our study demonstrates the importance of multidimensional studies to understand the diversification process of temperate plants in the Sino‐Japanese Floristic Region.

The Characteristic of Critical Genes in Neuroendocrine System and Their Regulation on Food Habit Transition and Metamorphosis of Veined Rapa Whelk Rapana venosa (Valenciennes, 1846) - Mei-Jie Yang; Jie Feng; Hao Song; Zheng-Lin Yu; Pu Shi; Jian Liang; Zhi Hu; Cong Zhou; Xiao-Lin Wang; Tao Zhang (Frontiers in Marine Science, 2021)
Metamorphosis is a critical developmental event in mollusks, and neuroendocrine system plays an essential role in this process. Rapana venosa is an economically important shellfish in China, but the artificial technology of R. venosa aquaculture is limited by metamorphosis. As a carnivorous gastropod, food habit transition makes the mechanism of R. venosa metamorphosis more complex. To investigate the changes in the neuroendocrine system and to reveal its role in regulating the food habit transition and metamorphosis of R. venosa , we cloned the cDNA sequences encoding 5-hydroxytryptamine receptor ( Rv-5HTR ), nitric oxide synthetase ( Rv-NOS ) and cholecystokinin receptor ( Rv-CCKR ), and investigated their expression by quantitative real-time PCR analysis, and explore the spatio-temporal changes of 5-HT protein expression using Immunohistochemical (IHC) analysis. The expression of the three geens was significantly increased in the early intramembrane veliger stage, which indicates that the three genes are related to the development of digestive system. Additionally, expression of the three genes was decreased after metamorphosis, while Rv-NOS and Rv-CCKR were increasingly expressed in competent larvae, which may help the larvae find suitable environments and promote digestive system development for metamorphosis, and the result of 5-HT IHC analysis also reflects the development of neuroendocrine system. Furthermore, results show that CCK can effect the expression of digestive enzyme, NOS and 5-HT receptor. Finally, based on the present results, we hypothesized that CCK and CCK receptor may be critical regulatory factors of food habit transition and metamorphosis. These results might provide information on the development of neuroendocrine system of R. venosa , and new insight into the regulation of the food habit transition and metamorphosis of gastropods.

Glaciibacter flavus sp. nov., isolated from a lichen sample - De-Feng An; Long-Qian Jiang; Kun Zhang; Gui-Ding Li; Xin-Yu Wang; Ming-Guo Jiang; Lei Lang; Li-Song Wang; Johannes F. Imhoff; Cheng-Lin Jiang; Yi Jiang (Archives of Microbiology, 2021)

In-Situ Seawater Gamma Spectrometry with LaBr3 Detector at a Nuclear Power Plant Outlet - Daowei Dou; Zhi Zeng; Wen Yu; Ming Zeng; Wu Men; Feng Lin; Hao Ma; Jianping Cheng; Junli Li (Journal of Marine Science and Engineering, 2021)
In a nuclear emergency, the application of in situ spectrometers for monitoring environmental radioactivity is significantly important, as information on the type and activity of radionuclides released from the accident can be obtained quickly. However, in emergency environmental radiological monitoring, a balance between energy resolution and detecting efficiency must be considered in selecting an appropriate detector. In this study, in situ gamma spectrometry was conducted with the LaBr3 detector to determine the radioactivity of seawater at the discharging outlet of a coastal nuclear power plant in southeast China. The results show that the LaBr3 scintillator has excellent energy resolution and detection efficiency, making it a promising detector for emergency monitoring.

Detection of Vestibular Schwannoma on Triple-parametric Magnetic Resonance Images Using Convolutional Neural Networks - Tzu-Hsuan Huang; Wei-Kai Lee; Chih-Chun Wu; Cheng-Chia Lee; Chia-Feng Lu; Huai-Che Yang; Chun-Yi Lin; Wen-Yuh Chung; Po-Shan Wang; Yen-Ling Chen; Hsiu-Mei Wu; Wan-You Guo; et al. (Journal of Medical and Biological Engineering, 2021)
Purpose The first step in typical treatment of vestibular schwannoma (VS) is to localize the tumor region, which is time-consuming and subjective because it relies on repeatedly reviewing different parametric magnetic resonance (MR) images. A reliable, automatic VS detection method can streamline the process. Methods A convolutional neural network architecture, namely YOLO-v2 with a residual network as a backbone, was used to detect VS tumors from MR images. To heighten performance, T1-weighted–contrast-enhanced, T2-weighted, and T1-weighted images were combined into triple-channel images for feature learning. The triple-channel images were cropped into three sizes to serve as input images of YOLO-v2. The VS detection effectiveness levels were evaluated for two backbone residual networks that downsampled the inputs by 16 and 32. Results The results demonstrated the VS detection capability of YOLO-v2 with a residual network as a backbone model. The average precision was 0.7953 for a model with 416 × 416-pixel input images and 16 instances of downsampling, when both the thresholds of confidence score and intersection-over-union were set to 0.5. In addition, under an appropriate threshold of confidence score, a high average precision, namely 0.8171, was attained by using a model with 448 × 448-pixel input images and 16 instances of downsampling. Conclusion We demonstrated successful VS tumor detection by using a YOLO-v2 with a residual network as a backbone model on resized triple-parametric MR images. The results indicated the influence of image size, downsampling strategy, and confidence score threshold on VS tumor detection.

A dye combination for the staining of pollen coat and pollen wall - Xin-Lei Jia; Jing-Shi Xue; Fang Zhang; Chi Yao; Shi-Yi Shen; Chang-Xu Sui; Yu-Jia Peng; Qin-Lin Xu; Yi-Feng Feng; Wen-Jing Hu; Ping Xu; Zhong-Nan Yang (Plant Reproduction, 2021)

Quantitative characterization of horizontal well production performance with multiple indicators: a case study on the Weiyuan shale gas field in the Sichuan Basin, China - Rongze Yu; Wei Guo; Lin Ding; Meizhu Wang; Feng Cheng; Xiaowei Zhang; Shangwen Zhou; Leifu Zhang (Frontiers of Earth Science, 2021)

Study on Microwave Heating Order and Electromagnetic Characteristics of Copper and Gold Ores - Feng Lin; Xia-Ting Feng; Gao-Ming Lu; Xiang-Xin Su; Shi-Ping Li; Jiu-yu Zhang (Rock Mechanics and Rock Engineering, 2021)

Experiments on granular flow behavior and deposit characteristics: implications for rock avalanche kinematics - Kun Li; Yu-Feng Wang; Qi-Wen Lin; Qian-Gong Cheng; Yue Wu (Landslides, 2021)

Selective Ferroptosis Inhibitor Liproxstatin-1 Attenuates Neurological Deficits and Neuroinflammation After Subarachnoid Hemorrhage - Yang Cao; Yin Li; Chao He; Feng Yan; Jian-Ru Li; Hang-Zhe Xu; Jian-Feng Zhuang; Hang Zhou; Yu-Cong Peng; Xiong-Jie Fu; Xiao-Yang Lu; Yuan Yao; et al. (Neuroscience Bulletin, 2021)

GTree: an Open-source Tool for Dense Reconstruction of Brain-wide Neuronal Population - Hang Zhou; Shiwei Li; Anan Li; Qing Huang; Feng Xiong; Ning Li; Jiacheng Han; Hongtao Kang; Yijun Chen; Yun Li; Huimin Lin; Yu-Hui Zhang; et al. (Neuroinformatics, 2021)

Increased resting state functional irregularity of T2DM brains with high HbA1c: sign for impaired verbal memory function? - Xin Zhang; Ying Yu; Zhe-Sheng Shi; Ke Xu; Jia-Hao Feng; Ze-Yang Li; Xiang-Nan Zhang; Shu-Ning Shen; Yang Yang; Lin-Feng Yan; Jin Zhang; Qian Sun; et al. (Brain Imaging and Behavior, 2021)

miR-23b Attenuates LPS-Induced Inflammatory Responses in Acute Lung Injury via Inhibition of HDAC2 - Zhi-Feng Luo; Xiang-Hui Jiang; Huan Liu; Li-Yuan He; Xiong Luo; Fu-Chun Chen; Yu-Lin Tan (Biochemical Genetics, 2021)

The molecular mechanism of a novel derivative of BTO-956 induced apoptosis in human myelomonocytic lymphoma cells - Yu-Lin Li; De-Jun Zhou; Zheng-Guo Cui; Lu Sun; Qian-Wen Feng; Shahbaz Ahmad Zakki; Yusuke Hiraku; Cheng-Ai Wu; Hidekuni Inadera (Apoptosis, 2021)

New secondary metabolite with cytotoxicity from spawning soft coral Asterospicularia laurae in Taiwan - Jui-Hsin Su; Chih-I Liu; Mei-Chin Lu; Chi-I Chang; Min-Ying Hsieh; Yu-Chi Lin; Chang-Feng Dai; Ya-Han Zhang; Zheng-Yu Lin; Yun-Sheng Lin (Natural Product Research, 2021)

The Effect of Wave-Induced Current and Coastal Structure on Sediment Transport at the Zengwen River Mouth - Chun-Hung Pao; Jia-Lin Chen; Shih-Feng Su; Yu-Ching Huang; Wen-Hsin Huang; Chien-Hung Kuo (Journal of Marine Science and Engineering, 2021)
The mechanisms that control estuarine sediment transport are complicated due to the interaction between riverine flows, tidal currents, waves, and wave-driven currents. In the past decade, severe seabed erosion and shoreline retreat along the sandy coast of western Taiwan have raised concerns regarding the sustainability of coastal structures. In this study, ADCPs (Acoustic Doppler Current Profiler) and turbidity meters were deployed at the mouth of the Zengwen river to obtain the time series and the spatial distribution of flow velocities and turbidity during the base flow and flood conditions. A nearshore circulation model, SHORECIRC, has been adapted into a hybrid finite-difference/finite-volume, TVD (Total Variation Diminishing)-type scheme and coupled with the wave-spectrum model Simulating Waves Nearshore (SWAN). Conventional finite-difference schemes often produce unphysical oscillations when modeling coastal processes with abrupt bathymetric changes at river mouths. In contrast, the TVD-type finite volume scheme allows for robust treatment of discontinuities through the shock-capturing mechanism. The model reproduces water levels, waves, currents observed at the mouth of the Zengwen River reasonably well. The simulated residual sediment transport patterns demonstrate that the transport process at the river mouth is dominated by the interaction of the bathymetry and wave-induced currents when the riverine discharge was kept in reservoirs. The offshore residual transport causes erosion at the northern part of the river mouth, and the onshore residual transport causes accretion in the ebb tidal shoals around the center of the river mouth. The simulated morphological evolution displays significant changes on shallower deltas. The location with significant sea bed changes is consistent with the spot in which severe erosion occurred in recent years. Further analysis of morphological evolution is also discussed to identify the role of coastal structures, for example, the extension of the newly constructed groins near the river mouth.

Environmental Effects on the Spatiotemporal Variability of Fish Larvae in the Western Guangdong Waters, China - Yuting Feng; Lijun Yao; Hui Zhao; Jing Yu; Zhaojin Lin (Journal of Marine Science and Engineering, 2021)
Spawning grounds occupy an important position in the survival and reproduction of aquatic life, which plays an important role in the replenishment of fishery resources, especially in the China coasts where fishery resources are depleting. This study investigated environmental effects on the spatiotemporal variability of fish larvae in the western Guangdong waters (WGWs), on the basis of generalized additive models (GAMs) and center of gravity (CoG). Satellite data including sea surface salinity (SSS), sea surface temperature (SST), and in situ observations for fish larvae from April to June in 2014–2015 were used. Results showed that 40.3% of the total variation in fish larvae density was explained. SST, SSS, and depth showed positive effects in 23–24 °C and 27–30 °C, 24–32 PSU, and 0–60 m, and showed negative effects in 24–27 °C, 32–34.2 PSU, 60–80 m. Based on the stepwise GAMs, the most important factor was month, with a contribution of 10.6%, followed by longitude, offshore distance, depth, and latitude, with contributions of 7.0%, 7.0%, 6.3%, 4.2%, 3.9%, and 1.3%, respectively. Fish larvae CoG shifted northward by 0.6° N and eastwards by 0.13° E from April to June. The distribution of fish larvae in the WGWs was affected by complex submarine topography in the Qiongzhou Strait, coastal upwelling in the WGWs, and runoff from the Pearl River.

Simulation of the fragmentation and propagation of jointed rock masses in rockslides: DEM modeling and physical experimental verification - Qi-wen Lin; Qian-Gong Cheng; Yu Xie; Feng-shou Zhang; Kun Li; Yu-feng Wang; Yuan-yuan Zhou (Landslides, 2021)

Delayed association of acute particulate matter 2.5 air pollution exposure with loss of complexity in cardiac rhythm dynamics: insight from detrended fluctuation analysis - Tsung-Ying Tsai; Li-Wei Lo; Shin-Huei Liu; Wen-Han Cheng; Yu-Hui Chou; Wei-Lun Lin; Yenn-Jiang Lin; Shih-Lin Chang; Yu-Feng Hu; Fa-Po Chung; Jo-Nan Liao; Tze-Fan Chao; et al. (Environmental Science and Pollution Research, 2021)

Remediation of contaminated soil and groundwater using chemical reduction and solidification/stabilization method: a case study - Shi-Feng Lu; Yu-Lin Wu; Zhan Chen; Tao Li; Chao Shen; Lin-Kang Xuan; Ling Xu (Environmental Science and Pollution Research, 2021)

Roles of FERONIA-like receptor genes in regulating grain size and quality in rice - Long Wang; Dandan Wang; Zhuhong Yang; Shun Jiang; Jianing Qu; Wei He; Zhenming Liu; Junjie Xing; Youchu Ma; Qinlu Lin; Feng Yu (Science China Life Sciences, 2021)

Paracoccus lichenicola sp. nov., Isolated from Lichen - Lei Lang; De-Feng An; Long-Qian Jiang; Gui-Ding Li; Li-Song Wang; Xin-Yu Wang; Qin-Yuan Li; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2021)

Understanding the dynamical-microphysical-electrical processes associated with severe thunderstorms over the Beijing metropolitan region - Xiushu Qie; Shanfeng Yuan; Zhixiong Chen; Dongfang Wang; Dongxia Liu; Mengyu Sun; Zhuling Sun; Abhay Srivastava; Hongbo Zhang; Jingyu Lu; Hui Xiao; Yongheng Bi; et al. (Science China Earth Sciences, 2021)

Improved control of Frankliniella occidentalis on greenhouse pepper through the integration of Orius sauteri and neonicotinoid insecticides - Qing-cai Lin; Hao Chen; Dirk Babendreier; Jin-ping Zhang; Feng Zhang; Xiao-yan Dai; Zuo-wen Sun; Zhao-peng Shi; Xiao-lin Dong; Guang-an Wu; Yi Yu; Li Zheng; et al. (Journal of Pest Science, 2021)

Improving the observation and prediction capabilities for Arctic marine environment: from the perspective of Arctic Shipping - Hui Wang; Qizhen Sun; Lin Zhang; Xi Liang; Qinghua Yang; Na Liu; Chunhua Li; Qingsheng Liu; Bingrui Li; Qian Feng; Xiao Cheng; Yi Yu (Acta Oceanologica Sinica, 2021)

Production of functional human nerve growth factor from the submandibular glands of mice using a CRISPR/Cas9 genome editing system - Yi Gu; Hui Cao; Fei Li; Jianli Yu; Rui Nian; Dongxiao Feng; Jingtao Lin; Haipeng Song; Wenshuai Liu (World Journal of Microbiology and Biotechnology, 2020)

Concurrent increases in post-pacing action potential duration and contractility predict occurrence of ventricular arrhythmia - Chih-Min Liu; Feng-Zhi Lin; Yao-Chang Chen; Yung-Kuo Lin; Yen-Yu Lu; Cheng-I Wu; Satoshi Higa; Shih-Ann Chen; Yi-Jen Chen (Pflügers Archiv - European Journal of Physiology, 2020)

Sand barrier morphological evolution based on time series remote sensing images: a case study of Anhaiao, Pingtan - Heshan Lin; Xingguang Yu; Zhigang Yu; Yikang Gao; Jinyan Xu; Aiping Feng; Zhijun Liu; Degang Jiang; Fan Yu (Acta Oceanologica Sinica, 2020)

WDR5a functions in cadmium-inhibited root meristem growth by regulating nitric oxide accumulation in Arabidopsis - Yu Zhang; Yang-Yang Tian; Lin-Feng Wang; Yun-Hui Li; Ting-Ting Li; Wen-Cheng Liu (Planta, 2020)

Diagnostic value of optic disc retinal nerve fiber layer thickness for diabetic peripheral neuropathy - Xiao-hong Wu; Jing-wen Fang; Yin-qiong Huang; Xue-feng Bai; Yong Zhuang; Xiao-yu Chen; Xia-hong Lin (Journal of Zhejiang University-SCIENCE B, 2020)

Characterization of a Protease Hyper-Productive Mutant of Bacillus pumilus by Comparative Genomic and Transcriptomic Analysis - Yong-Cheng Liu; Lin-Li Han; Tian-Yu Chen; Yan-Bing Lu; Hong Feng (Current Microbiology, 2020)

Impact of prophylactic/preemptive donor lymphocyte infusion and intensified conditioning for relapsed/refractory leukemia: a real-world study - Yu Wang; Qi-Fa Liu; De-Pei Wu; Jing-Bo Wang; Xi Zhang; Heng-Xiang Wang; Feng Gao; Shun-Qing Wang; Zi-Min Sun; Jian Ouyang; Kai-Lin Xu; Su-Jun Gao; et al. (Science China Life Sciences, 2020)

Grape seed proanthocyanidin extract ameliorates hepatic lipid accumulation and inflammation in grass carp (Ctenopharyngodon idella) - Rong-Hua Lu; Chao-Bin Qin; Feng Yang; Wen-Ya Zhang; Yu-Ru Zhang; Guo-Kun Yang; Li-Ping Yang; Xiao-Lin Meng; Xiao Yan; Guo-Xing Nie (Fish Physiology and Biochemistry, 2020)

Strain-softening composite damage model of rock under thermal environment - Wen-lin Feng; Chun-sheng Qiao; Tan Wang; Ming-yuan Yu; Shuang-jian Niu; Zi-qi Jia (Bulletin of Engineering Geology and the Environment, 2020)

Xanthatin mediates G 2 /M cell cycle arrest, autophagy and apoptosis via ROS/XIAP signaling in human colon cancer cells - Ya-di Geng; Lei Zhang; Guo-Yu Wang; Xiao-Jun Feng; Zhao-Lin Chen; Ling Jiang; Ai-Zong Shen (Natural Product Research, 2020)

Tyrosine Hydroxylase Gene Polymorphisms Contribute to Opioid Dependence and Addiction by Affecting Promoter Region Function - Jun-lin Liu; Shao-qing Li; Feng Zhu; Yu-xiang Zhang; Ya-nan Wu; Jing-si Yang; Bao Zhang; Chun-xia Yan (NeuroMolecular Medicine, 2020)

TNFSF13 upregulation confers chemotherapeutic resistance via triggering autophagy initiation in triple-negative breast cancer - Hui-Yu Lin; Chia-Hao Kuei; Hsun-Hua Lee; Che-Hsuan Lin; Yen-Lin Chen; Chi-Long Chen; Yuan-Feng Lin (Journal of Molecular Medicine, 2020)

Electrolytic enrichment method for tritium determination in the Arctic Ocean using liquid scintillation counter - Feng Lin; Tao Yu; Wen Yu; Jialin Ni; Li Lin (Acta Oceanologica Sinica, 2020)

Nitrogen and phosphorus co-starvation inhibits anthocyanin synthesis in the callus of grape berry skin - Hui-Zhen Zheng; Huan Wei; Shui-Huan Guo; Xin Yang; Ming-Xin Feng; Xu-Qiao Jin; Yu-Lin Fang; Zhen-Wen Zhang; Teng-Fei Xu; Jiang-Fei Meng (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Interferon-α2b spray inhalation did not shorten virus shedding time of SARS-CoV-2 in hospitalized patients: a preliminary matched case-control study - Shao-rui Hao; Ren Yan; Shan-yan Zhang; Jiang-shan Lian; Huan Cai; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Two novel pleiotropic loci associated with osteoporosis and abdominal obesity - Lu Liu; Xiao-Lin Yang; Hong Zhang; Zi-Jia Zhang; Xin-Tong Wei; Gui-Juan Feng; Ju Liu; Hui-Ping Peng; Rong Hai; Hui Shen; Qing Tian; Hong-Wen Deng; et al. (Human Genetics, 2020)

Nakamurella albus sp. nov.: A Novel Actinobacterium Isolated from a Lichen Sample - Long-Qian Jiang; De-Feng An; Kun Zhang; Gui-Ding Li; Xin-Yu Wang; Lei Lang; Ming-Guo Jiang; Li-Song Wang; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2020)

Whole brain radiotherapy induces cognitive dysfunction in mice: key role of gut microbiota - Xiao-Xiao Luo; Chun Yang; Gao-Feng Zhan; Shan Li; Dong-Yu Hua; Ai-Lin Luo; Xiang-Lin Yuan (Psychopharmacology, 2020)

Release from below- and aboveground natural enemies contributes to invasion success of a temperate invader - Yuan-Zheng Zhao; Ming-Chao Liu; Yu-Long Feng; Dong Wang; Wei-Wei Feng; Keith Clay; Lekeah A. Durden; Xiu-Rong Lu; Shuo Wang; Xiao-Lin Wei; De-Liang Kong (Plant and Soil, 2020)

A review of progress in coupled ocean-atmosphere model developments for ENSO studies in China - Rong-Hua Zhang; Yongqiang Yu; Zhenya Song; Hong-Li Ren; Youmin Tang; Fangli Qiao; Tongwen Wu; Chuan Gao; Junya Hu; Feng Tian; Yuchao Zhu; Lin Chen; et al. (Journal of Oceanology and Limnology, 2020)

Reversal of Social Recognition Deficit in Adult Mice with MECP2 Duplication via Normalization of MeCP2 in the Medial Prefrontal Cortex - Bin Yu; Bo Yuan; Jian-Kun Dai; Tian-lin Cheng; Sheng-Nan Xia; Ling-Jie He; Yi-Ting Yuan; Yue-Fang Zhang; Hua-Tai Xu; Fu-Qiang Xu; Zhi-Feng Liang; Zi-Long Qiu (Neuroscience Bulletin, 2020)

Comparison of epidemiological and clinical characteristics of COVID-19 patients with and without Wuhan exposure - Jiang-shan Lian; Huan Cai; Shao-rui Hao; Xi Jin; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Shan-yan Zhang; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

The Potential Role of PKA/CREB Signaling Pathway Concerned with Gastrodin Administration on Methamphetamine-Induced Conditioned Place Preference Rats and SH-SY5Y Cell Line - Gen-Meng Yang; Lu Li; Feng-Lin Xue; Chen-Li Ma; Xiao-Feng Zeng; Yong-Na Zhao; Dong-Xian Zhang; Yang Yu; Qian-Wen Yan; Yi-Qing Zhou; Shi-Jun Hong; Li-Hua Li (Neurotoxicity Research, 2020)

Characterization and bioactive potentials of secondary metabolites from Fusarium chlamydosporum - Zhao-Fu Wang; Wei Zhang; Lin Xiao; Yuan-Ming Zhou; Feng-Yu Du (Natural Product Research, 2020)

Hostaflavanol A, a new anti-inflammatory and antioxidant activities flavanol from the flowers of Hosta plantaginea - Li Yang; Yi-min Lin; Zhong-wei He; Ting-fang Zhang; Yu Li; Xiao-tong Xie; Yi-feng Wu; Jun-wei He (Medicinal Chemistry Research, 2020)

No evidence of greater biomass allocation to stolons at moderate resource levels in a floating plant - Chao Si; Wei Xue; Jing Lin; Jian-Feng Zhang; Meng-Meng Hong; Yi-Yue Wang; Liu-Fang Zhang; Fei-Hai Yu (Aquatic Ecology, 2020)

A chemically triggered transition from conflict to cooperation in burying beetles - Bo‐Fei Chen; Mark Liu; Dustin R. Rubenstein; Syuan‐Jyun Sun; Jian‐Nan Liu; Yu‐Heng Lin; Sheng‐Feng Shen (Ecology Letters, 2020)
Although interspecific competition has long been recognised as a major driver of trait divergence and adaptive evolution, relatively little effort has focused on how it influences the evolution of intraspecific cooperation. Here we identify the mechanism by which the perceived pressure of interspecific competition influences the transition from intraspecific conflict to cooperation in a facultative cooperatively breeding species, the Asian burying beetle Nicrophorus nepalensis . We not only found that beetles are more cooperative at carcasses when blowfly maggots have begun to digest the tissue, but that this social cooperation appears to be triggered by a single chemical cue – dimethyl disulfide (DMDS) – emitted from carcasses consumed by blowflies, but not from control carcasses lacking blowflies. Our results provide experimental evidence that interspecific competition promotes the transition from intraspecific conflict to cooperation in N. nepalensis via a surprisingly simple social chemical cue that is a reliable indicator of resource competition between species.

Stilbenoids from aerial parts of Dendrobium plicatile - Dan-Na Chen; Yu-Ye Wang; Wen-Jian Liu; Yue-Juan Chen; Ya-Ping Wu; Jing-Xian Wang; Feng He; Lin Jiang (Natural Product Research, 2020)

Non-motor Symptoms in Parkinson’s Disease Patients with Parkin Mutations: More Depression and Less Executive Dysfunction - Jie Song; Bo Shen; Yu-Jie Yang; Feng-tao Liu; Jue Zhao; Yi-Lin Tang; Chen Chen; Zheng-Tong Ding; Yu An; Jian-Jun Wu; Yi-Min Sun; Jian Wang (Journal of Molecular Neuroscience, 2020)

Aureimonas leprariae sp. nov., Isolated from a Lepraria sp. Lichen - Kun Zhang; Long-Qian Jiang; Li-Song Wang; De-Feng An; Lei Lang; Gui-Ding Li; Xin-Yu Wang; Song-Biao Shi; Qin-Yuan Li; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2020)

Agrobacterium-mediated genetic transformation of Chinese chestnut (Castanea mollissima Blume) - Zhi-lin Sun; Xiao Li; Wan Zhou; Jun-di Yan; Yue-rong Gao; Xiao-wei Li; Jia-chen Sun; Ke-feng Fang; Qing Zhang; Yu Xing; Ling Qin; Qing-qin Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)
Chinese chestnut ( Castanea mollissima ) is an important germplasm resource for the breeding of Castanea species worldwide with vital ecological and economic value. Biotechnology overcomes the limitations of traditional breeding and accelerates germplasm improvement. However, a genetic transformation system for Chinese chestnut has not yet been established. In this study, a stable and efficient Agrobacterium -mediated genetic transformation method for Chinese chestnut is described. Embryogenic calli of C. mollissima cv. ‘Yanshanhongli’ were used as the target material. The sensitivity of embryogenic calli to kanamycin was determined, whereby the proliferation of non-transformed calli was completely inhibited at 180 mg/L. Antibiotic inhibition results for Chinese chestnut embryogenic calli showed that 50 mg/L cefotaxime and 500 μM timentin completely inhibited the growth of Agrobacterium tumefaciens but did not affect the normal growth of Chinese chestnut embryogenic calli. When embryogenic calli were co-cultured for 2 days with Agrobacterium tumefaciens strain AGL1 harboring the PBI121-EGFP plasmid, an embryogenic callus transformation efficiency of 4.55% was obtained, and two transgenic chimera were acquired. This Agrobacterium -mediated transformation system for Chinese chestnut provides a fundamental platform for genetic improvement of core germplasm and for further verification of gene function.

Soil particle-size distribution and aggregate stability of new reconstructed purple soil affected by soil erosion in overland flow - Feng-Lin Zuo; Xiao-Yan Li; Xiao-Fan Yang; Yang Wang; Yu-Jun Ma; Yu-Han Huang; Chao-Fu Wei (Journal of Soils and Sediments, 2020)

Correction to: Soluble Epoxide Hydrolase Inhibition Attenuates Excitotoxicity Involving 14,15-Epoxyeicosatrienoic Acid–Mediated Astrocytic Survival and Plasticity to Preserve Glutamate Homeostasis - Yi-Min Kuo; Pei-Chien Hsu; Chia-Chi Hung; Ya-Yu Hu; Yu-Jie Huang; Yu-Ling Gan; Chun-Hua Lin; Feng-Shiun Shie; Wen-Kuei Chang; Lung-Sen Kao; Mei-Yung Tsou; Yi-Hsuan Lee (Molecular Neurobiology, 2019)

Soluble Epoxide Hydrolase Inhibition Attenuates Excitotoxicity Involving 14,15-Epoxyeicosatrienoic Acid–Mediated Astrocytic Survival and Plasticity to Preserve Glutamate Homeostasis - Yi-Min Kuo; Pei-Chien Hsu; Chia-Chi Hung; Ya-Yu Hu; Yu-Jie Huang; Yu-Ling Gan; Chun-Hua Lin; Feng-Shiun Shie; Wen-Kuei Chang; Lung-Sen Kao; Mei-Yung Tsou; Yi-Hsuan Lee (Molecular Neurobiology, 2019)

Macro-mechanical properties of saturated sandstone of Jushan Mine under post-peak cyclic loading: an experimental study - Wen-lin Feng; Chun-sheng Qiao; Shuang-jian Niu; Ming-yuan Yu; Zi-qi Jia (Arabian Journal of Geosciences, 2019)

Rubellimicrobium rubrum sp. nov., a novel bright reddish bacterium isolated from a lichen sample - Long-Qian Jiang; Kun Zhang; Gui-Ding Li; Xin-Yu Wang; Song-Biao Shi; Qin-Yuan Li; De-Feng An; Lei Lang; Li-Song Wang; Cheng-Lin Jiang; Yi Jiang (Antonie van Leeuwenhoek, 2019)

Expression of AHI1 Rescues Amyloidogenic Pathology in Alzheimer’s Disease Model Cells - Lai-Lei Ting; Hsien-Tsung Lu; Shu-Fen Yen; Thi Huong Ngo; Fang-Yu Tu; I-Shih Tsai; Yi-Hua Tsai; Fu-Yen Chang; Xiao-Jiang Li; Shihua Li; Ching-Kuo Lee; Shu-Huei Kao; et al. (Molecular Neurobiology, 2019)

First report of wisteria vein mosaic virus in Chinese wisteria in Jiangxi Province in China - Zhao-Lin Ji; Peng-Xiang Zhu; Yu-Hang Ji; Fei Xu; Feng Zhu (Journal of Plant Pathology, 2019)

Hydro-mechanical response with respect to the air ventilation for water filtration in homogeneous soil - Wei-Lin Lee; Yih-Chin Tai; Chjeng-Lun Shieh; Kuniaki Miyamoto; Yu-Feng Lin (Journal of Mountain Science, 2019)

A new indole-type alkaloid from the roots of Clematis florida var. plena - Kai-Hui Sun; Xin-Hua Ma; Xian-Ming Zeng; Zhong-Yue Lin; Yu-Mei Cai; Hai-Tao Zhang; Xiao-Yan Lin; Shi-Biao Feng; Tian-Hua Zhong; Yong-Hong Zhang (Natural Product Research, 2019)

Two-factor ANOVA of SSH and RNA-seq analysis reveal development-associated Pi-starvation genes in oilseed rape - Zhong-Wei Zhang; Ling-Yang Feng; Jian-Hui Wang; Yu-Fan Fu; Xin Cai; Chang-Quan Wang; Jun-Bo Du; Ming Yuan; Yang-Er Chen; Pei-Zhou Xu; Ting Lan; Guang-Deng Chen; et al. (Planta, 2019)

MicroRNA-365 Knockdown Prevents Ischemic Neuronal Injury by Activating Oxidation Resistance 1-Mediated Antioxidant Signals - Jia-Lin Mo; Zhi-Guang Pan; Xiao Chen; Yu Lei; Ling-Ling Lv; Cheng Qian; Feng-Yan Sun (Neuroscience Bulletin, 2019)

Paraventricular Thalamus as A Major Thalamic Structure for Wake Control - Yu-Feng Shao; Jian-Sheng Lin; Yi-Ping Hou (Neuroscience Bulletin, 2019)

Seasonal Dynamics of Gastrointestinal Nematode Infections of Goats and Emergence of Ivermectin Resistance in Haemonchus contortus in Hubei Province, China - Wei Yuan; Ke Lu; Hao Li; Jinming Liu; Chuanchuan He; Jintao Feng; Xin Zhang; Yudan Mao; Yang Hong; Yu Zhou; Jun Lu; Yamei Jin; et al. (Acta Parasitologica, 2019)

Adult sacrococcygeal teratoma: a retrospective study over eight years at a single institution - Xiang-ming Xu; Feng Zhao; Xiao-fei Cheng; Wei-xiang Zhong; Jing-peng Liu; Wei-qin Jiang; Xiao-kai Yu; Jian-jiang Lin (Journal of Zhejiang University-SCIENCE B, 2019)

Different intensity of autophagy regulate interleukin-33 to control the uncontrolled inflammation of acute lung injury - Ming Lei; Chuan-jiang Wang; Feng Yu; Ke Xie; Shi-hui Lin; Fang Xu (Inflammation Research, 2019)

Portable vertical pendulum tiltmeter development and application test - Jie-ning Xia; Qiang Lin; Li-Xia Geng; Zhen Li; Song Luo; Nong-Fa Li; Jian-Feng Yu; Jun Liu (Acta Geodaetica et Geophysica, 2019)

The roles of morphological traits, resource variation and resource partitioning associated with the dietary niche expansion in the fish‐eating bat Myotis pilosus - Yang Chang; Shengjing Song; Aoqiang Li; Yu Zhang; Zhongle Li; Yanhong Xiao; Tinglei Jiang; Jiang Feng; Aiqing Lin (Molecular Ecology, 2019)
Niche expansion and shifts are involved in the response and adaptation to environmental changes. However, it is unclear how niche breadth evolves and changes toward higher‐quality resources. Myotis pilosus is both an insectivore and a piscivore. We examined the dietary composition and seasonality in M . pilosus and the closely related Myotis fimbriatus using next‐generation DNA sequencing. We tested whether resource variation or resource partitioning help explain the dietary expansion from insects to fish in M . pilosus . While diet composition and diversity varied significantly between summer and autumn, the proportion of fish‐eating individuals did not significantly change between seasons in M . pilosus . Dietary overlap between M . pilosus and M . fimbriatus during the same seasons was much higher than within individual species across seasons. We recorded a larger body size, hind foot length, and body mass in M . pilosus than in M . fimbriatus and other insectivorous trawling bats from China. Similar morphological differences were found between worldwide fishing bats and nonfishing trawling bats. Our results suggest that variation in insect availability or interspecific competition may not play important roles in the dietary expansion from insects to fish in M . pilosus . Myotis pilosus has morphological advantages that may help it use fish as a diet component. The morphological advantage promoting dietary niche evolution toward higher quality resources may be more important than variation in the original resource and the effects of interspecific competition.

Characterization of the Cd(II) and nitrate removal by bacterium Acinetobacter sp. SZ28 under different electron donor conditions - Jun Feng Su; Chun Yu Gao; Ting Lin Huang; Xue Chen Bai; Dong Hui Liang; Lei He (Environmental Science and Pollution Research, 2019)

Intestinal Methylation and Demethylation of Mercury - Hong Li; Xiaoying Lin; Jiating Zhao; Liwei Cui; Liming Wang; Yuxi Gao; Bai Li; Chunying Chen; Yu-Feng Li (Bulletin of Environmental Contamination and Toxicology, 2019)

Magnesium sulfate inhibits binding of lipopolysaccharide to THP-1 cells by reducing expression of cluster of differentiation 14 - Ya-Ying Chang; Tzu-Yu Lin; Ming-Chang Kao; Tsung-Ying Chen; Ching-Feng Cheng; Chih-Shung Wong; Chun-Jen Huang (Inflammopharmacology, 2019)

Intraguild predation between Harmonia axyridis and Aphidius gifuensis: effects of starvation period, plant dimension and extraguild prey density - Xing-Lin Yu; Yi Feng; Wen-Yan Fu; Yuan-Xing Sun; Tong-Xian Liu (BioControl, 2019)

Atorvastatin ameliorates the contractile dysfunction of the aorta induced by organ culture - Feng Zhou; Fang Rao; You-Qing Deng; Hui Yang; Su-Juan Kuang; Fei-Long Wu; Shu-Lin Wu; Yu-Mei Xue; Xiao-Mu Wu; Chun-Yu Deng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Study on the bio-function of lipA gene in Aspergillus flavus - Wenzhao Bai; Tiejun Feng; Faxiu Lan; Guanglan Lin; Yu Li; Opemipo Esther Fasoyin; Yaju Liu; Kunzhi Jia (Genes & Genomics, 2019)

EGb761 improves the cognitive function of elderly db/db−/− diabetic mice by regulating the beclin-1 and NF-κB signaling pathways - Zhu-Fei Guan; Xiao-Ming Zhang; Ying-Hong Tao; Yu Zhang; Yan-Yan Huang; Gang Chen; Wei-Jun Tang; Gang Ji; Qi-Lin Guo; Ming Liu; Qian Zhang; Na-Na Wang; et al. (Metabolic Brain Disease, 2018)

Two new alkylated furan derivatives with antifungal and antibacterial activities from the plant endophytic fungus Emericella sp. XL029 - Xia Wu; Xue-Jiao Pang; Lu-Lin Xu; Ting Zhao; Xin-Yu Long; Qiong-Yin Zhang; Hai-Li Qin; Deng-Feng Yang; Xiao-Long Yang (Natural Product Research, 2018)

Rapid classification of virgin and recycled EPS containers by Fourier transform infrared spectroscopy and chemometrics - Xue-Chao Song; Qin-Bao Lin; Yi-Cai Zhang; Zhong Li; Yu Zeng; Zhi-Feng Chen (Food Additives & Contaminants: Part A, 2018)

Assessment of anti-diabetic activity of peanut shell polyphenol extracts - Xiao-meng Sun; Hai-qing Ye; Jing-bo Liu; Lei Wu; Ding-bo Lin; Ya-li Yu; Feng Gao (Journal of Zhejiang University-SCIENCE B, 2018)

Identification and Field Evaluation of the Sex Pheromone of Orthaga achatina (Lepidoptera: Pyralidae) - Qi Yan; Hai-Dong Li; Yan Chen; Zhan-Feng Ye; Xi-Yu You; Jun Zhou; Lan-Fang Mu; Shi-Jing Liu; Xiang-Bo Kong; Sajjad Ali Khuhro; Shuang-Lin Dong (Journal of Chemical Ecology, 2018)

Effects of dietary supplementation with algal astaxanthin on growth, pigmentation, and antioxidant capacity of the blood parrot ( Cichlasoma citrinellum × Cichlasoma synspilum ) - Feng Li; Shuiying Huang; Xiaoxia Lu; Jun Wang; Mingwei Lin; Yu An; Shaoting Wu; Minggang Cai (Journal of Oceanology and Limnology, 2018)

Integrating CNVs into meta-QTL identified GBP4 as positional candidate for adult cattle stature - Xiu-Kai Cao; Yong-Zhen Huang; Yi-Lei Ma; Jie Cheng; Zhen-Xian Qu; Yun Ma; Yue-Yu Bai; Feng Tian; Feng-Peng Lin; Yu-Lin Ma; Hong Chen (Functional & Integrative Genomics, 2018)

Assessing the efficacy of a live vaccine against avian encephalomyelitis virus - Wencheng Lin; Piaopiao Lu; Aijun Li; Yu Wu; Hongxin Li; Feng Chen; Jingyun Ma; Qingmei Xie (Archives of Virology, 2018)

Temporal and Spatial Variations of Microbial Carbon Utilization in Water Bodies from the Dajiuhu Peatland, Central China - Rui-Cheng Wang; Hong-Mei Wang; Xing Xiang; Yu Gao; Qing-Wei Song; Lin-Feng Gong (Journal of Earth Science, 2018)

Extension of C. elegans lifespan using the ·NO-delivery dinitrosyl iron complexes - Hsiao-Wen Huang; Yen-Hung Lin; Min-Hsuan Lin; Ya-Rong Huang; Chih-Hung Chou; Hsiao-Chin Hong; Mei-Ren Wang; Yu-Ting Tseng; Po-Chun Liao; Min-Chuan Chung; Yu-Jie Ma; Shou-Cheng Wu; et al. (JBIC Journal of Biological Inorganic Chemistry, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

Microsatellite records for volume 10, issue 1 - Ai-Qing Yu; Chengxin Fu; Chongbo He; Fei Liu; Guo-Hua Ding; Hongman Hou; Jian Zhao; Jianmin Yang; Jiansheng Wang; Kun-ci Chen; Lan-lan Zhang; Pan Li; et al. (Conservation Genetics Resources, 2018)

Characterization of the complete chloroplast genome of the Chinese cherry Prunus pseudocerasus (Rosaceae) - Ying Feng; Tao Liu; Xiao-Yu Wang; Bin-Bin Li; Cheng-Lin Liang; Yu-Liang Cai (Conservation Genetics Resources, 2018)

Genetic analysis of three porcine bocaparvoviruses and identification of a natural recombinant breakpoint in NS1 - Yu Zhou; Jia Xu; Shi-Kang Zhu; Qing-Feng Meng; Zhi-Xiong Lin; Ru Chen; Ai-Dong Qian (Archives of Virology, 2018)

Sumoylation of SUVR2 contributes to its role in transcriptional gene silencing - Yu-Xi Luo; Yong-Feng Han; Qiu-Yuan Zhao; Jin-Lu Du; Kun Dou; Lin Li; She Chen; Xin-Jian He (Science China Life Sciences, 2018)

Nature and origin of Triassic igneous activity in the Western Qinling Orogen: the Wenquan composite pluton example - Kun-Feng Qiu; Hao-Cheng Yu; Zong-Yang Gou; Zhi-Lu Liang; Jia-Lin Zhang; Rui Zhu (International Geology Review, 2018)

Dcf1 Triggers Dendritic Spine Formation and Facilitates Memory Acquisition - Qiang Liu; Ruili Feng; Yu Chen; Guanghong Luo; Huang Yan; Ling Chen; Rongfei Lin; Yuqiang Ding; Tieqiao Wen (Molecular Neurobiology, 2018)

Ice Squeezing Induced Multicolor Fluorescence Emissions from Polyacrylamide Cryogels - Chun Yang; Yan Zhang; Wei-Qin Cao; Ya-Nan Yan; Jian Wang; Xiao-Feng Ji; Tao-Lin Zhong; Yu Wang (Journal of Fluorescence, 2018)

Synthesis and biological evaluation of disulfides bearing 1,2,4-triazole moiety as antiproliferative agents - Xue-Feng Wang; Shuai Zhang; Bao-Lin Li; Ji-Jun Zhao; Yu-Ming Liu; Rui-Lian Zhang; Bo Li; Bao-Quan Chen (Medicinal Chemistry Research, 2017)

A new cycloartane triterpenoid glycoside from Souliea vaginata - Hai-Feng Wu; Xin Liu; Yin-Di Zhu; Jing Zhou; Ying-Ying Gong; Guo-Xu Ma; Xu-Dong Xu; Yi-Lin Liu; Zheng-Hong Luo; Di-Zhao Chen; Qiong-Yu Zou; Zi-Jian Zhao (Natural Product Research, 2017)

Far infrared promotes wound healing through activation of Notch1 signaling - Yung-Ho Hsu; Yuan-Feng Lin; Cheng-Hsien Chen; Yu-Jhe Chiu; Hui-Wen Chiu (Journal of Molecular Medicine, 2017)

17β-Estradiol and/or estrogen receptor alpha blocks isoproterenol-induced calcium accumulation and hypertrophy via GSK3β/PP2A/NFAT3/ANP pathway - Peiying Pai; Bharath Kumar Velmurugan; Chia-Hua Kuo; Chung-Yi Yen; Tsung-Jung Ho; Yueh-Min Lin; Yu-Feng Chen; Chao-Hung Lai; Cecilia Hsuan Day; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2017)

Magnesium Ions Promote the Biological Behaviour of Rat Calvarial Osteoblasts by Activating the PI3K/Akt Signalling Pathway - Jian Wang; Xiang-Yu Ma; Ya-Fei Feng; Zhen-Sheng Ma; Tian-Cheng Ma; Yang Zhang; Xiang Li; Lin Wang; Wei Lei (Biological Trace Element Research, 2017)

Down-Regulation of Neuregulin1/ErbB4 Signaling in the Hippocampus Is Critical for Learning and Memory - Jia Tian; Fei Geng; Feng Gao; Yi-Hua Chen; Ji-Hong Liu; Jian-Lin Wu; Yu-Jie Lan; Yuan-Ning Zeng; Xiao-Wen Li; Jian-Ming Yang; Tian-Ming Gao (Molecular Neurobiology, 2017)

Metformin Improves Functional Recovery After Spinal Cord Injury via Autophagy Flux Stimulation - Di Zhang; Jun Xuan; Bin-bin Zheng; Yu-long Zhou; Yan Lin; Yao-sen Wu; Yi-fei Zhou; Yi-xing Huang; Quan Wang; Li-yan Shen; Cong Mao; Yan Wu; et al. (Molecular Neurobiology, 2017)

Two new phenylpropanoids from Swertia atroviolacea and their anti-5 α -reductase activity - Hai-Yan Wu; Xue-Qing Kan; Yu Sheng; Lin-Yun Mou; Qing-Song Yang; Qiu-Feng Hu; Gan-Peng Li (Natural Product Research, 2017)

Punicalagin protects bovine endometrial epithelial cells against lipopolysaccharide-induced inflammatory injury - An Lyu; Jia-jia Chen; Hui-chuan Wang; Xiao-hong Yu; Zhi-cong Zhang; Ping Gong; Lin-shu Jiang; Feng-hua Liu (Journal of Zhejiang University-SCIENCE B, 2017)

HCV core inhibits hepatocellular carcinoma cell replicative senescence through downregulating microRNA-138 expression - Tzu-Yue Shiu; Yu-Lueng Shih; An-Chieh Feng; Hsuan-Hwai Lin; Shih-Ming Huang; Tien-Yu Huang; Chung-Bao Hsieh; Wei-Kuo Chang; Tsai-Yuan Hsieh (Journal of Molecular Medicine, 2017)

Pharmacological Inhibition of PERK Attenuates Early Brain Injury After Subarachnoid Hemorrhage in Rats Through the Activation of Akt - Feng Yan; Shenglong Cao; Jianru Li; Brandon Dixon; Xiaobo Yu; Jingyin Chen; Chi Gu; Wang Lin; Gao Chen (Molecular Neurobiology, 2017)

Integrative multi-omics analysis revealed SNP-lncRNA-mRNA (SLM) networks in human peripheral blood mononuclear cells - Wei Xia; Xiao-Wei Zhu; Xin-Bo Mo; Long-Fei Wu; Jian Wu; Yu-Fan Guo; Ke-Qin Zeng; Ming-Jun Wang; Xiang Lin; Ying-Hua Qiu; Lan Wang; Pei He; et al. (Human Genetics, 2017)

miR-137 and miR-491 Negatively Regulate Dopamine Transporter Expression and Function in Neural Cells - Xiaojian Jia; Feng Wang; Ying Han; Xuewen Geng; Minghua Li; Yu Shi; Lin Lu; Yun Chen (Neuroscience Bulletin, 2016)

Fungal spondylodiscitis in a patient recovered from H7N9 virus infection: a case study and a literature review of the differences between Candida and Aspergillus spondylodiscitis - Lie-dao Yu; Zhi-yun Feng; Xuan-wei Wang; Zhi-heng Ling; Xiang-jin Lin (Journal of Zhejiang University-SCIENCE B, 2016)

Characterization of the spatial variability of soil available zinc at various sampling densities using grouped soil type information - Xiao-Dong Song; Gan-Lin Zhang; Feng Liu; De-Cheng Li; Yu-Guo Zhao (Environmental Monitoring and Assessment, 2016)

A WD40 protein, AtGHS40, negatively modulates abscisic acid degrading and signaling genes during seedling growth under high glucose conditions - Yu-Chun Hsiao; Yi-Feng Hsu; Yun-Chu Chen; Yi-Lin Chang; Co-Shine Wang (Journal of Plant Research, 2016)

PreSurgMapp: a MATLAB Toolbox for Presurgical Mapping of Eloquent Functional Areas Based on Task-Related and Resting-State Functional MRI - Huiyuan Huang; Zhongxiang Ding; Dewang Mao; Jianhua Yuan; Fangmei Zhu; Shuda Chen; Yan Xu; Lin Lou; Xiaoyan Feng; Le Qi; Wusi Qiu; Han Zhang; et al. (Neuroinformatics, 2016)

Permeability of novel 4′-N-substituted (aminomethyl) benzoate-7-substituted nicotinic acid ester derivatives of scutellarein in Caco-2 cells and in an in vitro model of the blood-brain barrier - Yu Ou; Min Luo; Yong-Xi Dong; Hang Su; Xiao-Zhong Fu; Yu-Feng Cha; Shun Zhang; Yong-Long Zhao; Yong-Jun Li; Yong-Lin Wang (Medicinal Chemistry Research, 2016)

Combined effects of age and polymorphisms in Notch3 in the pathogenesis of cerebral infarction disease - Chun-Yu Zhu; Yue Wang; Qing-Xuan Zeng; Yu Qian; Huan Li; Zi-Xia Yang; Ya-Mei Yang; Qiong Zhang; Fei-Feng Li; Shu-Lin Liu (Metabolic Brain Disease, 2016)

Controlling effects of surface crusts on water infiltration in an arid desert area of Northwest China - Jin-Ling Yang; Gan-Lin Zhang; Fei Yang; Ren-Min Yang; Chen Yi; De-Cheng Li; Yu-Guo Zhao; Feng Liu (Journal of Soils and Sediments, 2016)

Assessment of the seasonal variation of simulated Wyrtki jet over the tropical Indian Ocean in CMIP5 models - Lin Liu; Baochao Liu; Guoqing Han; Lin Feng; Xinfang Li; Weidong Yu (Arabian Journal of Geosciences, 2016)

Methylation and Esterification of Magnolol for Ameliorating Cutaneous Targeting and Therapeutic Index by Topical Application - Chwan-Fwu Lin; Chi-Feng Hung; Ibrahim A. Aljuffali; Yu-Ling Huang; Wei-Chun Liao; Jia-You Fang (Pharmaceutical Research, 2016)

Trabala Vishnou Gigantina Yang (Lepidoptera: Lasiocampidae) Larval Fitness on six Sympatric Plant Species in Sea-Buckthorn Forest - Dong-Mei Wen; Lin-Feng Yu; Yong-Hua Liu; Xiong-Fei Yan; Peng-Fei Lu; You-Qing Luo (Journal of Insect Behavior, 2016)

Low temperature destruction of PCDD/Fs over V2O5-CeO2/TiO2 catalyst with ozone - Ming-feng Yu; Xiao-qing Lin; Mi Yan; Xiao-dong Li; Tong Chen; Jian-hua Yan (Environmental Science and Pollution Research, 2016)

Catalytic destruction of PCDD/Fs over vanadium oxide-based catalysts - Ming-feng Yu; Xiao-qing Lin; Xiao-dong Li; Mi Yan; Bayu Prabowo; Wen-wei Li; Tong Chen; Jian-hua Yan (Environmental Science and Pollution Research, 2016)

A new tigliane-type diterpene from Euphorbia dracunculoides Lam - Lin-Feng Dai; Qian Liang; Tie Liu; Ming-Yu He; Ping Zhao; Wen-Hui Xu (Natural Product Research, 2016)

Anisotropic Drained Deformation Behavior and Shear Strength of Natural Soft Marine Clay - Yu-Ke Wang; Lin Guo; Yu-Feng Gao; Yue Qiu; Xiu-Qing Hu; Ying Zhang (Marine Georesources & Geotechnology, 2016)

Adult reproductive diapause in Drosophila suzukii females - Yifan Zhai; Qingcai Lin; Jinping Zhang; Feng Zhang; Li Zheng; Yi Yu (Journal of Pest Science, 2016)

Paraventricular Nucleus Infusion of Epigallocatechin-3-O-Gallate Improves Renovascular Hypertension - Qiu-Yue Yi; Jie Qi; Xiao-Jing Yu; Hong-Bao Li; Yan Zhang; Qing Su; Tao Shi; Dong-Mei Zhang; Jing Guo; Zhi-Peng Feng; Mo-Lin Wang; Guo-Qing Zhu; et al. (Cardiovascular Toxicology, 2016)

Magnolol pretreatment attenuates heat stress-induced IEC-6 cell injury - Chen Mei; Sha-sha He; Peng Yin; Lei Xu; Ya-ran Shi; Xiao-hong Yu; An Lyu; Feng-hua Liu; Lin-shu Jiang (Journal of Zhejiang University-SCIENCE B, 2016)

Evaluating Induced Fractures Between a Large Artificial Lake and an Aquifer-Coal Seam System: A Case Study in Tangshan Coal Mine, China - Donglin Dong; Gang Lin; Yu-Feng F. Lin; Mingdong Zhao; Kai Li (Mine Water and the Environment, 2016)

Pollen and seed flow under different predominant winds in wind-pollinated and wind-dispersed species Engelhardia roxburghiana - Zheng-Feng Wang; Ju-Yu Lian; Wan-Hui Ye; Hong-Lin Cao; Qian-Mei Zhang; Zhang-Ming Wang (Tree Genetics & Genomes, 2016)

Mechanism Underlying the Analgesic Effect Exerted by Endomorphin-1 in the rat Ventrolateral Periaqueductal Gray - Tao Chen; Jing Li; Ban Feng; Rui Hui; Yu-Lin Dong; Fu-Quan Huo; Ting Zhang; Jun-Bin Yin; Jian-Qing Du; Yun-Qing Li (Molecular Neurobiology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Molecular Cloning and Characterization of Two Genes Encoding Tryptophan Decarboxylase from Aegilops variabilis with Resistance to the Cereal Cyst Nematode (Heterodera avenae) and Root-Knot Nematode (Meloidogyne naasi) - Lin Li; Minghui Zheng; Hai Long; Guangbing Deng; Atsushi Ishihara; Feng Liu; Junjun Liang; Zhifen Pan; Maoqun Yu (Plant Molecular Biology Reporter, 2016)

A new method for estimating effect size distribution and heritability from genome-wide association summary results - Lei Zhang; Yue-Ping Shen; Wen-Zhu Hu; Shu Ran; Yong Lin; Shu-Feng Lei; Yong-Hong Zhang; Christopher J. Papasian; Nengjun Yi; Yu-Fang Pei (Human Genetics, 2016)

Tumor MICA status predicts the efficacy of immunotherapy with cytokine-induced killer cells for patients with gastric cancer - Yu Chen; Wan-song Lin; Wei-feng Zhu; Jing Lin; Zhi-feng Zhou; Chuan-zhong Huang; Gang Chen; Yi Shi; Zeng-qing Guo; Yun-bin Ye (Immunologic Research, 2016)

Physiological and proteomic analysis in two wild tomato lines under waterlogging and high temperature stress - Hsin-Hung Lin; Kuan-Hung Lin; Jia-Yu Syu; Shun-Yuan Tang; Hsiao-Feng Lo (Journal of Plant Biochemistry and Biotechnology, 2016)

Identification of two novel critical mutations in PCNT gene resulting in microcephalic osteodysplastic primordial dwarfism type II associated with multiple intracranial aneurysms - Fei-Feng Li; Xu-Dong Wang; Min-Wei Zhu; Zhi-Hong Lou; Qiong Zhang; Chun-Yu Zhu; Hong-Lin Feng; Zhi-Guo Lin; Shu-Lin Liu (Metabolic Brain Disease, 2015)

CTRP3 attenuates post-infarct cardiac fibrosis by targeting Smad3 activation and inhibiting myofibroblast differentiation - Dan Wu; Hong Lei; Jin-Yu Wang; Cheng-Lin Zhang; Han Feng; Feng-Ying Fu; Li Li; Li-Ling Wu (Journal of Molecular Medicine, 2015)

New Perspectives on Dietary-derived Treatments and Food Safety—Antinomy in a New Era - Si-Yuan Pan; Si-Hua Gao; Rui-Chao Lin; Shu-Feng Zhou; Hong-Guan Dong; Min-Ke Tang; Zhi-Ling Yu; Kam-Ming Ko (Critical Reviews in Food Science and Nutrition, 2015)

Retraction Note to: Lactoferrin promote primary rat osteoblast proliferation and differentiation via up-regulation of insulin-like growth factor-1 expression - Jian-ming Hou; Man Wu; Qing-ming Lin; Fan Lin; Ying Xue; Xu-hua Lan; En-yu Chen; Mei-li Wang; Hai-yan Yang; Feng-xiong Wang (Molecular Biology Reports, 2015)

The diversity of coral associated bacteria and the environmental factors affect their community variation - Yan-Ying Zhang; Juan Ling; Qing-Song Yang; You-Shao Wang; Cui-Ci Sun; Hong-Yan Sun; Jing-Bin Feng; Yu-Feng Jiang; Yuan-Zhou Zhang; Mei-Lin Wu; Jun-De Dong (Ecotoxicology, 2015)

Associations between TRPV4 genotypes and body mass index in Taiwanese subjects - De-Min Duan; Semon Wu; Lung-An Hsu; Ming-Sheng Teng; Jeng-Feng Lin; Yu-Chen Sun; Ching-Feng Cheng; Yu-Lin Ko (Molecular Genetics and Genomics, 2015)

Metabolites of Scutellariae Radix Inhibit Injury of Endothelial Cells in Hypoxia Device - Chia-Lun Chao; Shiuan-Pey Lin; Yu-Chi Hou; Pei-Dawn Lee Chao; Nen-Chung Chang; Yu-Ching Huang; Feng-Ming Ho (Journal of Medical and Biological Engineering, 2015)

Photodegradation of Alachlor Using BiVO4 Photocatalyst Under Visible Light Irradiation - Yi-Kuo Chang; Yu-Shen Wu; Chung-Shin Lu; Pei-Feng Lin; Tsung-Yen Wu (Water, Air, & Soil Pollution, 2015)

Within-litter variation in birth weight: impact of nutritional status in the sow - Tao-lin Yuan; Yu-hua Zhu; Meng Shi; Tian-tian Li; Na Li; Guo-yao Wu; Fuller W. Bazer; Jian-jun Zang; Feng-lai Wang; Jun-jun Wang (Journal of Zhejiang University-SCIENCE B, 2015)

Nucleotide composition bias and codon usage trends of gene populations in Mycoplasma capricolum subsp. capricolum and M. agalactiae - XIAO-XIA MA; YU-PING FENG; JIA-LING BAI; DE-RONG ZHANG; XIN-SHI LIN; ZHONG-REN MA (Journal of Genetics, 2015)

Prauserella endophytica sp. nov., an endophytic actinobacterium isolated from Tamarix taklamakanensis - Jia-Meng Liu; Xugela Habden; Lin Guo; Li Tuo; Zhong-Ke Jiang; Shao-Wei Liu; Xian-Fu Liu; Li Chen; Rong-Feng Li; Yu-Qin Zhang; Cheng-Hang Sun (Antonie van Leeuwenhoek, 2015)

l-Amino acid carbamate prodrugs of scutellarin: synthesis, physiochemical property, Caco-2 cell permeability, and in vitro anti-oxidative activity - Yu-Feng Cha; Shun Zhang; Hang Su; Yu Ou; Xiao-Zhong Fu; Feng-Jie Jiang; Yong-Long Zhao; Yong-Xi Dong; Min Luo; Yong Huang; Yan-Yu Lan; Ai-Min Wang; et al. (Medicinal Chemistry Research, 2015)

Rapid emergence of a PB2-E627K substitution confers a virulent phenotype to an H9N2 avian influenza virus during adaption in mice - Xiaoyu Sang; Airong Wang; Tongjie Chai; Xijun He; Jie Ding; Xiaolong Gao; Yuanguo Li; Kun Zhang; Zhiguang Ren; Lin Li; Zhijun Yu; Tiecheng Wang; et al. (Archives of Virology, 2015)

Association between the CYP1A2 polymorphisms and risk of cancer: a meta-analysis - Wen-Xia Sun; Ying-Hua Chen; Zhi-Zhong Liu; Jian-Jun Xie; Wei Wang; Ya-Ping Du; Yu Chen; Xu-Liang Shen; Xiao-Feng He; Li-Xia Wu; Wu Wei; Lin Zhang (Molecular Genetics and Genomics, 2015)

Association between the CYP2E1 polymorphisms and lung cancer risk: a meta-analysis - Xiang-Hua Ye; Liang Song; Ling Peng; Zhibin Bu; Sen-Xiang Yan; Jie Feng; Xin-Li Zhu; Xin-Biao Liao; Xue-Lin Yu; Danfang Yan (Molecular Genetics and Genomics, 2015)

IL-12 could induce monocytic tumor cells directional differentiation - Ting-ting Ma; Bi-Tao Wu; Yan Lin; Hai-Yu Xiong; Qin Wang; Zi-Wei Li; Feng Cheng; Zhi-Guang Tu (Molecular and Cellular Biochemistry, 2015)

Eutrophic water purification efficiency using a combination of hydrodynamic cavitation and ozonation on a pilot scale - Wei-Xin Li; Chuan-Dong Tang; Zhi-Lin Wu; Wei-Min Wang; Yu-Feng Zhang; Yi Zhao; Giancarlo Cravotto (Environmental Science and Pollution Research, 2015)

Phylogenetic and recombination analysis of rice black-streaked dwarf virus segment 9 in China - Yu Zhou; Jian-Feng Weng; Yan-Ping Chen; Chang-Lin Liu; Xiao-Hua Han; Zhuan-Fang Hao; Ming-Shun Li; Hong-Jun Yong; De-Gui Zhang; Shi-Huang Zhang; Xin-Hai Li (Archives of Virology, 2015)

Esthetic Management of Mucogingival Defects After Excision of Epulis Using Laterally Positioned Flaps - Yu-feng Xie; Rong Shu; Jie-lei Qian; Zhi-kai Lin; Georgios E. Romanos (Cell Biochemistry and Biophysics, 2015)

Dental pulp stem cells derived conditioned medium promotes angiogenesis in hindlimb ischemia - ChongYang Shen; Lin Li; Ting Feng; JinRong Li; MeiXing Yu; Qiao Lu; Hong Li (Tissue Engineering and Regenerative Medicine, 2015)

Conjugated linoleic acid alters growth performance, tissue lipid deposition, and fatty acid composition of darkbarbel catfish (Pelteobagrus vachelli) - Gui-Fang Dong; Wen-Zuo Liu; Lin-Zhou Wu; Deng-hang Yu; Feng Huang; Peng-Cheng Li; Yan-ou Yang (Fish Physiology and Biochemistry, 2015)

Effects of rapamycin against paraquat-induced pulmonary fibrosis in mice - Xue Shao; Meng Li; Chong Luo; Ying-ying Wang; Ying-ying Lu; Shi Feng; Heng Li; Xia-bing Lang; Yu-cheng Wang; Chuan Lin; Xiu-jin Shen; Qin Zhou; et al. (Journal of Zhejiang University-SCIENCE B, 2015)

Impacts of uncertainty in AVOC emissions on the summer ROx budget and ozone production rate in the three most rapidly-developing economic growth regions of China - Feng Wang; Junling An; Ying Li; Yujia Tang; Jian Lin; Yu Qu; Yong Chen; Bing Zhang; Jing Zhai (Advances in Atmospheric Sciences, 2014)

Inhibition of acid-sensing ion channel 1a in hepatic stellate cells attenuates PDGF-induced activation of HSCs through MAPK pathway - Fan-rong Wu; Chun-xiao Pan; Chao Rong; Quan Xia; Feng-lai Yuan; Jie Tang; Xiao-yu Wang; Nan Wang; Wen-lin Ni; Fei-hu Chen (Molecular and Cellular Biochemistry, 2014)

Cause of severe droughts in Southwest China during 1951–2010 - Lin Feng; Tim Li; Weidong Yu (Climate Dynamics, 2014)

Development and characterization of 13 novel microsatellite loci in a threatened reef fish, humpback grouper (Cromileptes altivelis) - Yu Wang; Guohua Chen; Feng Yan; Haoran Lin; Jian Luo (Conservation Genetics Resources, 2014)

RETRACTED ARTICLE: Lactoferrin promote primary rat osteoblast proliferation and differentiation via up-regulation of insulin-like growth factor-1 expression - Jian-ming Hou; Man Wu; Qing-ming Lin; Fan Lin; Ying Xue; Xu-hua Lan; En-yu Chen; Mei-li Wang; Hai-yan Yang; Feng-xiong Wang (Molecular Biology Reports, 2014)

Polymorphisms of pentanucleotide repeats (tttta)n in the promoter of CYP11A1 and their relationships to polycystic ovary syndrome (PCOS) risk: a meta-analysis - Min Yu; Ruizhi Feng; Xiaoxi Sun; Haojue Wang; Huan Wang; Qing Sang; Li Jin; Lin He; Lei Wang (Molecular Biology Reports, 2014)

Cannabinoid receptor 1 disturbance of PPARγ2 augments hyperglycemia induction of mesangial inflammation and fibrosis in renal glomeruli - Chun-Liang Lin; Yung-Chien Hsu; Pei-Hsien Lee; Chen-Chou Lei; Jeng-Yi Wang; Yu-Ting Huang; Shao-Yu Wang; Feng-Sheng Wang (Journal of Molecular Medicine, 2014)

Retraction Note: Overestimated accuracy of circular dichroism in determining protein secondary structure - Kailei Lin; Huayan Yang; Zhengya Gao; Feng Li; Shaoning Yu (European Biophysics Journal, 2014)

Medullo-ponto-cerebellar white matter degeneration altered brain network organization and cortical morphology in multiple system atrophy - Chia-Feng Lu; Po-Shan Wang; Yuan-Lin Lao; Hsiu-Mei Wu; Bing-Wen Soong; Yu-Te Wu (Brain Structure and Function, 2014)

Development, inheritance and evaluation of 55 novel single nucleotide polymorphism markers for parentage assignment in the Pacific oyster (Crassostrea gigas) - Yu-Lin Jin; Ling-Feng Kong; Hong Yu; Qi Li (Genes & Genomics, 2014)

Genetic variation at 8q24, family history of cancer, and upper gastrointestinal cancers in a Chinese population - Heather P. Tarleton; Shen-Chih Chang; Sungshim Lani Park; Lin Cai; Baoguo Ding; Na He; Shehnaz K. Hussain; Qingwu Jiang; Li-Na Mu; Jianyu Rao; Hua Wang; Nai-Chieh Y. You; et al. (Familial Cancer, 2014)

HIRA is essential for the development of gibel carp - Meng-Yu Wang; Qiu-Hong Guo; Xin-Zheng Du; Li Zhou; Qian Luo; Qiao-Hui Zeng; Jia-Lin Wang; Hao-Bin Zhao; Yu-Feng Wang (Fish Physiology and Biochemistry, 2014)

A new oleanane-type triterpenoidal saponin from Pulsatilla chinensis - Zhan Shu; Zhong Chen; Yan-li Liu; Wei-feng Zhu; Yu-lin Feng; Qiong-ming Xu; Xiao-ran Li; Shi-lin Yang (Natural Product Research, 2013)

Fumigant activity of Illicium verum fruit extracts and their effects on the acetylcholinesterase and glutathione S-transferase activities in adult Sitophilus zeamais - Shi-Guang Li; Mao-Ye Li; Yan-Zhang Huang; Ri-Mao Hua; Hua-Feng Lin; Yu-Jie He; Lin-Lin Wei; Zhu-Qin Liu (Journal of Pest Science, 2013)

Design, synthesis, and evaluation of fluorescent cell-penetrating peptidic antagonists of Grb2-SH2 for targeting MCF-7 breast cancer cells - Yu-Cheng Hsiao; Chen-Yu Lee; Yi-Jhen Lin; Shu-Huai Tsai; Kee-Ching G. Jeng; Wei-Ting Chao; Feng-Di T. Lung (Medicinal Chemistry Research, 2013)

Ecological Risks Assessment and Pollution Source Identification of Trace Elements in Contaminated Sediments from the Pearl River Delta, China - Feng Li; Xiang-yun Zeng; Chang-hua Wu; Zhi-peng Duan; Yan-mao Wen; Guo-ru Huang; Xiao-lin Long; Min-Jian Li; Man-Jie Li; Jiang-Yu Xu (Biological Trace Element Research, 2013)

The effects of the codon usage and translation speed on protein folding of 3Dpol of foot-and-mouth disease virus - Xiao-xia Ma; Yu-ping Feng; Jun-lin Liu; Bing Ma; Li Chen; Yong-qing Zhao; Peng-hui Guo; Jun-zhen Guo; Zhong-ren Ma; Jie Zhang (Veterinary Research Communications, 2013)

Isolation and characterization of polymorphic microsatellite loci in Ping’s juniper Juniperus pingii - Zhong-Hu Li; Zhan-Lin Liu; Yu-Jin Wang; Min-Feng Fang; Ma-Li Wang; Zhi-Xuan Li; Gui-Fang Zhao (Conservation Genetics Resources, 2013)

Distribution and temporal trend of polybrominated diphenyl ethers in one Shanghai municipal landfill, China - Kai Huang; Jie Guo; Kuang-fei Lin; Xiao-yu Zhou; Jun-xia Wang; Peng Zhou; Feng Xu; Mei-Lan Zhang (Environmental Science and Pollution Research, 2013)

Differential distribution and activation of microglia in the brain of male C57BL/6J mice - Ting-Ting Yang; Chingju Lin; Chao-Tien Hsu; Tzu-Feng Wang; Fang-Yi Ke; Yu-Min Kuo (Brain Structure and Function, 2013)

Overestimated accuracy of circular dichroism in determining protein secondary structure - Kailei Lin; Huayan Yang; Zhengya Gao; Feng Li; Shaoning Yu (European Biophysics Journal, 2013)

Selenium Attenuates Adriamycin-Induced Cardiac Dysfunction via Restoring Expression of ATP-Sensitive Potassium Channels in Rats - Zhong-Wei Liu; Xiao-Lin Niu; Kun-Lun Chen; Yu-Jie Xing; Xuan Wang; Chuan Qiu; Deng-Feng Gao (Biological Trace Element Research, 2013)

The distribution and variability of simulated chlorophyll concentration over the tropical Indian Ocean from five CMIP5 models - Lin Liu; Lin Feng; Weidong Yu; Huiwu Wang; Yanliang Liu; Shuangwen Sun (Journal of Ocean University of China, 2013)

Enhanced differentiation potential of human amniotic mesenchymal stromal cells by using three-dimensional culturing - Xue Lin; Hao Yu Li; Lian Feng Chen; Bo Jiang Liu; Yian Yao; Wen Ling Zhu (Cell and Tissue Research, 2013)

Purification and characterization of alkaline phosphatase from the gut of sea cucumber Stichopus japonicus - Hai-Tao Wu; Dong-Mei Li; Bei-Wei Zhu; Jing-Heng Cheng; Jin-Jian Sun; Feng-Lin Wang; Yang Yang; Yu-Kun Song; Chen-Xu Yu (Fisheries Science, 2013)

Pseudomonas aeruginosa isolates of distinct sub-genotypes exhibit similar potential of antimicrobial resistance by drugs exposure - Zhen-Hong Liu; Yan Xu; Li-Bo Duo; Yu Liu; Zhao-Zhen Xu; Jane L. Burns; Gui-Rong Liu; Bao-Feng Yang; Shu-Lin Liu (Antonie van Leeuwenhoek, 2013)

Comparison of early transcriptome responses to copper and cadmium in rice roots - Chung-Yi Lin; Ngoc Nam Trinh; Shih-Feng Fu; Yu-Chyuan Hsiung; Li-Chiao Chia; Chung-Wen Lin; Hao-Jen Huang (Plant Molecular Biology, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Using three-dimensional multigrid-based snake and multiresolution image registration for reconstruction of cranial defect - Yuan-Lin Liao; Chia-Feng Lu; Chieh-Tsai Wu; Jiann-Der Lee; Shih-Tseng Lee; Yung-Nien Sun; Yu-Te Wu (Medical & Biological Engineering & Computing, 2013)

Glycogen synthase kinase-3β inactivation is an intracellular marker and regulator for endotoxemic neutrophilia - Tsan-Tzu Yang; Chia-Ling Chen; Wei-Chieh Lin; Yee-Shin Lin; Po-Chun Tseng; Chia-Yuan Hsieh; Yu-Hong Chen; Wei-Ching Huang; Cheng-Chieh Tsai; Chi-Yun Wang; Chi-Chang Shieh; Chiou-Feng Lin (Journal of Molecular Medicine, 2013)

Suggestion of GLYAT gene underlying variation of bone size and body lean mass as revealed by a bivariate genome-wide association study - Yan-Fang Guo; Li-Shu Zhang; Yong-Jun Liu; Hong-Gang Hu; Jian Li; Qing Tian; Ping Yu; Feng Zhang; Tie-Lin Yang; Yan Guo; Xiang-Lei Peng; Meng Dai; et al. (Human Genetics, 2013)

Tectonic mechanism of the Suining (Ms5.0) earthquake, center of Sichuan Basin, China - Rong-jun Zhou; Yong Li; Laurence Svirchev; Yong-jiu Zhang; Deng-fa He; Yu-lin He; Pei-lin Zhao; Zan-jun Wang; Feng Long; Jin-rong Su; Shi-yuan Wang; Ming-jian Liang; et al. (Journal of Mountain Science, 2013)

Albumin prevents reactive oxygen species-induced mitochondrial damage, autophagy, and apoptosis during serum starvation - Shu-Yu Liu; Chia-Ling Chen; Tsan-Tzu Yang; Wei-Ching Huang; Chia-Yuan Hsieh; Wan-Jou Shen; Tsung-Ting Tsai; Chi-Chang Shieh; Chiou-Feng Lin (Apoptosis, 2012)

The dissection and SSR mapping of a high-temperature adult-plant stripe rust resistance gene in American spring wheat cultivar Alturas - Lei Zhao; Jing Feng; Chun-Yu Zhang; Xiao-Dan Xu; Xian-Ming Chen; Quan Sun; Qing Miao; Shi-Chang Xu; Feng Lin (European Journal of Plant Pathology, 2012)

Cool seasons are related to poor prognosis in patients with infective endocarditis - Su-Jung Chen; Tze-Fan Chao; Yenn-Jiang Lin; Li-Wei Lo; Yu-Feng Hu; Ta-Chuan Tuan; Tsui-Lieh Hsu; Wen-Chung Yu; Hsin-Bang Leu; Shih-Lin Chang; Shih-Ann Chen (International Journal of Biometeorology, 2012)

Time-dependent expression and distribution of Egr-1 during skeletal muscle wound healing in rats - Yan-Yan Fan; Guang-Hua Ye; Ke-Zhi Lin; Lin-Sheng Yu; Shu-Zhen Wu; Miao-Wu Dong; Jun-Ge Han; Xiang-Ping Feng; Xing-Biao Li (Journal of Molecular Histology, 2012)

Calreticulin Mediates Nerve Growth Factor-Induced Neuronal Differentiation - Yu-Yin Shih; Akira Nakagawara; Hsinyu Lee; Hsueh-Fen Juan; Yung-Ming Jeng; Dong-Tsamn Lin; Yung-Li Yang; Yeou-Guang Tsay; Min-Chuan Huang; Chien-Yuan Pan; Wen-Ming Hsu; Yung-Feng Liao (Journal of Molecular Neuroscience, 2012)

Cloning and sequence analysis of two banana bunchy top virus genomes in Hainan - Nai-Tong Yu; Yu-Liang Zhang; Tuan-Cheng Feng; Jian-Hua Wang; Mahesh Kulye; Wen-Jun Yang; Zhan-Song Lin; Zhongguo Xiong; Zhi-Xin Liu (Virus Genes, 2012)

Risk stratification of spontaneous bacterial peritonitis in cirrhosis with ascites based on classification and regression tree analysis - Ke-Qing Shi; Yu-Chen Fan; Li Ying; Xian-Feng Lin; Mei Song; Ling-Fei Li; Xie-Yan Yu; Yong-Ping Chen; Ming-Hua Zheng (Molecular Biology Reports, 2012)

Association between TaqIB polymorphism of cholesteryl ester transfer protein and coronary artery disease in the Chinese population - Qi Yu; En-qi Liu; Si-hai Zhao; Ya-feng Li; Yan-li Wang; Yu-long Chen; Ke-na Wei; Bing-qiao Huang; Jian-lin Fan; Peng-hui Yang (Journal of Zhejiang University-SCIENCE B, 2012)

Regulation of voltage-gated sodium current by endogenous Src family kinases in cochlear spiral ganglion neurons in culture - Shuang Feng; Melissa Pflueger; Shuang-Xiu Lin; Bradley R. Groveman; Jiping Su; Xian-Min Yu (Pflügers Archiv - European Journal of Physiology, 2012)

The expression level of Rosa Terminal Flower 1 (RTFL1) is related with recurrent flowering in roses - Li-Na Wang; Yun-Feng Liu; Yu-Man Zhang; Rong-Xiang Fang; Qing-Lin Liu (Molecular Biology Reports, 2012)

Strontium Ranelate Prevents Bone Loss in a Rat Model of Localized Muscle Paralysis - Zhi-Feng Sheng; Yu-Lin Ma; Dejun Tong; De-Yu Fang; Qing-Chun Liang; Li-Hong Liu; Jian Zhang; Er-Yuan Liao (Annals of Biomedical Engineering, 2012)

Immobilization of foreign protein into polyhedra of Bombyx mori nucleopolyhedrovirus (BmNPV) - Xing-wei Xiang; Rui Yang; Lin Chen; Xiao-long Hu; Shao-fang Yu; Cui-ping Cao; Xiao-feng Wu (Journal of Zhejiang University-SCIENCE B, 2012)

A Novel Mutation in CACNA1S Gene Associated with Hypokalemic Periodic Paralysis Which has a Gender Difference in the Penetrance - Fei-Feng Li; Qian-Qian Li; Zhen-Xuan Tan; Si-Yao Zhang; Ji Liu; Er-ying Zhao; Gui-Chun Yu; Jin Zhou; Li-Ming Zhang; Shu-Lin Liu (Journal of Molecular Neuroscience, 2012)

AURKB and MAPK involvement in the regulation of the early stages of mouse zygote development - Lin Xu; Tong Liu; Feng Han; ZhiHong Zong; GuoLi Wang; BingZhi Yu; Jie Zhang (Science China Life Sciences, 2012)

ADAM17 regulates prostate cancer cell proliferation through mediating cell cycle progression by EGFR/PI3K/AKT pathway - Ping Lin; Xicai Sun; Tian Feng; Haifeng Zou; Ying Jiang; Zijun Liu; Dandan Zhao; Xiaoguang Yu (Molecular and Cellular Biochemistry, 2012)

The impact of iron oxide magnetic nanoparticles on the soil bacterial community - Shiying He; Youzhi Feng; Hongxuan Ren; Yu Zhang; Ning Gu; Xiangui Lin (Journal of Soils and Sediments, 2011)

Genome-wide analysis of OCT4 binding sites in glioblastoma cancer cells - Xue-feng Fang; Wei-yi Zhang; Na Zhao; Wei Yu; Dong Ding; Xu Hong; Li-sha Li; Hua-rong Zhang; Shu Zheng; Biao-yang Lin (Journal of Zhejiang University-SCIENCE B, 2011)

Relationship between temperature change and the requirement for a permanent pacemaker implantation in bradyarrhythmias - I-Fan Liu; Shih-Lin Chang; Li-Wei Lo; Yu-Feng Hu; Ta-Chuan Tuan; Chi-Woon Kong; Tsu-Juey Wu; Chern-En Chiang; Shih-Ann Chen; Yenn-Jiang Lin (International Journal of Biometeorology, 2011)

Study on algorithms of low SNR inversion of T 2 spectrum in NMR - Feng Lin; Zhu-Wen Wang; Jing-Ye Li; Xue-Ang Zhang; Yu-Long Jiang (Applied Geophysics, 2011)

Comparison of Relationships Between pH, Dissolved Oxygen and Chlorophyll a for Aquaculture and Non-aquaculture Waters - Changjuan Zang; Suiliang Huang; Min Wu; Shenglan Du; Miklas Scholz; Feng Gao; Chao Lin; Yong Guo; Yu Dong (Water, Air, & Soil Pollution, 2011)

Combined administration of D-galactose and aluminium induces Alzheimerlike lesions in brain - Fei Xiao; Xiao-Guang Li; Xiao-Yu Zhang; Jun-Dai Hou; Lian-Feng Lin; Qin Gao; Huan-Min Luo (Neuroscience Bulletin, 2011)

HLA polymorphism of the Zhuang population reflects the common HLA characteristics among Zhuang-Dong language-speaking populations - Li Shi; Xiao-qin Huang; Lei Shi; Yu-fen Tao; Yu-feng Yao; Liang Yu; Ke-qin Lin; Wen Yi; Hao Sun; Katsushi Tokunaga; Jia-you Chu (Journal of Zhejiang University-SCIENCE B, 2011)

Interaction of green tea polyphenol epigallocatechin-3-gallate with sunitinib: potential risk of diminished sunitinib bioavailability - Jun Ge; Ben-Xu Tan; Ye Chen; Li Yang; Xing-Chen Peng; Hong-Ze Li; Hong-Jun Lin; Yu Zhao; Meng Wei; Ke Cheng; Long-Hao Li; Hang Dong; et al. (Journal of Molecular Medicine, 2011)

Molecular epidemiology of Echovirus 30 in Taiwan, 1988–2008 - Guan-Ming Ke; Kuei-Hsiang Lin; Po-Liang Lu; Yi-Chin Tung; Chu-Feng Wang; Liang-Yin Ke; Min-Sheng Lee; Pei-Chin Lin; Hui-Ju Su; Yi-Ying Lin; Tzu-Ping Huang; Jen-Ren Wang; et al. (Virus Genes, 2011)

Fbxw8 is involved in the proliferation of human choriocarcinoma JEG-3 cells - Ping Lin; Jiejun Fu; Binjiahui Zhao; Feng Lin; Haifeng Zou; Leiyu Liu; Cheng Zhu; Hongmei Wang; Xiaoguang Yu (Molecular Biology Reports, 2011)

β-Actin is a downstream effector of the PI3K/AKT signaling pathway in myeloma cells - Yen-Peng Ho; Chi-Wei Kuo; Yuan-Tong Hsu; Yu-Shan Huang; Li-Ping Yew; Wei-Feng Huang; Kuo-Chih Lin; Jung-Hsin Hsu (Molecular and Cellular Biochemistry, 2011)

Three-dimensional reconstruction of cranial defect using active contour model and image registration - Yuan-Lin Liao; Chia-Feng Lu; Yung-Nien Sun; Chieh-Tsai Wu; Jiann-Der Lee; Shih-Tseng Lee; Yu-Te Wu (Medical & Biological Engineering & Computing, 2011)

Phylogeny of Arachis based on internal transcribed spacer sequences - Chuan Tang Wang; Xiu Zhen Wang; Yue Yi Tang; Dian Xu Chen; Feng Gao Cui; Jian Cheng Zhang; Shan Lin Yu (Genetic Resources and Crop Evolution, 2011)

Adenosine postconditioning protects against myocardial ischemia–reperfusion injury though modulate production of TNF-α and prevents activation of transcription factor NF-kappaB - Jian-Juan Ke; Feng-Xu Yu; Yan Rao; Yan-Lin Wang (Molecular Biology Reports, 2011)

Th17 promotes acute rejection following liver transplantation in rats - Xiao-jun Xie; Yu-fu Ye; Lin Zhou; Hai-yang Xie; Guo-ping Jiang; Xiao-wen Feng; Yong He; Qin-fen Xie; Shu-sen Zheng (Journal of Zhejiang University-SCIENCE B, 2010)

Inhibition of phosphodiesterase-4 reverses memory deficits produced by Aβ25–35 or Aβ1–40 peptide in rats - Yu-Fang Cheng; Chuang Wang; Huan-Bing Lin; Yun-Feng Li; Ying Huang; Jiang-Ping Xu; Han-Ting Zhang (Psychopharmacology, 2010)

Cloning and characterization of a potato TFL1 gene involved in tuberization regulation - Jian-Lin Guo; Chun-Lin Yu; Chun-Yuan Fan; Qi-Neng Lu; Jing-Ming Yin; Yun-Feng Zhang; Qing Yang (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Morphological changes of Fusarium oxysporum induced by CF66I, an antifungal compound from Burkholderia cepacia - Xin Li; Hui-Ying Yu; Yi-Feng Lin; Hong-Mei Teng; Lei Du; Guo-Gang Ma (Biotechnology Letters, 2010)

Artificial gynogenesis and assessment of homozygosity in meiotic gynogens of spotted halibut (Verasper variegatus) - Xiang-Shan Ji; Song-Lin Chen; Jing-Feng Yang; Hong-Yu Ma; Yun-Liang Jiang (Aquaculture International, 2010)

Quantification of model uncertainty in environmental modeling - Ming Ye; Philip D. Meyer; Yu-Feng Lin; Shlomo P. Neuman (Stochastic Environmental Research and Risk Assessment, 2010)

Predicting subcellular location of proteins using integrated-algorithm method - Yu-Dong Cai; Lin Lu; Lei Chen; Jian-Feng He (Molecular Diversity, 2010)

Relation of uric acid levels to aortic root dilatation in hypertensive patients with and without metabolic syndrome - Li-jiang Tang; Jian-jun Jiang; Xiao-feng Chen; Jian-an Wang; Xian-fang Lin; Yu-xi Du; Cong-feng Fang; Zhao-xia Pu (Journal of Zhejiang University-SCIENCE B, 2010)

Regulation of the seasonal population patterns of Helicoverpa armigera moths by Bt cotton planting - Yu-lin Gao; Hong-qiang Feng; Kong-ming Wu (Transgenic Research, 2010)

Over-expression of the AtGA2ox8 gene decreases the biomass accumulation and lignification in rapeseed (Brassica napus L.) - Xiao-ying Zhao; Deng-feng Zhu; Bo Zhou; Wu-sheng Peng; Jian-zhong Lin; Xing-qun Huang; Re-qing He; Yu-hong Zhuo; Dan Peng; Dong-ying Tang; Ming-fang Li; Xuan-ming Liu (Journal of Zhejiang University-SCIENCE B, 2010)

Involvement of the residues of GSKIP, AxinGID, and FRATtide in their binding with GSK3β to unravel a novel C-terminal scaffold-binding region - Shen-Long Howng; Chi-Ching Hwang; Chia-Yi Hsu; Meng-Yu Hsu; Chun-Yen Teng; Chia-Hua Chou; Mei-Feng Lee; Chia-Hung Wu; Shean-Jaw Chiou; Ann-Shung Lieu; Joon-Khim Loh; Chia-Ning Yang; et al. (Molecular and Cellular Biochemistry, 2010)

Impact of female cigarette smoking on circulating B cells in vivo: the suppressed ICOSLG, TCF3, and VCAM1 gene functional network may inhibit normal cell function - Feng Pan; Tie-Lin Yang; Xiang-Ding Chen; Yuan Chen; Ge Gao; Yao-Zhong Liu; Yu-Fang Pei; Bao-Yong Sha; Yan Jiang; Chao Xu; Robert R. Recker; Hong-Wen Deng (Immunogenetics, 2010)

Protein sumoylation sites prediction based on two-stage feature selection - Lin Lu; Xiao-He Shi; Su-Jun Li; Zhi-Qun Xie; Yong-Li Feng; Wen-Cong Lu; Yi-Xue Li; Haipeng Li; Yu-Dong Cai (Molecular Diversity, 2010)

A 9-bp Deletion Homoplasmy in Women with Polycystic Ovary Syndrome Revealed by Mitochondrial Genome-Mutation Screen - Guangchao Zhuo; Guofang Feng; Jianhang Leng; Lin Yu; Yan Jiang (Biochemical Genetics, 2010)

Construction of a Genetic Linkage Map and Mapping of a Female-Specific DNA Marker in Half-Smooth Tongue Sole (Cynoglossus semilaevis) - Xiaolin Liao; Hong-Yu Ma; Gen-Bo Xu; Chang-Wei Shao; Yong-Sheng Tian; Xiang-Shan Ji; Jing-Feng Yang; Song-Lin Chen (Marine Biotechnology, 2009)

Isolation and characterization of microsatellites in Chinese white olive (Canarium album) and cross-species amplification in Canarium pimela - Xin Zhang; Wan-Hui Ye; Hong-Lin Cao; Zheng-Feng Wang; Hao Shen; Ju-Yu Lian (Conservation Genetics, 2009)

A complete mitochondrial genome of wheat (Triticum aestivum cv. Chinese Yumai), and fast evolving mitochondrial genes in higher plants - Peng Cui; Huitao Liu; Qiang Lin; Feng Ding; Guoyin Zhuo; Songnian Hu; Dongcheng Liu; Wenlong Yang; Kehui Zhan; Aimin Zhang; Jun Yu (Journal of Genetics, 2009)

Human papillomavirus type-distribution in cervical cancer in China: the importance of HPV 16 and 18 - Wen Chen; Xun Zhang; Anco Molijn; David Jenkins; Ju-Fang Shi; Wim Quint; Johannes E. Schmidt; Ping Wang; Yu-Ling Liu; Lian-Kun Li; Hong Shi; Ji-Hong Liu; et al. (Cancer Causes & Control, 2009)

A 60-s postconditioning protocol by percutaneous coronary intervention inhibits myocardial apoptosis in patients with acute myocardial infarction - Wen-Shu Zhao; Lin Xu; Le-Feng Wang; Li Zhang; Zhi-Yong Zhang; Yu Liu; Xiu-Lan Liu; Xin-Chun Yang; Liang Cui; Lin Zhang (Apoptosis, 2009)

Resistin induces rat insulinoma cell RINm5F apoptosis - Chun-lin Gao; De-yu Zhao; Jie Qiu; Chun-mei Zhang; Chen-bo Ji; Xiao-hui Chen; Feng Liu; Xi-rong Guo (Molecular Biology Reports, 2009)

Polymorphisms within promoter of Japanese flounder (Paralichthys olivaceus) ovary cytochrome P450-c19 (CYP19a) gene associated with reproductive traits - Feng He; Hai Shen Wen; Shuang Lin Dong; Bao Shi; Cai Fang Chen; Lian Shun Wang; Jun Yao; Xing Jiang Mu; Yu Guo Zhou (Fish Physiology and Biochemistry, 2009)

A ThCAP gene from Tamarix hispida confers cold tolerance in transgenic Populus (P. davidiana × P. bolleana) - Xiao-Hong Guo; Jing Jiang; Shi-Jie Lin; Bai-Chen Wang; Yu-Cheng Wang; Gui-Feng Liu; Chuan-Ping Yang (Biotechnology Letters, 2009)

Numerical Simulations on the Effect of Sea–Land Breezes on Atmospheric Haze over the Pearl River Delta Region - Chen Xun-lai; Feng Ye-rong; Li Jiang-nan; Lin Wen-shi; Fan Shao-jia; Wang An-yu; Fong Soikun; Lin Hui (Environmental Modeling & Assessment, 2009)

Genome-wide association scan for stature in Chinese: evidence for ethnic specific loci - Shu-Feng Lei; Tie-Lin Yang; Li-Jun Tan; Xiang-Ding Chen; Yan Guo; Yan-Fang Guo; Liang Zhang; Xiao-Gang Liu; Han Yan; Feng Pan; Zhi-Xin Zhang; Yu-Mei Peng; et al. (Human Genetics, 2009)

Isolation and characterization of microsatellite loci in the commercially important mudshrimp Austinogebia edulis (Upogebiidae) using PCR-based isolation of microsatellite arrays (PIMA) - Tzen-Yuh Chiang; Hung-Du Lin; Tin-Yam Chan; Cheng-Yu Hung; Feng-Jiau Lin (Conservation Genetics, 2008)

The Influence of Center of Rotation on the Assessment of Trabecular Bone Densitometric and Structural Properties - Zhi-Feng Sheng; Ru-Chun Dai; Xian-Ping Wu; Yu-Lin Ma; Kang Xu; Yu-Hai Zhang; Ye-Bin Jiang; Er-Yuan Liao (Annals of Biomedical Engineering, 2008)

Assessment of sampling designs to measure riverine fluxes from the Pearl River Delta, China to the South China Sea - Hong-Gang Ni; Feng-Hui Lu; Xian-Lin Luo; Hui-Yu Tian; Ji-Zhong Wang; Yu-Feng Guan; She-Jun Chen; Xiao-Jun Luo; Eddy Y. Zeng (Environmental Monitoring and Assessment, 2008)

Prediction of compounds’ biological function (metabolic pathways) based on functional group composition - Yu-Dong Cai; Ziliang Qian; Lin Lu; Kai-Yan Feng; Xin Meng; Bing Niu; Guo-Dong Zhao; Wen-Cong Lu (Molecular Diversity, 2008)

Evolutionary characterization of influenza virus A/duck/Hubei/W1/2004 (H9N2) isolated from central China - Xiao-Juan Xu; Gao-Yuan Xu; Hong-Bo Zhou; Zheng-Jun Yu; An-Ding Zhang; Yun-Feng Song; Mei-Lin Jin; Huan-Chun Chen (Virus Genes, 2008)

A collection of 10,096 indica rice full-length cDNAs reveals highly expressed sequence divergence between Oryza sativa indica and japonica subspecies - Xiaohui Liu; Tingting Lu; Shuliang Yu; Ying Li; Yuchen Huang; Tao Huang; Lei Zhang; Jingjie Zhu; Qiang Zhao; Danlin Fan; Jie Mu; Yingying Shangguan; et al. (Plant Molecular Biology, 2007)

Biosorption and Bioreduction of Trivalent Aurum by Photosynthetic Bacteria Rhodobacter capsulatus - Youzhi Feng; Yongchang Yu; Yiming Wang; Xiangui Lin (Current Microbiology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Role of P-glycoprotein in Limiting the Brain Penetration of Glabridin, An Active Isoflavan from the Root of Glycyrrhiza glabra - Xi-Yong Yu; Shu-Guang Lin; Zhi-Wei Zhou; Xiao Chen; Jun Liang; Xue-Qing Yu; Balram Chowbay; Jing-Yuan Wen; Wei Duan; Eli Chan; Xiao-Tian Li; Jie Cao; et al. (Pharmaceutical Research, 2007)

Proteomic profiling of proteins dysregulted in Chinese esophageal squamous cell carcinoma - Xiao-Li Du; Hai Hu; De-Chen Lin; Shu-Hua Xia; Xiao-Ming Shen; Yu Zhang; Man-Li Luo; Yan-Bin Feng; Yan Cai; Xin Xu; Ya-Ling Han; Qi-Min Zhan; et al. (Journal of Molecular Medicine, 2007)

Methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C polymorphisms and the risk of primary Hepatocellular Carcinoma (HCC) in a Chinese population - Li-Na Mu; Wei Cao; Zuo-Feng Zhang; Lin Cai; Qing-Wu Jiang; Nai-Chieh You; Binh Yang Goldstein; Guo-Rong Wei; Chuan-Wei Chen; Qing-Yi Lu; Xue-Fu Zhou; Bao-Guo Ding; et al. (Cancer Causes & Control, 2007)

Effect of proximal femoral osteoporosis on cementless hip arthroplasty: A short-term clinical analysis - Xian-feng Lou; Yu-hong Li; Xiang-jin Lin (Journal of Zhejiang University-SCIENCE B, 2007)

Avian Reovirus activates a novel proapoptotic signal by linking Src to p53 - Lin Ping-Yuan; Liu Hung-Jen; Lai Meng-Jiun; Yu Feng-Ling; Hsu Hsue-Yin; Lee Jeng-Woei; Shih Wen-Ling (Apoptosis, 2006)

Protoplast Fusion between Geotrichum candidium and Phanerochaete chrysosporium to Produce Fusants for Corn Stover Fermentation - Yong Zhang; Shu-Mei Lin; Yu-Jing Zhu; Chang-Jiang Liu; Yan Dong; Fang-Fang Li; Gao-Feng Wu; Hai-Yan Wang; Jing-Hai Zhang (Biotechnology Letters, 2006)

A GIS Process for Delimitating Areas Potentially Endangered by Debris Flow - Fan-Chieh Yu; Chien-Yuan Chen; Tien-Chien Chen; Feng-Yi Hung; Sheng-Chi Lin (Natural Hazards, 2006)

A Novel Alginate Lyase with High Activity on Acetylated Alginate of Pseudomonas aeruginosa FRD1 from Pseudomonas sp. QD03 - Lin Xiao; Feng Han; Zhao Yang; Xin-zhi Lu; Wen-gong Yu (World Journal of Microbiology and Biotechnology, 2006)

Spatial and temporal dynamics of soil organic carbon in reserved desertification area - Shu-lan Cheng; Hua Ouyang; Hai-shan Niu; Lin Wang; Feng Zhang; Jun-qin Gao; Yu-qiang Tian (Chinese Geographical Science, 2004)

Intracellular expression of Vitreoscilla hemoglobin in Aspergillus terreus to alleviate the effect of a short break in aeration during culture - Yu-Hui Lin; Ywan-Feng Li; Min-Chang Huang; Ying-Chieh Tsai (Biotechnology Letters, 2004)

Study on construction of cDNA libraries from rat normal liver and regeneration liver with smart technique - Lin Jun-Tang; Wang Cong-Rui; Jogenananda Pramanik; Zhang Hui-Yong; Feng Hui-Gen; Yang Bao-Sheng; L. I. Yu-Chang; Xu Cun-Shuan (Indian Journal of Clinical Biochemistry, 2004)

The evaluation and analysis of the tourism resources in Jilin Province - Tao-fang Yu; Chao-lin Gu; Hong Wang; Xue-jun Duan; Xiao-feng Yi (Chinese Geographical Science, 2002)

Temporal selectivity by single neurons in the torus semicircularis of Batrachyla antartandica (Amphibia: Leptodactylidae) - Mario Penna; Wen-Yu Lin; Albert Feng (Journal of Comparative Physiology A, 2001)

Free-field unmasking response characteristics of frog auditory nerve fibers: comparison with the responses of midbrain auditory neurons - Wen-Yu Lin; Albert Feng (Journal of Comparative Physiology A, 2001)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Temporal selectivity for complex signals by single neurons in the torus semicircularis of Pleurodema thaul (Amphibia: Leptodactylidae) - Mario Penna; Wen-Yu Lin; Albert S. Feng (Journal of Comparative Physiology A, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)